Biological carbon pump drives co-removal of phosphorus and heavy metals in karst lakes - Xiaolong Li; Mingyu Shao; Sibo Zeng; Liangxing Shi; Qian Bao; Haibo He; Mohamed Aboueldahab; Ziling He; Yanglan Ding; Changkai Tang; Jianting Wu; Junyao Yan (Water Research, 2027)

Printability and freeze–thaw durability of wheat-straw-fibre modified 3D-printed recycled aggregate concrete - Yuxin Zhao; Xinyue Xi; Yuanxun Zheng; Yate Li; Shiao Yan; Zichen Zeng; Qiao Dong (European Journal of Environmental and Civil Engineering, 2026)

Genome-wide identification of the OfMYC gene family and putative involvement of OfMYC10/16 in petal senescence via an EIL–ERF–ROS regulatory module - Hui Xia; Qinyu Yan; Ting Zhang; Jie Yang; Hongguo Chen; Xuan Cai; Jingjing Zou; Zeqing Li; Xiangling Zeng; Yingting Zhang (Postharvest Biology and Technology, 2026)

Road surface erosion in a Loess Plateau watershed: Roles of road conditions, upslope contributing areas, and hydrological connectivity - Mengmeng Li; Juying Jiao; Qian Xu; Xiqin Yan; Ziqi Zhang; Jun Liao; Zeng Yan; Wenting Zhao; Xiaohan Jiang; Na Deng (CATENA, 2026)

Tyrosine hydroxylase as a therapeutic target: insights from adrenergic nerve and TNBC cell interactions - Yichen Luo; Yanhong Han; Huilong Nie; Minghao Feng; Cuiting Wei; Xiuling Ma; Kefeng Li; Zhuangzhuang Zhang; Guangxue Wang; Wenjun Pan; Xueyang Li; Liutong Yi; et al. (Journal of Molecular Medicine, 2026)

Spatial transcriptomics reveals the molecular dynamics of follicular development in the yak ovary under high-altitude hypoxia - Xupeng Li; Yuan Li; Chunhai Zhang; Yufan Wang; Zhuo Chen; Ruilan Zeng; Ying Cen; Lixue Yang; Shi Yin; Yan Xiong; Xianrong Xiong; Jian Li (Theriogenology, 2026)

Five undescribed compounds isolated from Gerbera delavayi with their anti-inflammatory activity - Li Jiang; Yang Wang; Zeng-Dan Ran; Ding-Yan Lu; Rui-Xi Li; Jia Sun; Yong Huang; Xue Ma; Yong-Jun Li (Phytochemistry, 2026)

Zero-valent Fe reshapes microbial and viral communities, regulating arsenic bioavailability reduction in composting: Metagenomic and metaproteomic insights - Guangsheng Qin; Xiaolin Lu; Qiqiang Zhang; Yaling Peng; Linghu Zeng; Rongchun Huang; Yanan Luo; Shengfei Yan; Hui Liang; Zhengzhun Tan; Weijun Pan; Shasha Liang; et al. (Journal of Environmental Chemical Engineering, 2026)

A physics-guided neural surrogate framework for bridge weigh-in-motion based on influence-line superposition - Jian-An Li; Yan Zeng; Dongming Feng; Baoquan Wang; Yichao Xu (Engineering Structures, 2026)

Supramolecular reconstruction of rice straw lignocellulosic microfibrils into high-performance food packaging films - Haibo Huang; Zhen Zhang; Runhan Zhao; Yan Qing; Zhuozheng Yu; Yao Zhang; Zhanjiang Yu; Ming Li; Guangsheng Zeng; Zhihan Li; Yiqiang Wu (Carbohydrate Polymers, 2026)

Robust and self-healing flexible transparent electrodes based on nanocellulose-mediated dual-dynamic networks with capillary-driven junction welding - Bingyang Liu; Pengfei Li; Jinsong Zeng; Yan Zhang; Fei Li; Yujie Shi; Gensheng Xiao; Tieqing Su (Carbohydrate Polymers, 2026)

Integration of niche evolution and pre-adaptation shaped the diversity of Cypripedium (Orchidaceae) in subtropical and temperate regions since mid-Miocene times - Liu-Qiong Wei; Peng Zhou; Pei-Yang Zhang; Si-Xian Li; Bo-Ni Lai; Ru-Yang Ye; Ji-Hong Li; Yan Luo; Xiao-Hong Zeng; Yi-Zhen Liu; Xiao-Guo Xiang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Interpretable causal machine learning elucidates performance regulation via atomic Fe‑S synergistic pathways in Sulfidated zero‑valent Iron - Zimin Yan; Rupeng Wang; Zhiling Li; Tianyi Huang; Yunxia Zu; Xiaoxi Zeng; Di Cao; Bin Wu; Jun Huang; Shih-Hsin Ho; Aijie Wang (Water Research, 2026)

Transcriptomic and metabolomic analyses reveal cobalt-induced mitochondrial metabolic alterations in human cortical organoids - Xinhua Guo; Hao Li; Yan Huang; Lujun Zhao; Zhiqiu Wang; Xizhi Zhu; Pinli Zeng; Yina Huang; Hong Gao; Xiaobo Cen; Qian Bu (Toxicology, 2026)

Temperature-sensitive chlorophyll degradation uncouples degreening from other ripening traits and guides postharvest quality improvement in kiwifruit - Ameer Hamza Hafeez; Zheng Zhang; Ang Li; Zhebin Zeng; Yan Chen; Tiantian Li; Xiaomei Ji; Yi Wang; Zhongyan Wang; Yunjiang Cheng; Hamza Sohail; Di Feng; et al. (Postharvest Biology and Technology, 2026)

Functional characterization of PxUGT33W1 with abamectin response and reproduction in Plutella xylostella - Bingxue Li; Chao Xie; Minghui Yan; Bingwei Chen; Xiangdong Zeng; Xiyue Zhang; Guangyu Yu; Mengxue Luo; Shaoling Zhang; Minsheng You; Shijun You; Lei Xiong (Pesticide Biochemistry and Physiology, 2026)

Bacillus amyloliquefaciens K309 promotes copper detoxification in vivo through concerted biosorption and microbial metabolism - Mingyang Cheng; Yiran Shao; Tianming Niu; Yu Sun; Tianqi Fan; Chenxi Jiang; Minghan Li; Hongyuan Wang; Boshi Zou; Shuhui Fan; Mingxiao Liu; Jianzhong Wang; et al. (Journal of Hazardous Materials, 2026)

Deciphering the carrier potential of microplastics aged in freeze-thaw soils: Multiscale insights into mechanisms for antibiotic adsorption amplification - Wen-hao Yang; Jian-yong Wu; Kong-yan Luo; Ling-li Ma; Bin Yan; Jin-song Guo; Jie Zeng; Yi-zhi Pei; Jun-min Gao (Journal of Hazardous Materials, 2026)

Product-grade enrichment of byproduct deuterium in PEM natural water electrolysis for hydrogen production - Zezheng Zhang; Jinguang Cai; Chao Lv; Ning Zeng; Aojie Liu; Qin Li; Liuxin Yang; Rui Hou; Siyi Liu; Peilong Li; Yan Shi; Xiaopeng Wang; et al. (Journal of Cleaner Production, 2026)

Influence of organic-matter occurrence on hydrocarbon-generation timing in source rocks: Evidence from the Shahejie Formation, Dongying Sag, China - Peng-Yan Du; Jin-Gong Cai; Hui-Min Liu; Qian Chao; Zheng Li; Xu Li; Xue-Jun Wang; Jia-Zong Du; Xiang Zeng (Journal of Asian Earth Sciences, 2026)

Corrigendum to “In-situ forming carboxymethyl chitosan hydrogel containing Paeonia suffruticosa Andr. leaf extract for mixed infectious vaginitis treatment by reshaping the micro-biota” [Carbohydrate Polymers 339 (2024) 122255] - Shiami Jia; Shengting Huang; Rezhemu Jimo; Yongbu AXi; Yuanhui Lu; Ziling Kong; Jun Ma; Heran Li; Xiao Luo; Yan Qu; Kaijun Gou; Rui Zeng; et al. (Carbohydrate Polymers, 2026)

Spring deep flooding reduces methane emissions from paddy soils through combined physical, carbon pool, and microbial functional mechanisms - Kui Li; Dengming Yan; Aohui Sun; Chanyuan Qin; Ziheng Pang; Zhiyong Liu; Jin Zhou; Jianping He; Kainan Xiang; Kai Zeng; Yelan Yu; Zeheng Li; et al. (CATENA, 2026)

Computationally assisted combinatorial rational design of xylanase with improved thermostability and catalytic performance for lignocellulosic biomass hydrolysis - Yan Zou; Guoyu Liu; Xueying Zeng; Jia Liu; Haotian Wang; Jingtao Zhang; Hairong Hu; Guankai Hao; Jie Liu; Shenglin Duan; Peng Yuan; Xiuting Li (Bioresource Technology, 2026)

Deep degassing in the southeastern margin of the Tibetan Plateau: Fluid fluxes, sources, and tectonic implications of the Ganzi-Litang suture zone - Deyang Zhao; Xiaocheng Zhou; Miao He; Jiao Tian; Yao Yang; Ju Zhang; Jingchao Li; Jinyuan Dong; Yucong Yan; Zhaojun Zeng; Yuwen Wang (Applied Geochemistry, 2026)

YRD1km: A 1-km Hourly High-Resolution Regional Reanalysis Dataset over the Yangtze River Delta with Emphasis on Thermodynamic Structure - Yan-An Liu; Zhengyan Zhang; Tianyue Zeng; Zhenglong Li; Pengbo Xu; Juan Zhang; Bo Li; Jun Li (Advances in Atmospheric Sciences, 2026)
High-resolution atmospheric thermodynamic information is essential for resolving localized weather processes in complex urbanized regions such as the Yangtze River Delta (YRD). However, existing global reanalysis products are limited by coarse spatial resolution, constraining their ability to represent fine-scale thermodynamic structures. In this study, we develop YRD1km, a 1-km hourly regional thermodynamic reanalysis dataset for the YRD, generated through dynamical downscaling of ERA5 using the WRF model with a three-level nested configuration. The framework integrates optimized physical parameterizations, a combined observation and analysis nudging strategy, and updated high-resolution land-use information. The current dataset covers the summer seasons (June–August) from 2021 to 2023, a period characterized by frequent convection and strong land–atmosphere interactions. Comprehensive validation against dense surface and radiosonde observations demonstrates that YRD1km consistently outperforms ERA5 in near-surface temperature, relative humidity, and surface pressure, with reductions of approximately 35% in MAE and RMSE for temperature and humidity and more than 78% for surface pressure. Vertical evaluations reveal substantial improvements throughout the troposphere, particularly for moisture fields. YRD1km also exhibits enhanced temporal stability and reduced discontinuities associated with assimilation window transitions in ERA5. A severe convective case further illustrates its ability to resolve multi-level thermodynamic anomalies preceding convective initiation. Overall, YRD1km provides a physically consistent, high-resolution thermodynamic reanalysis framework that supports detailed weather diagnostics, urban meteorology studies, and future regional AI-based weather modeling applications.

Shifting the processing boundary: On-Farm Pulsed Electric Field Intervention (OFPI) for proactive bioburden reduction and functionalization of raw milk - Bing Yan; Lang-Hong Wang; Jin-Lin Cai; Xiao-Jun Zhang; Cai-Yun Wang; Jian Li; Rui Wang; Xin-An Zeng; Jian He (Trends in Food Science & Technology, 2026)

Targeting CX3CR1 inhibits silica-induced epithelial-mesenchymal transition and pulmonary fibrosis in mice via the NF-κB signaling pathway - Jiaxin Zhang; Yuhua Wang; Chuanyi Huo; Xukun Jiao; Xinying Zeng; Jingya Li; Zhonghui Zhu; Yifei Wang; Lin Tian; Yan Wang (Toxicology, 2026)

An LLM-based framework to evaluate the suitability and accessibility of campsites: A case study of Changsha, China - Yu Man; Yan Shi; Ying Zeng; Minghui Li; Jingsha Han (Sustainable Cities and Society, 2026)

Discovery of isotope 153Hf near the proton drip line via isochronous mass spectrometry: extending the nuclear landscape with HIAF - Hongfu Li; Min Zhang; Hongyang Jiao; Xing Xu; Chaoyi Fu; Jinyang Shi; Jiahao Lv; Xu Zhou; Yuanming Xing; Mingze Sun; Yuhu Zhang; Xiaohong Zhou; et al. (Science Bulletin, 2026)

Dimeric 2-(2-phenethyl)chromones from agarwood of Aquilaria malaccensis - Wei Li; Xian-Yun Yan; Hao Wang; Li Yang; Sheng-Zhuo Huang; Jun Zeng; Fei Wu; Guang-Ying Chen; Wen-Li Mei; Lin-Fu Liang; Hao-Fu Dai; Yong-Min Zhang (Phytochemistry, 2026)

Decoding genetic basis of nitrogen use efficiency in maize using AI-generated deep phenotypes - Haoyan Yang; Lingju Zeng; Xiangjian Gou; Yang Shao; Xianlong Song; Shuang Zhang; Xiaoyan Qian; Zhenwei Zhang; Xiao Wang; Haitao Li; Bo Peng; Juliet Nkiruka Anyanwu; et al. (Molecular Plant, 2026)

Associations between prenatal per- and polyfluoroalkyl substance exposure and maternal fatty acid homeostasis: Nonmonotonic, compartment-specific patterns in plasma and red blood cells - Chuxin Liao; Yitian Zhang; Yingxuan Zeng; Peishan Liu; Shutian Zhong; Yan Mu; Yingxia Wu; Tiange Li; Zhengzheng Zhou; Zhifeng Zhou (Journal of Hazardous Materials, 2026)

Nitric acid-modified co-pyrolyzed biochar from gentamicin mycelial residue and biomass regulates cattle manure composting: Reducing carbon loss and enhancing humification - Yingjin Song; Huiling Niu; Yamei Zeng; Guanyi Chen; Zeng Dan; Beibei Yan; Lan Mu; Yuxing Luo; Yinjie Zhong; Sheng Xu; Qingyi Li; Anna Jin (Journal of Environmental Management, 2026)

Antarctic krill oil Pickering emulsions stabilized by zein/sodium caseinate-xanthan gum nanoparticles: stability, bioaccessibility, and anti-inflammatory activity - Yan Zeng; Yuchan Chen; Minmin Zeng; Ying Li; Jianxin Chai; Ye Peng; Quancai Sun; Kun Hu (Food Research International, 2026)

Effective photodynamic inactivation of curcumin in combination with ethylenediaminetetraacetic acid against Burkholderia gladioli pathovar cocovenenans - Xiu-Xia Tian; Jia-Jun Yan; Rui Huang; Quan Zhou; Qi-Ying Zeng; Yu-Ming Jiang; Zi-Hui Chen; Hai-Yan Wang; Bai-Sheng Li; Yong-Ning Wu; Wei-Liang Wu (Food Research International, 2026)

Unraveling the impact of food processing technologies on postbiotic bioactivity, food matrix interactions, and human health outcomes - Junxin Zhao; Mengfei Duan; Ruiying Xu; Yumeng Cheng; Jinheng Li; Deguo Wang; Xianghui Yan; Ping Yu; Zheling Zeng; Yunzhi Lin; Yoshimitsu Masuda; Ken-ichi Honjoh; et al. (Food Bioscience, 2026)

Contrasting impacts of policy interventions and population mobility on organic aerosols and oxygenated volatile organic compounds in Beijing - Yu Zhang; Weiqi Xu; Wei Zhou; Jintai Lin; Mengying Wang; Yan Li; Siqi Zeng; Ziyi Zhang; Xiaomin Cheng; Yang Yang; Yele Sun (Environmental Pollution, 2026)

Impacts of urban open space environments on residents' health: A perspective on potentially toxic metals in dust - Yue Zeng; Qiang Ban; Junjie Yu; Changchun Qiu; Yajie Jiang; Xinyu Liu; Dian Lin; Shiqi Yan; Yunqin Li; Binxin Wu; Wei Yu; Rong Yu (Environmental Pollution, 2026)

Multi-omics analysis of LFA-1 peptide-functionalized silk fibroin nanofibers targeting RPE and activating AMPK–HO-1 signaling to suppress pyroptosis and alleviate diabetic retinopathy progression - Zepeng Xu; Chenxiao Lu; Zhenting Wang; Yaojia Liu; Guangmeng Mo; Yan Yang; Xiaoli Lu; Kunmeng Li; Yihuan Zeng; Yan Dong; Ni Tian (Chemical Engineering Journal, 2026)

Unraveling the critical role of ClO• in the degradation of emerging organic contaminants by far-UVC/chlorine: Radical contribution assessment and influence of water matrix - Ping Li; Ge Zeng; Wenjun Zhang; Qiuling Lu; Haonan Lu; Kai Wang; Jun Ma; Yan Zhang; Tao Yang (Chemical Engineering Journal, 2026)

QTL mapping for berry firmness and functional characterization of a prioritized candidate gene VvNAC83 in grape - Nan Jia; Yonggang Yin; Changjiang Liu; Bin Han; Yan Sun; Shuli Han; Xinyu Wang; Pengtao Shi; Qingming Zeng; Minmin Li (Theoretical and Applied Genetics, 2026)

Proteomic comparison of human neural cell-derived extracellular vesicles and parental cells from Alzheimer’s disease and cognitively normal individuals - Jia-Yan Xin; Jie Liu; Hao-Min Dong; Hai-Lun Yu; Zhong-Song Xiao; Jian-Ni Hu; Qiu Jiang; Yu-Peng Zhu; Lin Feng; Yun Feng; Yu-Juan Jia; Zi-Yu Yuan; et al. (Science China Life Sciences, 2026)

Effects of Typical Karst Tourist Town on the Lijiang River Water: From Heavy Metals to N-Nitrosamines - Yuanyu Shan; Yuru Su; Xinli Xing; Bingquan Zhu; Honghu Zeng; Yuan Zhang; Junyu Li; Xiaoyu Yan; Wenwen Chen; Benjian Li (Journal of Earth Science, 2026)

Soil carbon redistribution and micronutrient constraints drive cotton yield decline under long-term fertilization in desert agroecosystems - Jingming Yan; Rapkat Sabit; Zhihao Zhang; Yanju Gao; Guangxing Zhao; Xinping Dong; Yuhe Zhu; Xiangyi Li; Corina Graciano; Waqar Islam; Fanjiang zeng (Agriculture, Ecosystems & Environment, 2026)

Intermittent aeration-driven iron cycling for the remediation of waste pit-sealing mud: metabolic mechanisms and model evaluation - Xiangshan Zeng; Xinyi Wu; Dandan Yan; Changhui Hu; Jinlai Yuan; Ruiqi Li; Yan Wang; Ming Dou; Yafei Yang (Environmental Geochemistry and Health, 2026)

Non-monotonic regulation of collective dynamics by group size and speed in schooling fish - Junjia Zeng; Ke Xie; Yanfei Yang; Sijing Chen; Gowena Ling Yi Goh; Yacheng Deng; Ning Li; Tao Zhou; Fei Pu; Wenjing Lu; Kuoqiu Yan; Peng Xu (Aquaculture, 2026)

Development and Application of Thermo-Fluid–Solid Coupling Seepage Experimental System of Coal Rock Cracked by Controlled Electric Pulse - Fazhi Yan; Changjiong Gao; Wei Yang; Jiang Xu; Shoujian Peng; Tao Zeng; Yihan Wang; Ziwen Li (Rock Mechanics and Rock Engineering, 2026)

PD-1/PD-L1 inhibitor induces systemic inflammation and alters cardiac lipid metabolism in C57BL/6 J mice - Cong Ye; Zhi-Ting Jiang; Chen Yan; Xin-Ran Li; Yu-Hua Zhu; Ling-Yu Zeng; Lan Luo (Human Cell, 2026)

Caspase-1 boosts immunotherapeutic efficacy via induction of CD8+ T cell cytotoxicity through interleukin-18 secretion in epidermal growth factor receptor-tyrosine kinase inhibitor-resistant non-small cell lung cancer - Yajie Cheng; Jiawen Tang; Yangyi Li; Chunsheng Wang; Mini Zhang; Zihang Zeng; Jianguo Zhang; Qingwei Wang; Jiang Luo; Fajian He; Wen Ouyang; Jing Yu; et al. (Science China Life Sciences, 2026)

Sotagliflozin pretreatment attenuates acute LPS-induced depression-like behavioral abnormalities and modulates the gut microbiota–immune–brain axis - Jun Zeng; Lihuimei Zhou; Lei Liao; Daobin Wu; Rongying Yang; Chunda Zhang; Zhou Bai; Xinrong Fan; Xiangyu Zhou; Chunxiang Zhang; Jiafu Li; Lijia Chang; et al. (Psychopharmacology, 2026)

Dysfunctional Mitochondria in Microglia Drive Cognitive Aging and Neurodegeneration via cGAS–STING - Guanqin Ma; Erlin Wang; Xiaoxu Yan; Xiang-Xiong Xu; Xiaohong Li; Xueling Ma; Wan-Hua Yang; Jianxiong Zeng; Xiaochun Xie (Neuroscience Bulletin, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Metabolomic analysis and functional validation of coumarin metabolites in Chinese cabbage’s defense responses against Alternaria brassicae - Qi Zeng; Chunting Liu; Huishen Wang; Jingwen Jia; Xuemei Yan; Xifan Liu; Yuxuan Qiu; Xiaowu Wang; Baohua Li (Plant Science, 2026)

Norian (late Triassic) Foraminifera from the Baoshan Block, Yunnan Province (China) and their response to palaeoenvironmental changes - Shuqin Zhou; Muhui Zhang; Weiping Zeng; Haishui Jiang; David P.G. Bond; Paul B. Wignall; Yan Chen; Hanxiao Li; Xulong Lai (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Single-cell RNA sequencing reveals cadmium-induced cell-type-specific mechanisms of developmental neurotoxicity in human cortical organoids - Yan Huang; Zhiqiu Wang; Hao Li; Zhong Wang; Guiming Luo; Lujun Zhao; Pingli Zeng; Xizhi Zhu; Aiqin Xue; Guohui Bian; Daili Song; Maoyang He; et al. (Journal of Hazardous Materials, 2026)

The Hippo–Yki pathway governs growth and cell fate in the posterior silk gland of the silkworm - Yan Ma; Zhiyong Zhang; Wenhui Zeng; Zhou Fang; Xin Yu; Lin Cheng; Zehui Ma; Qipeng Zeng; Dena Jiang; Yiyun Tang; Jie Hu; Chen Zhao; et al. (Insect Biochemistry and Molecular Biology, 2026)

Photosynthesis-induced carbonate precipitation amplifies calcium isotope differences between surface water and groundwater in carbonate-rich watersheds - Mingyu Shao; Zaihua Liu; Sibo Zeng; Ding He; Zhaofeng Zhang; Hao Yan; Qian Bao; Liguo Tang; Xin Li; Hailong Sun; Junyao Yan; Liangxing Shi (Geochimica et Cosmochimica Acta, 2026)

Structural and rheological modulation of low-oil emulsions by deamidated pea protein–gum arabic coacervates for reduced-fat applications - Lijuan Luo; Ping Li; Yuanyuan Deng; Guang Liu; Yan Zhang; Xiaojun Tang; Pengfei Zhou; Zhihao Zhao; Jiarui Zeng; Mingwei Zhang (Food Chemistry, 2026)

Impact of high-pressure processing on the degradation kinetics and bioactivity of resveratrol - Wen-Chien Lu; Yu-Tsung Cheng; Yung-Jia Chan; Shu-Ju Chen; Yan-Zhen Wu; Zeng-Chin Liang; Po-Hsien Li (Food Chemistry, 2026)

Variations in semi- and non-volatile organic substances during physical recycling and their migration from rPET bottles - Yi-Qi Liu; Yan Zeng; Shao-Fu Zeng; Zhi-Wei Wang; Lei Zhu; Li-Li Jin; Gui-Qin Shang; Gui-Hua Liu; Chang-Ying Hu (Food Packaging and Shelf Life, 2026)

Comparative analysis of chemical compositional profiles and immunomodulatory activity of ginseng in different habitats - Chen-Yue Zeng; Quan-Kuan Dai; Hua-Ze Wu; Ao Li; Yong-Lin Chen; Qing-Hui He; Dan Tang; Hong-Yan Ma (Journal of Natural Medicines, 2026)

Transport of Emerging Contaminants Through Cell Lipid Membranes in Aquatic Systems - Ying Li; Xinyu Zhang; Shuangkai Yang; Xin Zeng; Xinyue Liang; Yaxin Guo; Yan Wang; Zhong Weng; Precious M. Ojo; Xiaofeng Peng; Shuxia Xu; Wen Zhang; et al. (Current Pollution Reports, 2026)

Fe-N-C-supported LaFeO3 heterojunction electrodes for efficient copper and fluoride removal in symmetric capacitive deionization - Shaojian Xie; Yujia Wang; Rui Zhang; Lei Huang; Jia Yan; Zhenxin Chen; Hongguo Zhang; Meng Li; Hongbo Zeng (Water Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Numerical investigation of vortex-induced vibration control in square cylinder using synthetic jets - Shiqing Li; Meihua Xia; Shuxuan Cai; Yan Han; Peng Hu; Lingwei Zeng (Ocean Engineering, 2026)

Efficient persulfate activation via a novel layered porous biochar enhanced with nano-zero-valent iron loading and synergistic sulfidation modification: Performance and mechanism - Lei Shen; Zichen Qin; Yuanding Shi; Yan Li; Pengyao Guo; Jinwei Zhang; Yijun Shen; Chun Yang; Yuchen Zeng; Dongxiao Sun; Zhiqiang Dong; Lei Ding (Journal of Water Process Engineering, 2026)

Synergistic benefits of polysaccharide-essential trace element complexes via coordination: Unraveling the links among structure, antioxidant activity, bioavailability, and gut microbiota - Yueqin Li; Ruonan Yan; Shufeng He; Tchouli Noufeu; Xiaoqun Zeng; Qiwei Du; Zhen Wu; Daodong Pan (Food Chemistry, 2026)

Precise mapping of high-temperature adult-plant stripe rust resistance gene Yr52 in wheat - Mingjie Xiang; Yibo Zhang; Shuaiwei Cao; Jiangna Han; Haohao Yan; Chenfang Wu; Jiale Li; Xunying Yuan; Xiangrui Cheng; Shuqing Yang; Zhuang Li; Xiaoting Wang; et al. (Theoretical and Applied Genetics, 2026)

Sabulicella flocculans sp. nov., a Floc-Forming Bacterium of the Genus Sabulicella Isolated from Activated Sludge - Ansi Jiang; Xinjing Du; Yaqi Liu; Dian Jiao; Han Chen; Xin Wang; Yong Zhang; Shanhui Wang; Wei Li; Haiyan Zeng; Yan Huang; Dongru Qiu (Current Microbiology, 2026)

Magmatic parent fluids sources and transport in a strike-slip fault zone: Hydrogeochemical evidence from the Southwestern Tibetan plateau - Yunfei Bai; Zheming Shi; Xiaocheng Zhou; Jinyuan Dong; Chen Wu; Guangcai Wang; Shaomin Liu; Lizhi Wang; Miao He; Jingchao Li; Jiao Tian; Yucong Yan; et al. (Applied Geochemistry, 2026)

Polyprenylated acylphloroglucinols from Hypericum monogynum and their reversal of multidrug resistance in MCF-7/ADR cells - Yan-Rong Zeng; Peng Zhao; Jing-Yi Yin; Hong-Jin Ban; Zhan Feng; Yu-Xiang Li; Min Yang; Jing Tan; Cheng-Jian Tan; Jue Yang; Xiao-Jiang Hao; Chun-Mao Yuan (Molecular Diversity, 2026)

PDG_DB: A comprehensive database unveils environmental distribution patterns of plastic-degrading genes via large-scale multi-omic data analysis - Jiayu Zhang; Zuowu Zhang; Zehan Shen; Zehui Yu; Jiao Chen; Li Zeng; Dongyi Li; Xing Yan; Bing Li; Jonathan W.C. Wong (Water Research, 2026)

Effects of pig bone‑derived hydroxyapatite on contaminated manure composting: Humification, copper/zinc immobilization, and high‑risk antibiotic resistance genes - Jiaxin Liu; Chaoqun Yan; Shulin Zhang; Guoquan Zeng; Shiyu Ma; Jingtong Dai; Huayan Huang; Yanglong Li; Feifan Yu; Yu-xian Shangguan; Heng Xu; Huakang Liu (Journal of Hazardous Materials, 2026)

Synergistic abatement of nitrogen oxides and volatile organic compounds using novel dual-functional catalysts: A critical review - Yating Li; Qiyan Zeng; Shanshan Cai; Minghui Jiang; Xingyu Jiang; Leneng Yang; Kai Yan; Paolo Centomo; Carlo Meneghini; Daiqi Ye; Yulong Shan; Peirong Chen (Journal of Environmental Sciences, 2026)

Inhibitory effect of pulsed electric field pretreatment on acrylamide formation in air-fried French fries and its mechanism - Jian Li; Yue-Wei Huang; Yi-Tong Li; Shi-Yin Luo; Wei-Yan Xiong; Jin-Hua Wang; Jun-Hu Cheng; Ting-Shi He; Xin-An Zeng (Food Research International, 2026)

Sensitivity analysis and multi-objective particle swarm optimization (MOPSO) of a hollow fiber membrane module for the solar-based heating and humidification system - Si Zeng; Peng Peng; Nan-Feng Li; Cai-Hang Liang; Rong-Hui Qi; Yan-fang Dong; Yu-Kui Men; Jia-Hui Li; Gui-Yin Li (Energy and Buildings, 2026)

CuI additive induced co-regulation of ion transport and interfacial chemistry in poly(ethylene oxide)-based solid-state electrolytes for improved battery performance - Kepan Yan; Xuexiao Chen; Haoliang Huang; Zicong Yu; Jingcheng Lu; Zhipeng Yu; Sitaramanjaneya Mouli Thalluri; Jinfeng Zeng; Wei Wang; Fei Lin; Yijuan Li; Weicai Zhang; et al. (Chemical Engineering Journal, 2026)

Next-generation chitosan biodegradable films reinforced with bioactive acid-DES: A sustainable solution for improved mechanical, antibacterial, and anti-browning properties - Dehong Lu; Huimin Yao; Nouman Ali Shah; Sajid Ali; Li-Yan Zeng; Ping Shi; Yuan-Sen Liu; Ziru Dai; Hafiz Umer Javed (Carbohydrate Polymers, 2026)

Preparatory Activity Indexes Motor Memory in the Motor Cortex - Xiao–Lin Shen; He–Xin Zhao; Yu–Hao Xiao; Yong–Xiang Wang; Li–Zhang Zeng; Hong–Yan Geng (Neuroscience Bulletin, 2026)

Chitinimonas violaceus sp. nov., a violacein-producing and floc-forming bacterium isolated from the activated sludge of a municipal sewage treatment plant in Zhuhai, China - Yan Huang; Yaqi Liu; Ansi Jiang; Yong Zhang; Diao Jiao; Xin Wang; Wei Li; Haiyan Zeng; Dongru Qiu (Antonie van Leeuwenhoek, 2026)

Two new menthane monoterpene derivatives isolated from Hypericum monogynum - Yan-Rong Zeng; Hong-Jin Ban; Jing-Yi Yin; Zhan Feng; Ya-Nan Li; Yan Liu; Xiao-Jiang Hao; Chun-Mao Yuan (Phytochemistry Letters, 2026)

Sublethal effects of typical neonicotinoids exposure on Drosophila melanogaster: Insights from phenotypic abnormalities to molecular mechanisms - Fang Li; Chen Yan; Yitian Min; Wenbin Li; Siying He; Weiping Xiong; Zhuotong Zeng; Biao Song (Pesticide Biochemistry and Physiology, 2026)

Presymbiotic activation of karrikin signaling creates a permissive state for arbuscular mycorrhizal symbiosis by derepressing the NSP1–NSP2–SLR1 transcriptional complex in rice - Kai Hong; Xueying Yang; Yiqing Tan; Yonggang Liu; Qianwei Xia; Longjun Zeng; Linyuan Zou; Ke Wan; Ya Zhang; Shujing Kang; Tao Huang; Wanqing Lv; et al. (Molecular Plant, 2026)

Magma flare-up and Nd isotopic excursion records from the Himalaya: Implications for an early Paleozoic Cordilleran-type orogen - Lilong Yan; Lingsen Zeng; Li-E Gao; Linghao Zhao; Haitao Wang (Lithos, 2026)

Ginkgetin alleviates UV-induced skin photoaging by reducing oxidative stress and promoting DNA repair via AKT-mediated homologous recombination repair - Yiting Zhao; Liyuan Zhou; Shuzhan Shen; Xidie Yin; Qihang Chang; Yu Yan; Chunying Li; Zhi Cao; Haiyan Zhang; Qingyu Zeng; Xiuli Wang; Peiru Wang (Journal of Photochemistry and Photobiology B: Biology, 2026)

Arsenic species-adaptive removal from groundwater by carbon foam-supported Mn-doped FeOOH with precisely regulated Fe/Mn ratios - Heng Li; Tian Liang; Qian Zeng; Zhigang Wang; Ying Xiong; Bing Yan (Journal of Environmental Management, 2026)

High-CH4-selectivity CO2 photoreduction enabled by in-situ constructed S-scheme Cs2CuCl4/NiAl-LDH heterojunction - Hai-bing Zhao; Yue Shu; Sheng-ning Zeng; Wen-rong Ouyang; Duo-fu Li; Hong Zhong; Wei Huang; Yan Sui (Journal of Environmental Chemical Engineering, 2026)

A pilot-scale certification for copper recovery from waste printed circuit boards by NH3-NH4Cl-CuSO4 slurry electrolysis: perspective but challenge - Qian Liang; Ling Hu; Xiangfei Zeng; Jinchuan Qin; Yunhui Han; Huimin Yang; Huan Li; Xingyu Luo; Shuyuan Chen; Shaoqin Chen; Jiqin Wang; Jiancheng Shu; et al. (Journal of Environmental Chemical Engineering, 2026)

Electrochemical remediation technologies for persistent organic pollutants in soil and water - Ping Zhang; Qin Zeng; Longchun Yan; Hongyu Xiao; Zhihui Yang; Yuchun Li (Environmental Research, 2026)

A dual-gradient Janus architecture: Engineering aerogel sensors with high sensitivity and wide linear range for human-machine interaction - Xianghui Zeng; Yao Lu; Junwei He; Liming Zou; Zezhao Ding; Yang Fan; Yan Vivian Li (Chemical Engineering Journal, 2026)

An intrinsic lignin-cellulose separator with tunable ion sieving and dissolution resistance toward dendrite-free aqueous zinc-ion batteries - Yusheng Lei; Pengpeng Li; Biliu Lan; Yutong Lu; Shunmin Yi; Yanfei Zeng; Tonghan Yang; Ketong Luo; Dongliang Yan; Zhian Qiu; Shaohui Hu; Qifan Liu; et al. (Chemical Engineering Journal, 2026)

Blast Fragmentation Prediction Model Based on Energy Fan Theory - Dongqiang Liu; Xinhua Zeng; Ming Chen; Peng Zhang; Jiangping Yan; Wenbo Lu; Fengze Zhao; Mingze Li; Zhanzhi Tan (Rock Mechanics and Rock Engineering, 2026)

Dendrobium officinale polysaccharides alleviate atopic dermatitis in vivo and in vitro through inhibition of inflammation and mitochondrial dysfunction - Bijun Zeng; Gufen Jiang; Chang Wang; Hongxia Zhou; Yujin Zhang; Yi-ning Yan; Zi Chen; Lang Zhang; Xiaoyu Li; Mengzhou Xie; Zhibo Yang; Haizhen Wang (Journal of Molecular Histology, 2026)

Activity of the Fendong Buried Fault in the Linfen Basin, Shanxi Province, China: significance of neotectonic evolution and future seismic risk - Guirang Hu; Zihong Li; Xiaobing Yan; Jinyan Zeng; Bin Li; Ruiguo Ren; Xuejing Hao (International Journal of Earth Sciences, 2026)

The enhanced nitrous oxide emissions are driven by prokaryotic ammonia oxidizers and nirK-denitrifiers under various combinations of nitrogen and rice straw in a paddy soil - Chunyan Wu; Yinxiu Liu; Xu Tang; Tao Sun; Che Tan; Yu Zeng; Yan Li; Chang Yin; Yongchao Liang (Soil Ecology Letters, 2026)

Thermal Cracking Properties of Granite Considering Mineral Heterogeneity Based on a Thermo-Mechanical Grain-Based Model - Yan Zhang; Minglang Zou; Zhilong Zhang; Junqian Ren; Tianbin Li; Peng Zeng; Chunchi Ma (Journal of Earth Science, 2026)

An Improved LightGBM model with ADASYN and Whale Optimization Algorithm for Rockburst Intelligent Prediction - Yan Zhang; Jin Qiao; Tianbin Li; Chunchi Ma; Peng Zeng; Shaojun Li; Minglang Zou; Xiangsheng Zheng (Rock Mechanics and Rock Engineering, 2026)

Sustainable postharvest management practices for kiwifruit: Principles, approaches, and future directions - Qinhong Liao; Xiaojiao Li; Shixian Zeng; Wenxuan Chen; Ping Huang; Zihao Wang; Chi Yan; Qiqiang Wu; Qiuhong Niu; Yong Wang; Zhenshuo Wang (Postharvest Biology and Technology, 2026)

Genome-wide identification of the laccase gene family in wheat (Triticum aestivum L.) during Fusarium pseudograminearum infection - Li-Yu Chen; Yi Diao; Ju-Hong Ma; Xiang-Xue Zhang; Rui Li; Yan Liu; Hong-Tao Tang; Zhi Wang; Sha Gao; Rui-Huan Xu; Zhen-sheng Kang; De-Jun Han; et al. (Plant Science, 2026)

New mechanistic insights into the antiviral candidate CA-P: Activation of plant redox-mediated defense and suppression of virus biosynthesis - Rong-Shuang Luo; Yan-Wei Huang; Yu-Cheng Gu; Long Cheng; Wu-Bin Shao; Yan-Mei Liao; Qian Guo; Dan Zeng; Hong-Mei Xiang; Xiang Zhou; Li-Wei Liu; Zhi-Bing Wu; et al. (Pesticide Biochemistry and Physiology, 2026)

Posttranslational regulation of TOR kinase activity controls resource allocation between plant growth and immunity in Arabidopsis - Jianwei Li; Ran Wang; Chenying Li; Xijie Guo; Qinghong Li; Zhixuan Wu; Shanshan Zeng; Fan Qi; Yuchen Wang; Zhiyi Jia; Weiwei Yu; Zeming Huang; et al. (Molecular Plant, 2026)

Tectonic controls and earthquake response of thermal fluid geochemistry in southern Yunnan, southeastern Tibetan Plateau - Chenhua Li; Xiaocheng Zhou; Miao He; Zhaojun Zeng; Yuwen Wang; Jiao Tian; Yucong Yan; Bingyu Yao; Hejun Su; Ruigang Li (Geothermics, 2026)

The mechanism of enhanced technofunctionality of wheat aleurone layer sourdough fermentation by interaction of exopolysaccharides and gluten proteins - Chenchen Yan; Fanrong Zeng; Yisheng Du; Dandan Li; Chong Xie; Runqiang Yang; Pei Wang (Food Chemistry, 2026)

Enhancement of protein gelation and nutritional properties in pea protein gels through enzymatic deamidation - Lijuan Luo; Ping Li; Yuanyuan Deng; Guang Liu; Yan Zhang; Xiaojun Tang; Pengfei Zhou; Zhihao Zhao; Jiarui Zeng; Mingwei Zhang (Food Hydrocolloids, 2026)

Flexural performance of CFRP grid-reinforced ultra-high performance concrete (UHPC) plates under cyclic incremental loading - JinJing Liao; Haotian Li; Yu Zheng; Linna Geng; Yan Zhuge; Jun-Jie Zeng (Engineering Structures, 2026)

Oxygen vacancy engineered M0.5Ni0.5Fe2O4 for enhanced chemical looping combustion performance - Xinyu Li; Jianshuai Li; Lina Wang; Lei Liu; Yan Lin; Shenglong Teng; Yiwen Song; Dewang Zeng; Yu Qiu (Chemical Engineering Journal, 2026)

Recombinant Bacillus subtilis Displaying DHAV-1 VP1 Protein as a Dual-Function Probiotic: Evaluation of Immunological Efficacy, Growth Performance, Antioxidant Capacity, and Intestinal Health in Cherry Valley Ducks - Bin Chen; Yicen Tang; Lihui Huang; Zhenhua Wang; Jianzhen Li; Mengwei Zhang; Yang Yang; Dongmei Zhang; Bo Jing; Yan Zeng; Xueqin Ni; Jinlong Yang; et al. (Probiotics and Antimicrobial Proteins, 2026)

Low-temperature mineral engineering stabilizes anchored cobalt sites for ultrafast antibiotic destruction via electron transfer-driven radical/nonradical synergy - Liyao Ren; Ran Liu; Runbin Zeng; Lingling Cao; Wenyu Wang; Xuguang Li; Xing Xu; Yanxia Zhao; Liangguo Yan; Yanfei Li; Wen Song (ENGINEERING Environment, 2026)

Safe nitrogen boundaries for sustainable pomelo production: A case study in the hilly regions of southern China - Ziwei Luo; Ran Li; Xiaotong Hu; Yedong Liu; Zhiyuan He; Ruixiang Yang; Zhixiong Zeng; Yingzhe Zeng; Bingkun Lu; Xiaojun Yan; Liangquan Wu (Agriculture, Ecosystems & Environment, 2026)

Pathogenicity of Porcine reproductive and respiratory syndrome virus in the reproductive system of female piglets: Pathological damage to the uterine horns and developmental arrest - Yi-Xin Yan; Ying Guan; Lei Zhao; Han-Yu Li; Tong Xu; Li-Na Shao; Si-Yuan Lai; Yi Qing; Liang-Peng Ge; Zuo-Hua Liu; Jing Sun; Xiu Zeng; et al. (Veterinary Microbiology, 2026)

Vitamin C rescues embryonic developmental arrest caused by maternal Kdm2a deficiency via regulating PTEN/PI3K/AKT axis - Qinhui Yang; Yumian Xie; Ying Cen; Ruilan Zeng; Yuan Li; Xupeng Li; Yan Xiong; Honghong He; Shi Yin; Jian Li; Xianrong Xiong (Theriogenology, 2026)

TRAF7 protects against acute lung injury by promoting K6-linked ubiquitination of AKT - Jia Wang; Meng-Liu Zeng; Ya-Zhou Sun; Xu-Tao Zhang; Xin-Yan Li; Wei-Yi Qu; Wei Li; Jia-Yi Liu; Xu Cheng; Jun Zhang; Han Tian; Hui Liu; et al. (Science Bulletin, 2026)

A novel context-aware deep learning framework for ship radiated noise recognition - Di Zeng; Yuning Li; Xianli Pan; Shefeng Yan (Ocean Engineering, 2026)

A triple-functional NiCo2S4/Mn0.2Cd0.8S/Cu7S4 heterojunction for superior photothermal-assisted photocatalytic H2 evolution - Yan Xiong; Ya Li; Ya-Nan Wu; Qun-Zeng Huang (Journal of Environmental Chemical Engineering, 2026)

Insight into greenhouse gas emission in freshwater aquaculture ponds in Jiangsu Province: Variation due to species used and ponds management practice - Yifan Li; Hongyu Wang; Qingfei Zeng; Erik Jeppesen; Xiaohong Gu; Jie Yan (Journal of Environmental Sciences, 2026)

Cold plasma technology in food Systems: Mechanisms, multifunctional applications, and pathways to industrial adoption - Lang-Hong Wang; Haiqian Xu; Bing Yan; Boru Chen; Xin-An Zeng; Yanyan Huang; Jian Li (Food Control, 2026)

Radial growth resilience of temperate deciduous oaks to drought events across aridity gradients in the southern Loess Plateau, China - Xiaoqi Chen; Xiaomin Zeng; Xiaohong Liu; Huiyue Yan; Quanxi Li; Mao Wei (Dendrochronologia, 2026)

A tri-component hydrogel composed of Bletilla striata polysaccharide, carboxymethyl chitosan and cinnamaldehyde: Potent enhancement of diabetic wound healing - Li Liu; Aimin Yan; Jia Zeng; Shaohui Geng; Xinxin Li; Guangrui Huang (Carbohydrate Polymers, 2026)

Dynamic evolution of organic aerosols and gaseous compounds from thirdhand smoke - Liu Yang; Wei Zhou; Weiqi Xu; Siqi Zeng; Zijun Zhang; Bo You; Yan Li; Long Jia; Yi Zhang; Xi Chen; Yele Sun (Building and Environment, 2026)

Hierarchical Framework for Reservoir Co-management: A Cross-scale Reservoir Dispatch Paradigm Balancing Energy and Morphogenic Flow Needs - Hong Zeng; Tian-Yao Zhang; Yi-Ming Liao; Guang-Wen Ma; Ji-Dong Li; Wei-Bin Huang; Yan-Mei Zhu; Shi-Jun Chen (Water Resources Management, 2026)

Cataract Aggravates Alzheimer-Like Pathologies and Cognitive Deficits in an APP/PS1 Mouse Model - Zhao Geng; Zhong-Yuan Yu; Jun Tan; Xuan-Yue Wang; Gui-Hua Zeng; Jiang-Hui Li; Yu-Di Bai; Xiao-Qin Zeng; Yu-Peng Zhu; Cheng-Rong Tan; An-Yu Shi; Yu-Hui Liu; et al. (Neuroscience Bulletin, 2026)
Clinical investigations have suggested a potential link between cataracts and Alzheimer’s disease (AD). However, whether cataract has an impact on the progression of AD remains unclear. The objective of this research was to determine the relationship between cataracts and AD. A cataract model was established in APP/PS1 [mutant amyloid precursor protein (APP) and a mutant presenilin-1 (PS1) gene] mice via lens puncture. Behavioural assays were used to evaluate cognitive function. Immunohistochemistry, immunofluorescence, and enzyme-linked immunosorbent assays (ELISA) were applied to detect AD-related pathology. Visual signals were markedly obstructed following surgery to induce cataracts, and these mice presented an increased cerebral amyloid-beta (Aβ) load, while no significant alterations in the levels of enzymes associated with Aβ metabolism were detected. In addition, compared with control mice, cataract model mice presented increased astrogliosis and microgliosis, along with elevated levels of proinflammatory factors. Moreover, cataract model mice presented more pronounced cognitive impairments than did control mice. Our study offers experimental confirmation that cataract considerably contributes to the pathogenesis of AD, thereby emphasizing the importance of visual signals in maintaining cognitive well-being.

Brachymonas moutaii sp. nov., a floc-forming bacterium isolated from a distillery wastewater treatment plant - Yaqi Liu; Hui Wang; Ansi Jiang; Junmei Wu; Bi Chen; Yong Zhang; Siliang Yuan; Yan Huang; Haiyan Zeng; Xin Wang; Dian Jiao; Wei Li; et al. (Antonie van Leeuwenhoek, 2026)

A Conserved Bactericidal Permeability-Increasing Protein (BPI) Mediates Immune Sensing and Host Defense in the Hong Kong Oyster (Crassostrea hongkongensis) - Laiba Shafique; Yuwei Zhao; Muhammad Farhan Khan; Cheng Huang; Li Li; Peng Zhang; Peng Zhu; Da Zeng; Xueyu Yan; Bin Gong; Yongyan Liao; Youhou Xu; et al. (Fishes, 2026)
The bactericidal permeability-increasing protein (BPI) and lipopolysaccharide binding protein (LBP) are fundamental to innate immunity. However, their functional diversity and evolutionary conservation in ecologically crucial invertebrates, such as oysters, remain largely understudied. In this study, we identify and characterize a novel homolog of BPI/LBP, designated as ChBPI/LBP in the Hong Kong oyster (Crassostrea hongkongensis). Through structural and phylogenetic analysis, we identify ChBPI/LBP as a distinct member of the BPI protein family, with a high isoelectric point (pI of 9.26), indicating potent cationic BPI-like bactericidal function. We found that ChBPI/LBP is constitutively highly expressed at mucosal sites such as the gills and is rapidly upregulated in hemocytes following a challenge with Aeromonas hydrophila. Recombinant ChBPI/LBP demonstrated potent and specific bactericidal activity against Gram-negative pathogens. These findings suggest that ChBPI/LBP is an important antimicrobial peptide (AMP) effector in the oyster’s immune response. This work provides novel perspectives on the evolutionary mechanisms of innate immunity in bivalves and may have implications for disease management in aquaculture.

Genetic origins and climate‐induced erosion in economically important Asian walnuts - Peng‐Zhen Fan; Guang‐Fu Zhu; Moses C. Wambulwa; Richard I. Milne; Zeng‐Yuan Wu; Ya‐Huang Luo; Robabeh Shahi Shavvon; Alistair S. Jump; Debabrata Maity; Lian‐Ming Gao; Hai‐Ling Qi; Hong‐Yu Wu; et al. (Conservation Biology, 2026)
The global climate is undergoing unprecedented changes, posing significant threats to species persistence. However, the spatiotemporal impacts on genetic diversity remain poorly understood, hindering species conservation and management. Walnuts, generally referred to as Juglans regia and J. sigillata , are economically vital in Asia, but little is known about their genetic origins and how the species will be affected by future climate change. Using 31 microsatellites, we genotyped 5282 individuals from 233 populations of walnuts in Asia. We assessed genetic diversity patterns and demographic history and investigated potential future genetic erosion risks. Genetic diversity of walnuts was high in the Himalaya and Hengduan Mountains. The 2 species diverged during the Pleistocene (around 1.41 Ma BP), and J. regia contained 2 genetic groups (JR1 and JR2). The JR2 group had the lowest diversity and likely arrived in northern China around 9.77 ka BP, perhaps via human transport. The Western Himalaya likely served both as a glacial refugium and the center of origin for J. regia , and the Eastern Himalaya appears to have been the refugium for J. sigillata . The 2 species appear to have hybridized in the Central Himalaya and the Sichuan basin and surroundings, forming two distinct hybrid zones. Our results indicate that genetic diversity will be reduced by up to 9.03% due to range loss under future climate change and dramatic genetic structure turnover in the Himalaya and Hengduan Mountains. In situ conservation in the Himalaya is essential for safeguarding genetic diversity and adaptive potential in Asian walnuts, while ex situ preservation of genetically unique wild germplasm, coupled with its integration into breeding programs, will enhance climate resilience. The findings advance our understanding of the origin of Asian walnuts and how future climatic change may affect their genetic diversity, offering a model for conservation and breeding strategies in other tree species facing similar threats.

Acupuncture as a modulator of microglial polarization and pyroptosis in depression: evidence from a chronic unpredictable mild stress rat model - Xinhong Wu; Zhuoran You; Tiansheng Zhang; Jingyu Zeng; Meng Li; Simin Yan; Jianguo Li; Peng Li; Junliang Shen; Siyu Liu; Muhammad Shahzad Aslam; Jingxuan Li; et al. (Metabolic Brain Disease, 2026)

Design, synthesis and cytotoxic activity of sulfonylated derivatives of camptothecin - Xiong-Fei Luo; Zhi-Jun Zhang; Zi-Long Song; Zhi-Ping Wang; Jia-Xuan Yan; Xiao-Fei Liu; Li-Zeng Peng; Cheng-Jie Yang; Ying-Qian Liu (Natural Product Research, 2026)

Machine learning-based diagnosis of uterine myomas and sarcomas using tumor-educated platelet transcriptomics: a retrospective multicenter study - Xudong Liu; Roujie Huang; Hua Yang; Yu Dong; Lei Li; Zhe Li; Jia Zeng; Qingxia Zhang; Yun Liu; Lei Zhang; Yidi Ma; Lin Zhang; et al. (Science Bulletin, 2026)

Coupled water-carbon cycling in karst regions: a review of processes and modeling - Mingyu Shao; Jianting Wu; Zaihua Liu; Sibo Zeng; Rasheed Mohammed Abdul; Hailong Sun; Enmin Zhou; Haibo He; Junyao Yan; Liangxing Shi; Hang Li; Chaowei Lai; et al. (Journal of Hydrology, 2026)

Association between prenatal PFAS exposure and catch-up growth in children born with adverse outcomes: evidence from a prospective cohort study - Su-Qin Tan; Yan-Xi Li; Shao-Ya Huang; Shen-Pan Li; Qiong Zhang; Cui-Lan Tang; Ying-Chao Ye; Guang-Hui Dong; Jian Chen; Dan Cai; Xiao-Wen Zeng (Journal of Hazardous Materials, 2026)

Maillard-induced pea protein isolate/carboxymethyl chitosan conjugates: Synthesis, characterization, and applications in O/W emulsions - Wenhao Liu; Xiaoye Xu; Kehao Li; Siya Lin; Xinxin Zeng; Lihui Duan; Yan Huang; Shini Ma; Xiaoyan Liu; Yajie Shen; Jie Pang; Chunhua Wu (Food Research International, 2026)

Advanced physical-based techniques for the extraction and modification of plant protein: mechanisms, functions, and applications - Yi-han Cai; Meng-na Li; Hao-yue Xu; Fang Huang; Yu-xin Zhao; Jie-han Zhang; Yan-yan Huang; Xin-An Zeng (Food Chemistry, 2026)

Nanochitin surface charge modulates nisin composite self-assembly: A multiscale simulation-experimental exploration - Wenhao Liu; Haixin Jiang; Xiaoye Xu; Lihui Duan; Yan Huang; Xinxin Zeng; Xiaoyan Liu; Yuanzhao Li; Jie Pang; Chunhua Wu (Food Chemistry, 2026)

Synergistic ionic doping for enhanced thermopower and switchable polarity in PEDOT: PSS ionic thermoelectrics - Sili Zhou; Xin Li; Jing Huang; Qiyu Meng; Zhen Liu; Jianrong Zeng; Yan Zhang; Lei Li; Dongbai Sun; Dan Zhao; Xavier Crispin; Peng Zhang (Chemical Engineering Journal, 2026)

Molecular insights into facet-specific interaction mechanism underlying humic acid adsorption on rutile TiO2 - Jiajun Li; Shishuang Zhang; Yan Xiang; Qiuyi Lu; Lei Xie; Hongbo Zeng (Chemical Engineering Journal, 2026)

Closed-form solution method for mechanical response of isolated-span transmission line after ice shedding based on state discretization - Zhao Yan; Si-yuan Wu; Xing Fu; Hong-nan Li; Hao Li; Zeng-hao Huang (Cold Regions Science and Technology, 2026)

Evolution of secondary organic aerosol under extremely high humidity conditions in urban areas of southwestern China: Formation and scavenging - Yifan Zhao; Zhier Bao; Xin Long; Yiliang Liu; Yan Han; Lingshuo Meng; Xiaoling Zeng; Lijuan Li; Xin Qi; Zhanliang Li; Chao Peng; Liuyi Zhang; et al. (Atmospheric Research, 2026)

Byakangelicol Alleviates Ischemic Brain Injury by Inhibiting Microglial Activation and Oxidative Stress - Xiao Wan Wang; Yan Qiong Fu; Zhuo Li Li; Ting Li; Hui Lan Wang; Yu Zheng; Chan Zhang; Miaolin Zeng; Chan Li; Dewei Xie; Bai Hui Chen (Molecular Neurobiology, 2026)

Unraveling stress-mediated fluid-fault interactions in 2021–2022 seismic sequence: Insights from unsupervised machine learning and multiparametric hydrochemical anomalies in Xianshuihe fault zone - Yucong Yan; Zheming Shi; Xiaocheng Zhou; Guangcai Wang; Zuochen Zhang; Yunfei Bai; Zhaojun Zeng; Bingyu Yao; Yuwen Wang; Miao He; Jiao Tian; Ruibin Li; et al. (Applied Geochemistry, 2026)

Wave attenuation in Sonneratia apetala mangroves during extreme wave—a field study in Southern China - Yuliang Zhu; Zhiqiang Li; Chunhua Zeng; Yan Sun; Xiaodong Bian; Lulu Liu (Acta Oceanologica Sinica, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

Utilizing phosphogypsum-derived CaAl LDH-chitosan to remove Pb2+ from oil/gas field wastewater: Adsorption behavior and competitive mechanism - Jing Bai; Qijia You; Yushuan Peng; Zhihao Li; Yuling Zhang; Qiulin Deng; Huiwei Liao; Faqin Dong; Xiaofeng Zeng; Zixun Yan (Process Safety and Environmental Protection, 2025)

Corrigendum to “Orbital forcing of lacustrine cycles in the Eocene Shahejie Formation of China, and its paleoclimate significance” [Palaeogeography, Palaeoclimatology, Palaeoecology. 677, 2025, 113188] - Shaolong Zhang; Jingong Cai; Xiang Zeng; Jianping Yan; Fuqiang Lai; Xiaojun Zhu; Kuihua Zhang; Junliang Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Clastic record from Northern Tethyan Himalaya: Implication for the initial India-Asian collision in the western Yarlung-Zangpo suture zone, South Tibet - Xu-dong Guo; Lin Ding; Fu-long Cai; Gui-zhen Guo; Xiao-yan Xu; Peng Han; Chang-jun Gu; Mei-yu Liu; Xiang-li Ding; Xu Liu; Xin-lei Li; Deng Zeng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Structural and geochronological studies of the Cona detachment and Cona Rift: Implications for the Miocene evolution of the Cona region - Zhuo Tang; Hanwen Dong; Rongze Fei; Linghao Zhao; Li'e Gao; Yaying Wang; Lilong Yan; Lingsen Zeng (Journal of Structural Geology, 2025)

A novel 450 nm blue laser-mediated sinoporphyrin sodium-based photodynamic therapy inactivates Cutibacterium acnes through stress-mediated metabolic alterations - Hengtong Fan; Zejun Ren; Shuqi Chen; Tingting Huang; Guoxiong Liu; Yashou Guo; Yan Zheng; Yifan Cheng; Xing Li; Yibo Mei; Yuhang Chen; Huihui Tuo; et al. (Journal of Photochemistry and Photobiology B: Biology, 2025)

Dermal bioaccessibility of organophosphate esters in indoor dust: Influencing factors, release kinetics, and health risk assessment - Zijia Hong; Yu Bon Man; Yue Li; Linying Xiao; Shitong Han; Zhuoyao Chen; Bingyan Lan; Xiaomin Yan; Jiwen Luo; Lixuan Zeng; Yuan Kang (Journal of Hazardous Materials, 2025)

Long-term substitution of chemical fertilizer with organic manure enhances the activity and autotrophic growth of ammonia-oxidizing archaea and comammox nitrospira in paddy soil - Chunyan Wu; Xu Tang; Che Tan; Tao Sun; Yu Zeng; Yinxiu Liu; Yingxia Liu; Yan Li; Yongchao Liang; Chang Yin (Journal of Environmental Management, 2025)

Fabrication of oil-in-natural deep eutectic solvents Pickering interfacial catalysis: Boosting a sustainable platform for enzymatic esterification of high-acid oil - Liyan Pan; Weiqi Liu; Yuanyuan Deng; Guang Liu; Yan Zhang; Xiaojun Tang; Ping Li; Zhihao Zhao; Jiarui Zeng; Mingwei Zhang; Pengfei Zhou (Food Chemistry, 2025)

Recent advances in green modification of lotus rhizome starch: Physicochemical properties, techno-functional characteristics and challenges - Xianqiang Chen; Yanzhao Liu; Ruibing Duan; Yassin Haran; Siyang Li; Zhongyi Liu; Xiaoling Zeng; Zongyu Liu; Jie Li; Shoulei Yan (Food Chemistry, 2025)

Development of eco-friendly chitosan films enhanced with bioactive citric acid-based deep eutectic agents for sustainable food packaging and fish preservation - Ping Shi; Xin Wang; Sajid Ali; Li-Yan Zeng; Xinhui Xian; Jinling Huang; Shengyun Qin; Yuansen Liu; Hafiz Umer Javed (Food Hydrocolloids, 2025)

Rod-structured phytic acid-functionalized covalent organic frameworks for enhanced uranium extraction from seawater - Tian Xia; Jiaxiang Liu; Jianqiao Zhang; Wenxiang Tang; Jianxin Xue; Liying Hao; Jianrong Zeng; Shushen Chen; Ziming Li; Yan Song; Jixiang Li (Desalination, 2025)

2D-confined multicore nanoengineering: Stress-dissipating compartments with Sb O C covalent boulevards for ultrahigh-rate capability and stability over 10,000 cycles - Yue Lu; Kai Li; Gaoshan Zeng; Zhaojin Wang; Xuan Wang; Zezhao Wang; Xingyu Lv; Wenhui Zhang; Wei Yan; Jiujun Zhang (Chemical Engineering Journal, 2025)

Dissolving microneedles loaded with Acanthopanax Senticosus-derived vesicles and PEI for antibacterial activity, cfDNA scavenging, anti-inflammation, and angiogenesis in diabetic wounds - Huiling Ye; Junze Tang; Wanting Liang; Yushan Li; Zhaoyi Ye; Jiasen Lin; Guining Cao; Yaoxun Zeng; Yu Sun; Meijing Wang; Ziqiao Li; Xin Cheng; et al. (Chemical Engineering Journal, 2025)

Crystal structure-dependent ammonium-ion storage mechanisms in nanostructured MnO2 polymorphs - Jingang Wu; Binbin Wei; Quanxing Guo; Haojun Zeng; Xin Liu; Qiaoyan Chen; Xutao Yan; Yuechan Li; Qi-Yuan Fan; Zhengbing Qi; Hanfeng Liang (Chemical Engineering Journal, 2025)

Poly-l-lysine functionalized melanin nanocarrier boosts dsRNA delivery and RNAi efficiency in the migratory locust - Shuai Li; Jianqin Zhang; Hao Wang; Xingyun Zhao; Lin Yang; Lin Chai; Yangyang Liu; Zhangwu Zhao; Bernard Moussian; Abeer El Wakil; Kun Yan Zhu; Zhanghua Zeng; et al. (Chemical Engineering Journal, 2025)

Energy-efficient and formaldehyde-free biomass-based boards derived from Pleurotus Ostreatus substrate waste: A novel sustainable utilization strategy - Yalan Yan; Yan Li; Bo Wang; Xin Zhang; Xu Zeng; Shuang Ding; Bo Ren; Xiaodong Yang (Bioresource Technology Reports, 2025)

Identification, Characterization, and Expression Profiling of Oryza Sativa Betaine Aldehyde Dehydrogenase Genes Exposed to Realistic Environmental Contamination of Oxyfluorfen - Yi Zhuo Wang; Jun Jin Lu; Xu Zhen Shi; Ya Nan Qu; Li Qing Zeng; Xiao Liang Liu; Xi Ran Cheng; Yan Hui Wang; Zhao Jie Chen (Tropical Plant Biology, 2025)

Crosstalk Between Abscisic Acid (ABA) and Brassinosteroid (BR) Signaling Pathways Is Revealed by Competing Endogenous RNA (ceRNA) Network in Brassica napus - Yaqia Chen; Jinfeng Wu; Changrui Ma; Yuqing Zeng; Dawei Zhang; Dinggang Zhou; Jihong Zhang; Lili Liu; Mei Li; Mingli Yan (Plant Molecular Biology Reporter, 2025)

A mini-review on the role of leucine-rich repeat receptor-like kinases (LRR-RLKs) in plant responses to drought stress - Shengjie Yan; Yunlin Zeng; Yutao Huang; Weiping Wang; Ni Li; Xianwen Zhang (Molecular Biology Reports, 2025)

Targeting the STAT3/ACLY axis attenuates pulmonary inflammation but delays Mycoplasma pneumoniae clearance via citrate metabolism - Yan Yang; Xinchao Yi; Chang Liu; Qianrui Zeng; Xinru Li; Haodang Luo; Peiyi Yan; Shuilian Gu; Chun Li; Lihua Xiao; Haiying Wu; Yumeng Li; et al. (Medical Microbiology and Immunology, 2025)

Tunnel Collapse Risk Analysis Based on Attribute Mathematical Theory and TSP Geological Forecast Technique - Yan Zhang; Xiangsheng Zheng; Haiyang Cao; Liangjie Gu; Tianbin Li; Peng Zeng (Journal of Earth Science, 2025)

Seasonality of the Heat Budget on the Ross Sea Continental Shelf in a Coupled Regional Ocean-Sea Ice-Ice Shelf Model - Jiabao Zeng; Chengyan Liu; Zhaomin Wang; Liangjun Yan; Yang Liu; Yue Xia; Xi Liang; Xiang Li; Wen Xu (Advances in Atmospheric Sciences, 2025)

A BrDof2.4-BrHDA6 module is involved in ABA-CTK-mediating leaf yellowing in Chinese flowering cabbage by affecting histone H3 and H4 acetylation of CCGs - Zhen-liang Mou; Lei Yan; Zong-li Liu; Xin-guo Su; Ze-xiang Zeng; Yuan Rong; Wei Shan; Jian-fei Kuang; Wang-jin Lu; Jian-ye Chen; Wei Wei; Jia Si (Postharvest Biology and Technology, 2025)

GA suppresses the conversion from α-linolenic acid to JA through the GhGAI1-GhMYC3-GhLOX3 module to promote cotton fiber elongation - Xi Zhu; Qingwei Suo; Bo Ding; Jianyan Zeng; Yang Yang; Yumei Yang; Rongyu Hu; Linzhu Jiang; Silu Li; Huiming Zhang; Yi Wang; Mi Zhang; et al. (Plant Science, 2025)

Orbital forcing of lacustrine cycles in the Eocene Shahejie Formation of China, and its paleoclimate significance - Shaolong Zhang; Jingong Cai; Xiang Zeng; Jianping Yan; Fuqiang Lai; Xiaojun Zhu; Kuihua Zhang; Junliang Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Be–Nb–Ta mineralization in granites: An example from the Nyalam area in the Himalayan belt, southern Tibet - Li-E Gao; Lingsen Zeng; Linghao Zhao; Lilong Yan; Yinglong Di; Guangxu Li; Yaying Wang; Rui Wang; Li Wang (Lithos, 2025)

Response of macroinvertebrate drift to dam-induced flow fluctuations: A field experiment in the Yarlung Zangbo river - Jiaxuan Tang; Qinghui Zeng; Fengbo Zhang; Baolong Zhao; Kang Zhao; Qin Yang; Long Yan; Wenhang Su; Pingfeng Li; Jinliang Zhang; Peng Hu (Journal of Environmental Management, 2025)

Hypocalcemia as biological mechanism responsible for prenatal exposure to polycyclic aromatic hydrocarbons (PAHs) and anemia: Insights from Zunyi birth cohort - Lei Luo; Wenbi Yang; Haonan Zhang; Lei Bai; Zhongbao Chen; Lin Tao; Haiyan Wang; Shimin Xiong; Ruoxuan Li; Yijun Liu; Xingyan Liu; Yan Xie; et al. (Journal of Environmental Sciences, 2025)

Discovery of Fukuyoa yasumotoi (Dinophyceae) from the Xisha Islands, South China Sea: A comprehensive study on morphology, molecular phylogeny and toxicity - Ruifang Wang; Wenguang Zhang; Zhongyong Yan; Shiwen Zhou; Ruoyu Guo; Junjie Zheng; Xinfeng Dai; Douding Lu; Qinglin Mu; Jiangning Zeng; Mengmeng Tong; Zhun Li; et al. (Harmful Algae, 2025)

Quality changes and improvement strategies of prefabricated aquatic products during storage and reheating processes - Xiaoye Xu; Wenhao Liu; Kehao Li; Lihui Duan; Yan Huang; Xinxin Zeng; Jie Shi; Shini Ma; Jie Pang; Chunhua Wu (Food Research International, 2025)

A lateral flow biosensor based on metal enhanced fluorescence effect for sensitive detection of CP4-EPSPS in genetically modified crops - Haijuan Zeng; Yan Zhang; Xiaowu Zhou; Hua Liu; You Li; Lemei Zhu; Juan Liu; Jinbin Wang (Food Bioscience, 2025)

Teleost-specific TLR25/MyD88 signaling promotes K63-linked ubiquitination of IRF1 to induce IFNa gene expression - Yunkun Li; Shihui Yi; Wuhao Tang; Lei Shi; Huizhen Yan; Lei Ning; Jing Pu; Kanbei Shiyi; Lanxin Zhang; Xiaoshuang Chen; Jiayun Wu; Shiyong Yang; et al. (Fish & Shellfish Immunology, 2025)

Synergistic modification of spinel LiMn2O4 with MgO doping and coating for mitigating the Jahn-Teller effect and enhancing lithium extraction from brine - Wenjie Fan; Luxiang Ma; Wencheng Pan; Xin Zeng; Zhixiang Li; Hongli Su; Peng Zhang; Yan Zhao (Desalination, 2025)

Origins of coulombic efficiency anomalies in sodium-ion batteries: Impact of linear carbonates and sodium interfaces - Jinyan Guo; Fanghong Zeng; Jun Gan; Yan Chen; Yanjin Liu; Lijiao Quan; Zhao Li; Hebing Zhou; Jiarong He; Lidan Xing; Weishan Li (Chemical Engineering Journal, 2025)

Garnet dissolution–reprecipitation processes in leucogranitic magma and their profound geochemical consequences - Rui Wang; Li-E Gao; Lingsen Zeng; Lilong Yan; Linghao Zhao; Guyue Hu; Li Wang; Haitao Wang (Chemical Geology, 2025)

Various formation pathways of size-resolved secondary organic aerosols at a coastal site in Eastern China - Meng-Xue Tang; Jia-Yuan Wang; Ke-Jin Tang; Wen-Jie Yu; Li He; Xiao-Feng Huang; Ling-Yan He; Hui Zeng; Si-Hua Lu; Min Hu (Atmospheric Environment, 2025)

Metabolic Control of Stem Cell Function: Insights into Amino Acid-Driven Mechanisms - Jiawei Zeng; Xiaohao Liu; Jiaming Bi; Chuzi Mo; Han Zhang; Yan Chai; Yunhe Lin; Siwei Li; Zhongjun Liu; Mingyan Yao; Shuaimei Xu; Peiyan Yuan (Stem Cell Reviews and Reports, 2025)

Effects of nitrogen and phosphorus additions in shaping C:N:P stoichiometry of plants, soil and microbes in a semi-shrub desert ecosystem - Shuwen Xue; Atawula Jiashalaiti; Yan Lu; Dongdong Zhang; Bo Zhang; Zhihao Zhang; Lei Li; Fanjiang Zeng (Plant and Soil, 2025)

Crushing characteristics and energy dissipation modeling of Single-Particle-Size carbonaceous mudstone as roadbed fill - Yan Wang; Hong-yuan Fu; Jian-Ping Song; Ling Zeng; Tao Li; Jian-Ping Xiong; Hong-Ri Zhang; Wen-Guang Wang; You-Jun Li; Jing-Cheng Chen (Bulletin of Engineering Geology and the Environment, 2025)

Estuarine morphodynamics regime shift caused by catchment reservoir: Illustration from the Minjiang River Estuary - Huikun Yao; Wenyan Zhang; Maotian Li; Weihua Li; Yan Song; Dan Peng; Jilong Wang; Jianwei Zeng; Junjie Yu; Xiaohe Lai; Lijun Hou (Ocean & Coastal Management, 2025)

Crowd safety assessment for flood evacuation in subway platform tunnels - Shuchao Cao; Luhan Ma; Yiping Zeng; Yan Wang; Peng Wang; Li Xu (Tunnelling and Underground Space Technology, 2025)

Modeling of carbon sink for concrete structures: From hydration kinetics to climate-driven carbonation - Ye Tian; Jia-Cheng Xu; Guo-Yi Zhang; Zu-Shi Tian; Bei Li; Ruo-Yi Zhao; Qiang Zeng; Bo-Tao Huang; Dong-Ming Yan (Sustainable Chemistry and Pharmacy, 2025)

Sequential interfacial contributions of microplastics to microbial adhesion and metal adsorption - Wu Li; Yan Ji; James McGree; Raymond Jianxiong Zeng; Beibei He; Ashantha Goonetilleke (Science of The Total Environment, 2025)

Oxalic acid-tea saponin complex preserves freshness and inhibits iron-polyphenol-mediated blue stain in postharvest lotus rhizomes - Xianqiang Chen; Xiaoling Zeng; Zhongyi Liu; Siyang Li; Zongyu Liu; Yassin Haran; Jie Li; Shoulei Yan (Postharvest Biology and Technology, 2025)

Two unprecedented 2-(2-phenethyl)chromone derivatives with anti-Helicobacter pylori and anti-inflammatory activities from agarwood of Aquilaria crassna - Xiao-Hong Li; Hao Wang; Wen-Li Mei; Wen-Hua Dong; Jun Zeng; Sheng-Zhuo Huang; Hui-Qin Chen; Yan-Mei Wei; Fei Wu; Zhi-Yong Guo; Hao-Fu Dai (Phytochemistry Letters, 2025)

Interfacial electron transfer in Co Fe catalysts drives self-sustained tetracycline degradation and radical enhancement in low-oxidant system - Wen Song; Lingling Cao; Runbin Zeng; Wei Hong; Liangguo Yan; Haiqiang Qi; Yanfei Li; Xin Tan; Xuguang Li (Journal of Water Process Engineering, 2025)

Interpretable machine learning models for predicting hormesis of binary antibiotic mixtures on Vibrio qinghaiensis sp.-Q67 - Ling-Yun Mo; Si-Tong Long; Pei-Pei Zhang; Yan-Peng Liang; Hong-Hu Zeng; Yong-Hong Zhang; Li-Tang Qin (Journal of Hazardous Materials, 2025)

Unravelling heavy metal releases from municipal solid waste incineration fly ash: Multi-parameter leaching behaviour, ecological risk prediction models and integrated stabilisation strategies - Sun Mingyi; Ma Liping; Yang Jingxian; Dai Quxiu; Yang Jie; He Binbin; Xie Longgui; Liu Yongqing; Hu Yao; Duan Li; Zhou Guanyun; Luo Yuetao; et al. (Journal of Environmental Chemical Engineering, 2025)

Manipulating internal catalytic microenvironment of dynamic Cu/SSZ-13 catalysts by in situ Ce incorporation for efficient NH3-SCR - Yan Wang; Tiantian Zhang; Xinya Wu; Yuanjiang Wang; Hao Qu; Cheng Zhang; Jianguo Cui; Cailing Xu; Zhaoqiang Li; Yongquan Qu; Shanghong Zeng (Journal of Environmental Chemical Engineering, 2025)

Recent research progress of methane dry reforming to syngas - Yan Wang; Rui Li; Chunyang Zeng; Wenjuan Sun; Hui Fan; Qingxiang Ma; Tian-Sheng Zhao (Fuel, 2025)

Effect of low-energy stirring temperature on the formation of oil-in-water emulsions stabilized by gelatin-arginine complexes - Jun Qi; Yu-cong Li; Hui-min Yan; Li-ting Zeng; Ao-jing Lv; Rui-ling Dong; Xue-qing Li; Zhou Lin; Le-le Shao; Lang Zhang; Guo-qing Duan; Chun-hui Zhang; et al. (Food Research International, 2025)

Fucoidan-based delivery systems: From fabrication strategies to applications - Wenhao Liu; Xiaoye Xu; Lihui Duan; Xianyang Xie; Xinxin Zeng; Yan Huang; Yuanzhao Li; Zijian Zhi; Jie Pang; Chunhua Wu (Food Research International, 2025)

Investigating the effects of pulsed electric field (PEF) on the physicochemical properties and biological activities of chlorophyll aggregates: Mechanistic insights - Zhi-Hong Zhang; Xin Huang; Yan-yan Huang; Jian Li; Xin-An Zeng; Xianli Gao (Food Chemistry, 2025)

Black rice stepwise fermentation enhances yogurt gel quality: Solidification rate, texture, LAB distribution and viability persistence - Jiarui Zeng; Zhiming Wang; Guang Liu; Xuchao Jia; Pengfei Zhou; Ping Li; Zhihao Zhao; Yan Zhang; Xiaojun Tang; Dong Liu; Yuanyuan Deng; Mingwei Zhang (Food Chemistry, 2025)

Associations of urinary biomarkers of exposure to drinking-water disinfection by-products with haematological parameters and systemic inflammation indices among women undergoing assisted reproductive technology treatment - A-Xue Liu; Yu Miao; Min Zhang; Xiao-Ying Liu; Yan-Ling Deng; Jia-Yue Zeng; Yang-Juan Li; Wen-Qing Lu; Chang-Jiang Liu; Qiang Zeng (Environmental Pollution, 2025)

Mitigation of acidification-induced system failure in high-load anaerobic digestion: Mechanistic coherence on the role of zero valent iron-loaded biochar - Wu Zeng; Anina James; Aohua Li; Ziyu Jin; Qiang Liu; Binghua Yan; Yadong Yang; Junyi Ma; Junting Pan (Chemical Engineering Journal, 2025)

Hydrophilic and lipophilic diblock polymer-based co-delivery nanoplatform for impossible mission: Resistance management toward insecticides via Nrf2-sMaf pathway - Jiajia Zhao; Zeng Wang; Jiaming Yin; Ying Wei; Mingshan Li; Jialin Gou; Meizhen Yin; Jie Shen; Shuo Yan (Chemical Engineering Journal, 2025)

Construction of Pt2+-Ov-Ce3+ enrooted structure by reduction-gel method to inhibit high temperature deactivation of three-way catalysts - Zhaohua Song; Xuzi Liu; Li Qu; Lu Zeng; Panpan Liu; Hailong Zhang; Yi Jiao; Fajun Jiang; Huicheng Yan; Jianli Wang; Yaoqiang Chen (Chemical Engineering Journal, 2025)

RUSLE tends to overestimate soil erosion in revegetated conditions: Evidence from long-term runoff plots monitoring on China’s Loess Plateau - Jun Liao; Jiaxi Wang; Juying Jiao; Zeng Yan; Jianjun Li; Ziqi Zhang; Mengmeng Li; Qian Xu; Xiaohan Jiang; Wenting Zhao; Qi Ling; Hanyuan Sheng; et al. (CATENA, 2025)

Single cell protein production of co-culture Kodamaea ohmeri and Lactococcus lactis in corn straw hydrolysate - Yong-Qiang Yang; Xu Li; Zhen-Zhi Wang; Xiao-Yan Huang; Du-Wen Zeng; Xin-Qing Zhao; Zhi-Qiang Liu; Feng-Li Zhang (Bioresource Technology, 2025)

Effects of exhalation directions on particle dispersion in high-speed train cabin and seat allocation strategies: an experimental and numerical study - Hang Zhang; Tiantian Wang; Yaozheng Zeng; Hengkui Li; Yan Zhu; Fangcheng Shi; Yu Wang; Yibin Lu; Jianfeng Zhou (Building and Environment, 2025)

Molecular detection and phylogenetic analysis of lumpy skin disease virus in Yunnan Province, China from 2019 to 2023 - Jun Yao; Xue Li; Lei Tan; Lin Gao; Pei Zhu; Jiarui Xie; Rui Yan; Taoyin Yu; Fengyi Xia; Qiyun Chen; Bangquan Zeng; Jiaping Yang (Veterinary Research Communications, 2025)

Molecular evolution of chloroplast genome in Triumfetta (Grewioideae, Malvaceae) - Rushan Yan; Yujie Zeng; Chengyu Chen; Abdur Rab; Hui Li; Raza Ullah; Madiha Islam; Ying Cui; Mengyang Liu; Xiaoxuan Tian (Planta, 2025)

Construction of a Machine Learning-Based Clopidogrel Resistance Risk Prediction Model - Ruo-Ying Wang; Shui-Di Yan; Jian-Qi Zeng; Tong Mu; Ya Yan; Yuan-Yi Zhao; Lin Xie; Li-Li Liu (Cardiovascular Toxicology, 2025)

The importance of fungal necromass in soil organic carbon: Insights from elevation gradients in arid regions - Mengfei Cong; Zhihao Zhang; Guangxing Zhao; Xinping Dong; Yan Lu; Lei Li; Yang Hu; Weiqi Wang; Zhaobin Mu; Akash Tariq; Jordi Sardans; Josep Peñuelas; et al. (Applied Soil Ecology, 2025)

Assessing soil health of pesticide-polluted land with earthworms: a review - Panpan Duan; Wenjun Wang; Fang Li; Chen Yan; Wenbing Li; Tianwei Peng; Xuxin Li; Wenhua Yi; Biao Song; Zhuotong Zeng (Environmental Monitoring and Assessment, 2025)

Antibacterial activity of pimaradienoic acid from Eleutherococcus trifoliatus (L.) S. Y. Hu - Deng Hongxian; Zhang Mengyu; Xiao Lin; Li Huanhuan; Xu Shiqi; Zeng Si; Luo Luncai; Jiang Hezhong; Tong Yan (Natural Product Research, 2025)

Dual-mode delivery of canine parvovirus type 2c VP2 protein in recombinant Lactobacillus plantarum: Surface display and intracellular expression systems - Zhe Xu; Huaiyue He; Dan Wang; Mengmeng Xiao; Jinman Li; Yulin Hou; Yangyi Chen; Xuan Zu; Jingtao Hu; Guilian Yang; Yanlong Jiang; Wentao Yang; et al. (Veterinary Microbiology, 2025)

Corrigendum to “Influence of cascade reservoirs on the distribution, transport, and retention patterns of biogenic elements in the Jinsha River” [Sci. Total Environ. 951 (2024) 175535] - Baolong Zhao; Qinghui Zeng; Jianhua Wang; Yunzhong Jiang; Long Yan; Jiaming Hou; Jiaxuan Tang; Fengbo Zhang; Kang Zhao; Xinyu Li; Peng Hu (Science of The Total Environment, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Association between phthalate exposure and reproductive health in patients undergoing assisted reproductive treatment: A systematic review and meta-analysis - Guangmei Xie; Yongjia Zhou; Qingyong Zheng; Li Wang; Yan Wang; Haijing Zeng; Jialing Wang; Xinyan Li (Reproductive Toxicology, 2025)

Short-chain chlorinated paraffins at environmentally relevant doses disrupt glucose homeostasis and insulin signaling by macrophage-mediated inflammation - Ying-Wen Mu; Wen-Huan Yao; Hui Li; Cui-Li Zhang; Yan-Jing Zhang; Xiu-Ning Zhang; Ge Song; Xiu-Lan Zhao; Tao Zeng (Journal of Hazardous Materials, 2025)

Innovative municipal sludge dewatering: High efficiency and high-dryness through the synergistic effect of MoS2 piezoelectric catalysis and electro-dewatering - Binqi Rao; Yulin Li; Zhuo Zeng; Yin Duan; Yan Zhang; Fang Zhou; Weilun Ren; Pin Zhou; Xilong Lu; Quanfa Zhou; Peng Xu (Journal of Environmental Management, 2025)

Multi-Scale study on combustion acceleration and Self-Catalytic mechanisms of Nickel-Based energetic complex [Ni(N2H4)2](N3)2 - Cheng Dong; Shiyong Chen; Lixiao Shen; Tu Xu; Yinning Zeng; Yan Li; Zhenxin Yi; Chenguang Zhu; Lin Zhang; Shunguan Zhu (Fuel, 2025)

Dynamic changes in metabolites during the manufacture of three distinct flavor types of Tieguanyin - Lin Zeng; Yan-Qing Fu; Jin-Long Liu; Yuan-Chao Li; Shui-lian Gao; Ying Gao; Fang Wang; Yong-Quan Xu (Food Chemistry, 2025)

Associations of phthalate metabolites in urine and follicular fluid with endometrial thickness in the TREE cohort - Xiu-Ting Li; Chong Liu; Yan-Ling Deng; Yu Miao; Min Zhang; Jia-Yue Zeng; Peng-Hui Liu; A.-Xue Liu; Yang-Juan Li; Jin-Qin Zhu; Ning Zhang; Juan Li; et al. (Environmental Toxicology and Pharmacology, 2025)

Hybrid electrospun fibers with metal-based catalysts for zinc-air battery: Recent development and future perspectives - Mahmood ul Haq; Yongbiao Mu; Saz Muhammad; Baoxin Wu; Kejun Yan; Jiahui Luo; Zheng Li; Zhiqing Tang; Muhammad Ajmal; Wenjia Li; Lin Zeng (Chemical Engineering Journal, 2025)

Responses of Peanut Growth and Microbial-community Diversity in Rhizosphere Soil to Foliar Sorbitol-chelated-potassium - Huanyang Zhang; Chuanhao Han; Qianqian Wei; Tengsheng Li; Fanhe Zeng; Li Zhao; Xiang Shi; Jing Zhang; Ziqi Zhang; Dongyun Yan (Journal of Soil Science and Plant Nutrition, 2025)

lncRNA PVT1 regulates chondrocyte proliferation and apoptosis through the glycolysis process mediated by miR-552-3p/PKM2 to promote osteoarthritis - Demiao Zeng; Bin Li; Longhua Zhang; Guodong Zhang; Xiangjia Yan; Mengshi Huang; Jun Jiang; Zenggao Han (In Vitro Cellular & Developmental Biology - Animal, 2025)

Regulation of LCN-2/PI3K/Akt on TNF-α induced inflammatory response of porcine intramuscular adipocytes - Xiaoying Dong; Xiaona Zeng; Yongjian Li; Yiming Yan; Shuang Gao; Yanfei Chen; Shengqiu Tang; Meiqi Liang; Yiyi Pan; Xiaonan Zhou; Wei Luo; Yuchen Tang (In Vitro Cellular & Developmental Biology - Animal, 2025)

ATF4 regulates PI3K/AKT signaling axis to promote angiogenesis after myocardial infarction - Pingping He; Weirong Zeng; Jiao Li; Yu Zhang; Ranzun Zhao; Weiwei Liu; Yongchao Zhao; Zhijiang Liu; Changyin Shen; Wei Chen; Yan Wang; Bei Shi (In Vitro Cellular & Developmental Biology - Animal, 2025)

MY-1 promotes angiogenesis in the ischemic hindlimbs by regulating the stability of CDC42 via PSMD14 - Xian Ding; Yuxin Zhang; Yuting Zeng; Qianlin Li; Sijie Qiu; Ping Xiao; Xin Luo; Jiaping Chen; Qianwen Deng; Dehong Yang; Yanli Zhang; Wenjuan Yan (Angiogenesis, 2025)

Modelling and optimization of mixed-parallel straight and two-sided disassembly line balancing problem - Wei Liang; Zeqiang Zhang; Yanqing Zeng; Dan Ji; Yu Zhang; Haiye Chen; Yan Li; Lixia Zhu (Swarm and Evolutionary Computation, 2025)

The regulatory module involved in ABA-induced ethylene production and fruit ripening in banana and its implications - Liming Zeng; Zhengnan Xie; Zehong Ding; Yan Yan; Jinghao Yang; Weiwei Tie; Guangyuan He; Guangxiao Yang; Jian Zeng; Yin Li; Meiying Li; Wei Hu (Postharvest Biology and Technology, 2025)

Andrograpalides A–N, structurally diverse ent-labdane diterpenoids with anti-inflammatory activities from the leaves of Andrographis paniculata - Xiao Zhang; Yan-Zhen Li; Ya-Ting Lai; Wei Zeng; Min Yu; Jun-Tao Huang; Hong-Lei Jin; Wei-Qun Yang; Zhong-Xiang Zhao (Phytochemistry, 2025)

Prediction of shear characteristics at core pile-cemented soil interface for offshore wind turbine pile foundation based on machine learning - Yu-liang Yan; Yu-xi Zeng; Yong-chao Liu; Bing-bing Li; Xiu-feng Liu; Bi-sheng Xu (Ocean Engineering, 2025)

Overexpression of anthocyanin activator LrAN2 improving black goji berry (Lycium ruthenicum) tolerant to cadmium stress - Peiyan Ai; Zhiqiang Wang; Yan Li; Rong Yang; Biao A; Yixin Jia; Yuan Zong; Ying Wang; Shaohua Zeng (Journal of Hazardous Materials, 2025)

Water environmental capacity of estuarine microplastics capped by species sensitivity threshold - Yichuan Zeng; Hua Wang; Dongfang Liang; Weihao Yuan; Yuting Yan; Haosen Xu; Siqiong Li; Jiayao Dou (Journal of Hazardous Materials, 2025)

Endocrine disruption of Triphenyl Phosphate via VIT-2 in Caenorhabditis elegans: A comparative analysis with estradiol and 4-hydroxytamoxifen - Chongli Shi; Mengyan Huang; Yang Zheng; Chen Wang; Hiu Yan Lam; Susu Wang; Lingjun Zeng; Yi Peng; Yulun Gu; Yu Li; Haibin Hao; Haibo Chen; et al. (Journal of Hazardous Materials, 2025)

Organ-specific lithium accumulation and its toxic effects on female reproduction - Qigang Fan; Yi Sun; Qingjun Shen; Yuxin Wang; Jisheng Nie; Yanbing Lin; Shuaishuai Xing; Yan Li; Benhong Xu; Jianjun Liu; Xiaoting Shen; Guangbo Qu; et al. (Journal of Hazardous Materials, 2025)

Interpersonal environmental communication promotes pro-environmental behaviors: a systematic examination across time and groups - Jianchi Tian; Yuanchao Gong; Chuikai Zeng; Xiaoming Tian; Yang Li; Xiaoqing Zheng; Yan Sun (Journal of Environmental Management, 2025)

Synergistic effect of hollow n-Al/H-MoO3 in the gas-phase reaction zone of solid propellant - Shuping Li; Cheng Dong; Xuan Qi; Shiyong Chen; Lixiao Shen; Yinning Zeng; Yan Li; Zhenxin Yi; Lin Zhang; Shunguan Zhu (Fuel, 2025)

Associations of acrylamide biomarkers with reproductive lifespan: A cross-sectional study in U.S. women - Junying Li; Chen Chen; Xing Dong; Yushan Cao; Zhuo Bao; Yixuan Liu; Jinxiang Yan; Pei Zhang; Yongzhen Guo; Xianxu Zeng (Food and Chemical Toxicology, 2025)

Three-dimensional flame-retardant quasi-solid composite electrolyte with a fiber structure formed using the coaxial electrospinning to suppress lithium dendrite growth - Gaofeng Zheng; Yizhe Chen; Ruixin Chen; Xiaotong Li; Zihan Chen; Ziyue Zeng; Huangping Yan (Chemical Engineering Journal, 2025)

Deployment Optimization of Pressure Sensors in Pipeline Network Via Fusing Shortest Path Planning and Monte Carlo Tree Search - Yupei Yan; Longyu Chen; Jinyu Ma; Jian Li; Zhoumo Zeng; Xinjing Huang (Water Resources Management, 2025)

Genotyping by target sequencing (GBTS)-based genetic mapping uncovers synergistic interactions for stripe rust resistance in wheat cultivar Flanders - Lei Liu; Jinyu Han; Dandan Zhang; Yuqing Li; Chuanliang Zhang; Shengjie Liu; Ziyi Yan; Weijun Zheng; Chunlian Li; Qingdong Zeng; Zhensheng Kang; Dejun Han; et al. (Theoretical and Applied Genetics, 2025)

Network pharmacology analysis and animal experiment validation of inflammation inhibition by Swertiamarin in treating Ulcerative colitis - Tang Jiafeng; Wang Lijuan; Wei Lan; You Yiqing; Yang Shiyu; Zeng Tao; Dang Tingting; Sun Haoli; Li Xiaoshan; Zhang Yan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Nuclear magnetic resonance-based metabolomic study of rat brain after different intensity treadmill running - Ni Zeng; Jie-Ting Li; Zhi-Juan Zhang; Zhi-Peng Yan; Tao Liao; Guo-Xin Ni (Journal of Physiology and Biochemistry, 2025)
Previous studies have revealed that different intensities of exercise training have an impact on cognition. However, the cognitive effects of different intensities of exercise and its underlying mechanisms are not fully understood. The aim of this paper was to investigate the effects of different intensities of treadmill exercise on cognition in rats from the perspective of metabolomic analysis. In this study, ninety-six male rats were randomly divided into four groups: control group (CON group, n = 24), low-intensity running group (LIR group, n = 24), medium-intensity running group (MIR group, n = 24), and high-intensity running group (HIR group, n = 24). After 4 weeks of treadmill running, rats in the LIR group located the platform significantly faster than those in the CON( p = 0.027) and HIR( p = 0.011) groups. After 8 weeks of treadmill running, rats in the LIR and MIR groups also found the platform more quickly than those in CON group ( p = 0.003 and p = 0.015, respectively). Additionally, rats in the MIR group showed significantly increased superoxide dismutase (SOD)/catalase (CAT) in the hippocampus compared with those exposed to HIR( p = 0.03), LIR( p = 0.0008), and CON( p = 0.0004). Metabolomic analysis revealed that, after 8 weeks of running, 14 metabolites with similar characteristics differed between the MIR and HIR groups compared to the CON group. The LIR group showed significant alterations in 12 key metabolites compared to the CON group. The LIR, MIR, and HIR groups also demonstrated significant changes in 3, 4, and 3 metabolic pathways respectively, when compared to the CON group. In conclusion, the above results indicate that LIR can effectively decrease fumarate accumulation, thereby enhancing the TCA cycle and brain energy metabolism which in turn improved cognitive function, while MIR can modify glutathione metabolism to alleviate oxidative stress (OS), supporting cognitive function.

Machine learning-based design, screening, and activity validation of topoisomerase I inhibitors - Ya-Kun Zhang; Jian-Bo Tong; Jia-Le Li; Rong Wang; Yan-Rong Zeng (Molecular Diversity, 2025)

Astrocyte involvement in brain metastasis: from biological mechanisms to therapeutic strategies - Teng Zhou; Yuxin Yan; Mingxi Lin; Cheng Zeng; Xinhui Mao; Yifei Zhu; Jinlu Han; Dou-Dou Li; Jian Zhang (Cancer and Metastasis Reviews, 2025)

Bombella intestini: A probiotic honeybee(Apis mellifera)gut bacterium - Meng Jie Jin; Andrew B. Barron; Sheng Yang He; Xu Jiang He; Qiang Huang; Li Zhen Zhang; Zi Long Wang; Xiao Bo Wu; Wei Yu Yan; Zhi Jiang Zeng (Journal of Insect Physiology, 2025)

Insights into the synergistic effects of exogenous glycine betaine on the multiphase metabolism of oxyfluorfen in Oryza sativa for reducing environmental risks - Zhao Jie Chen; Xu Zhen Shi; Ya Nan Qu; Si Ying Li; Gan Ai; Yi Zhuo Wang; Li Qing Zeng; Xiao Liang Liu; Xuesheng Li; Yan Hui Wang (Journal of Hazardous Materials, 2025)

Intergenerational inequity from hydrological drought in a warming world - Rutong Liu; Kebing Chen; Jiabo Yin; Biqiong Wu; Yan Zhao; Zhiming Liang; Na Li; Fengxian Gao; Jing Tian; Yujie Zeng; Jiali Guo (Journal of Environmental Management, 2025)

A new approach to color correction and equalization for generating mars global color image mosaics from Tianwen-1 MoRIC images - Xin Ren; Xiaoxia Zhang; Wangli Chen; Wei Yan; Xingguo Zeng; Xu Tan; Xingye Gao; Qiang Fu; Lin Guo; Qing Zhang; Zhaopeng Chen; Guobin Yu; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Assessment of geothermal waters in Yunnan, China: Distribution, quality and driving factors - Zhaojun Zeng; Li Yang; Yueju Cui; Xiaocheng Zhou; Miao He; Yuwen Wang; Yucong Yan; Bingyu Yao; Xiaojing Hu; Weiye Shao; Jian Li; Hong Fu (Geothermics, 2025)

Cu-Thioamide coordination polymers derived Cu-S catalysts for CO2 electroreduction to formate - Honglin Li; Xin Zhang; Yuanyuan Wen; Jingyuan Li; Yu Liu; Hongjun Mao; Hongman Sun; Jingbin Zeng; Zifeng Yan (Fuel, 2025)

Utilizing reverse oxygen spillover effect to enhance hydrodeoxygenation performance of CuCoCeOx catalysts via low-temperature air pretreatment - Ziyi Yan; Xiaofeng Wang; Fandi Zeng; Liang Qi; Yanfei Zhang; Qingbo Li (Chemical Engineering Journal, 2025)

Chemical homogeneity enables long-term stability of cobalt-free high-voltage spinel cathode materials - Chunlin Zeng; Guanjun Chen; Qian Zhang; Yan Li; Chengzhi Dai; Ruotong Zhao; Shichun Mu; Weihao Zeng; Jinlong Yang (Chemical Engineering Journal, 2025)

Mechanistic insights into endometriosis: roles of Streptococcus agalactiae and L-carnitine in lesion development and angiogenesis - Yuan Zhuang; Ting Lyu; Yang Chen; Wei Li; Lei Tang; Shi-ping Xian; Peng-fei Yang; Lijie Wang; Qian-qian Zhang; Chaoming Mei; Yu-jing Lin; Zhixiang Yan; et al. (Angiogenesis, 2025)

Dietary bile acid supplementation alters the gut transcriptome and metagenome and contributes to herbivorous diet adaptation in juvenile allodiploid hybrid fish - Zexun Zhou; Ye Yuan; YunYun Liu; Shandong Chen; Yongchun Li; Yan Miao; Shi Wang; Zhongyuan Shen; Lei Zeng; Li Ren; Chang Wu; Qizhi Liu; et al. (Aquaculture, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Phenol-driven ammonium recovery from coal chemical wastewater in a bioelectrochemical system (BES) - Ran Zeng; Li-Hui Yang; Si-Yuan Zhai; Cheng-Yan Liu; Na Lin; Qing-Hua Ou-Yang; Yan-Hua Xu; Ai-Jie Wang; Hao-Yi Cheng (Journal of Hazardous Materials, 2025)

Large-scale distribution and ecological risk assessment of inorganic arsenic in surface sediments of Chinese marginal seas - Sijia Liu; Jiaxi Zhang; Ziheng Yan; Xi Wu; Shaofeng Wang; Xiaoming Zhao; Junyi Shi; Zidan Yuan; Xiangfeng Zeng; Jiaxing Zhou; Changpeng Sang; Yongbin Li; et al. (Journal of Hazardous Materials, 2025)

Prediction methodology of air absorbed dose rates for Chinese cities with deep learning models - Chong Guo; Xiaoyu Li; Zhihui Yan; Lekang Chen; Bing Tang; Wenjie Zeng (Journal of Environmental Radioactivity, 2025)

Tectonic variations in NS-trending rifts, southern Tibetan Plateau: insights from hydrothermal emissions and seismic activities - Jiao Tian; Xiaocheng Zhou; Minghui Liao; Miao He; Zhaojun Zeng; Yucong Yan; Bingyu Yao; Yuwen Wang; Shihan Cui; Gaoyuan Xing; Chunhui Cao; Liwu Li; et al. (Journal of Asian Earth Sciences, 2025)

Disintegration and separation of the bilobate-shaped meteoric fragment during hypersonic atmospheric entry - Ziwen Li; Yong Yu; Xiangyuan Zeng; Haoyu Li; Tongge Wen; Xiaoran Yan (Icarus, 2025)

Insight into the succession pattern of the microbial community of fermented grains and driving forces during pit fermentation of Maotai-flavor baijiu - Xiangyong Zeng; Lanlan Liu; Dong Li; Tao Li; Chaoyang Wei; Dounan Li; Yan Yan; Wentao Cao (Food Research International, 2025)

Corrigendum to “A highly sensitive and reusable magnetic nano-electrochemical biosensor for the detection of the liver cancer biomarker heat shock protein 70” [Chem. Eng. J. 505 (2025) 159860] - Ruming Liu; Ying Li; Yan Liu; Yixuan Wang; Qiuyue Si; Dorothy Araba Yakoba Agyapong; Juan Feng; Ruiqin Fang; Lixia Tang; Fei Cao; Hongjuan Zeng (Chemical Engineering Journal, 2025)

Glymphatic Impairment Associated with Neurocognitive Dysfunction in Moyamoya Disease - Chaofan Zeng; Yuanren Zhai; Peicong Ge; Chenglong Liu; Xiaofan Yu; Wei Liu; Junsheng Li; Qiheng He; Xingju Liu; Xun Ye; Qian Zhang; Rong Wang; et al. (Translational Stroke Research, 2025)

Advancements in Laboratory Studies of Layered Rock Masses for Deep Engineering: Insights and Future Perspectives - Yan Zhang; Kai Meng; Xuanmei Fan; Guoqing Chen; Xiangsheng Zheng; Shaojun Li; Tianbin Li; Peng Zeng; Min Xia (Journal of Earth Science, 2025)

Analysis of Sandbar–Trough Bed Level Changes Under Regular Wave Conditions—A Case Study of Ten-Mile Silver Beach, Hailing Island, China - Xiaodong Bian; Zhiqiang Li; Yan Sun; Daoheng Zhu; Tao Chen; Chunhua Zeng (Journal of Marine Science and Engineering, 2025)
Understanding the evolution of the sandbar–trough system under regular wave conditions is essential for revealing the dynamic responses of coastal morphology in non-extreme environments and provides a scientific basis for long-term beach stability assessments and coastal erosion management. This study conducted a three-day field observation on Ten-Mile Silver Beach, Hailing Island, China, to investigate the coupling relationships between hydrodynamic factors and bed elevation changes during the morphological evolution of the sandbar–trough system. The results indicate that gravity wave (>0.04 Hz) energy is a key driver of bed elevation changes. During the erosion phase, gravity wave energy increases, and the peak wave energy frequency shifts toward lower frequencies, accompanied by a contraction of low-frequency energy and an expansion of high-frequency energy. In contrast, the accretion phase exhibits the opposite pattern. As the sandbar–trough system developed, the explanatory power of hydrodynamic factors on bed elevation decreased by 41% in the trough region and increased by 3.7% in the sandbar region, indicating a spatially differentiated pattern characterized by weakened forcing in the trough and enhanced response over the sandbar. During the geomorphic adjustment process, the trough area exhibited increased sensitivity, with gravity wave energy, near-infragravity wave (0.01–0.04 Hz) energy, far-infragravity wave (0.004–0.01 Hz) energy, mean wave height, and significant wave steepness reversing their influence directions on bed elevation. In contrast, the sandbar area maintained a more stable hydrodynamic control mechanism, with only the influence pattern of significant wave steepness undergoing a shift. This study enhances the understanding of geomorphology–hydrodynamics coupling within nearshore sandbar–trough systems and provides theoretical insights and technical support for monitoring and evaluating coastal erosion and accretion processes under normal wave conditions.

Peanut yield prediction using remote sensing and machine learning approaches based on phenological characteristics - Xuehui Hou; Junyong Zhang; Xiubin Luo; Shiwei Zeng; Yan Lu; Qinggang Wei; Jia Liu; Wenjie Feng; Qiaoyu Li (Computers and Electronics in Agriculture, 2025)

Design of multi-epitope chimeric phage nanocarrier vaccines for porcine deltacoronavirus - GuoQing Zhao; YuMin Zhang; Yan Li; ShiDan Zhang; ShengJing Jiao; XiaoYan Zeng; JingJiao Ma; YuQiang Cheng; HengAn Wang; YaXian Yan; JianHe Sun; Pan Tao; et al. (Veterinary Microbiology, 2025)

Fabrication of flexible polymer-MOF composite electrolyte for solid-state lithium metal batteries with high rate performance - Jiansheng Gao; Yan Chai; Jialun Ni; Yong Zeng; Gaoyuan Zhang; Xueling Liu; De Ning; Xinghui Jin; Huajun Zhao; Dong Zhou; Rui Gao; Wei Wu; et al. (Chemical Engineering Journal, 2025)

Arsenic Accumulation in Different Parent Materials of Rice (Oryza Sative L.) are Affected by Root Morphology - Yi Chen; Dehui Tu; Deqiang Li; Yinggang Xu; Yueyi Wu; Zhaoyong Zeng; Xiaoyan Tang; Yang Li; Chaorui Yan; Ting Lan; Fu Huang; Xuesong Gao; et al. (Journal of Plant Growth Regulation, 2025)

Tree-level carbon stock estimations across diverse species using multi-source remote sensing integration - Qing Li; Jia Yin; Xiaoxin Zhang; Dalei Hao; Matheus Pinheiro Ferreira; Wenhui Yan; Ye Tian; Da Zhang; Shen Tan; Sheng Nie; Tianyu An; Xiaoyao Li; et al. (Computers and Electronics in Agriculture, 2025)

Three new dimeric 2-(2-phenethyl)chromones from the agarwood of Aquilaria malaccensis - Xian-Yun Yan; Wei Li; Hao Wang; Wen-Hua Dong; Jun Zeng; Fei Wu; Wen-Li Mei; Lin-Fu Liang; Hao-Fu Dai (Phytochemistry Letters, 2025)

Two unprecedented 5,6,7,8-tetrahydro-2-(2-phenylethyl)chromones with anti-Helicobacter pylori activity from agarwood of Aquilaria sinensis 'Reke 1' - Ke-Xin Qin; Hao Wang; Li Yang; Yan-Mei Wei; Cai-Hong Cai; Hui-Qin Chen; Wen-Hua Dong; Wei Li; Xian-Yun Yan; Jun Zeng; Wen-Li Mei; Jie Jian; et al. (Phytochemistry Letters, 2025)

A review of redox-active polymers for selective electrochemical removal of uncharged organic pollutants from water - Zhen Qiu; Guanda Shen; Wenxin Yan; Xin Zeng; Maonan Jiang; Yongfu Li; Hai Xiang; Hailu Fu; Chang Liu; Bing Yu (Journal of Environmental Chemical Engineering, 2025)

Soil minerals regulate soil organic carbon accumulation through glomalin-related soil protein along an elevation gradient in a mountain arid ecosystem - Guangxing Zhao; Zhihao Zhang; Weiqi Wang; Mengfei Cong; Xinping Dong; Yanju Gao; Zhaobin Mu; Yan Lu; Lei Li; Akash Tariq; Jordi Sardans; Josep Penuelas; et al. (Environmental Research, 2025)

The inventory of OH and H2O in the non-polar regions of the Moon - Wen Yu; Hao Yan; Hong Tang; Xiongyao Li; Yu Wei; Huiming Bao; Chuanjiao Zhou; Bing Mo; Yanxue Wu; Haiyang Luo; Jialong Hao; Ruiying Li; et al. (Earth and Planetary Science Letters, 2025)

Heterogeneous zebra-patterned ultra-sensitive flexible sensor for human motion detection and game control - Xianghui Zeng; Yao Lu; Liming Zou; Zirui Pu; Deqiang Chen; Zezhao Ding; Yang Fan; Yanli Wang; Yan Vivian Li (Chemical Engineering Journal, 2025)

Construction of phenothiazine-decorated ZnO quantum dots with intelligent response to bacterial pH/amidase microenvironment for inducing bacterial ferroptosis-like death - Wu-Bin Shao; Rong-Shuang Luo; Yan-Wei Huang; Long Cheng; Dan Zeng; Xiang Zhou; Li-Wei Liu; Song Yang (Chemical Engineering Journal, 2025)

Magnitude, distribution and temporal trend of nitrous oxide emissions from China’s natural soils over 1980–2022 - Songbai Hong; Zimeng Li; Mingsong Tang; Fa Li; Yitong Yao; Yanzi Yan; Mingzhu He; Xuhui Wang; Hui Zeng; Shilong Piao (Science China Earth Sciences, 2025)

Understanding the Antidepressant Mechanisms of Acupuncture: Targeting Hippocampal Neuroinflammation, Oxidative Stress, Neuroplasticity, and Apoptosis in CUMS Rats - Jianguo Li; Xinhong Wu; Simin Yan; Junliang Shen; Tao Tong; Muhammad Shahzad Aslam; Jingyu Zeng; Yiping Chen; Wenjie Chen; Meng Li; Zhuoran You; Kaiyue Gong; et al. (Molecular Neurobiology, 2025)

Oxalate-derived NiO@NiAl-layered double hydroxide core-shell material for supercapacitors - Hong-Li Yue; Hong-Yan Zeng; Wei Yan; Chao-Wei Luo; Zi-Feng Tian; Kai-Wen Xu (Applied Clay Science, 2025)

Development and Characterisation of an Immortal Cell Line From Largemouth Bass ( Micropterus salmoides ) for Viral Studies - Qianyi Mai; Qing Wang; Yingying Li; Jiyuan Yin; Xubing Mo; Cunbin Shi; Yan Ren; Donghai Liu; Xuanming Liu; Dongli Sun; Weiqiang Liu; Yuqi Jin; et al. (Journal of Fish Diseases, 2025)
Largemouth bass ( Micropterus salmoides ), a freshwater fish species, is cultivated widely across China. The industry has been greatly affected by various viral diseases. We generated a new immortal cell line from the fin of M. salmoides (MSF). It has been successfully maintained in continuous culture for over 80 passages. Cells multiply well at 28°C using Medium 199 or Leibovitz's L‐15 supplemented with 10%–20% fetal bovine serum. MSF cells comprise a mass of epithelialoid cells. Chromosome analysis showed that ploidy at passage 55 was 2 n = 58. Amplification and analysis of the sequence of cytochrome oxidase I gene ascertained the origin of MSF cells from M. salmoides . The cell line is devoid of contamination with mycoplasma. Successful transfection with a GFP reporter gene indicated that the MSF cell line can be a useful tool for further gene expression studies. MSF cells exhibited susceptibility to Largemouth bass ranavirus (LMBV), Infectious spleen and kidney necrosis virus (ISKNV), and Siniperca chuatsi rhabdovirus (SCRV). Transmission electron microscopy (TEM), and immunofluorescence confirmed that the MSF cell line showed high susceptibility to all the tested viruses. The titre values of MSF after infection with LMBV, ISKNV, and SCRV reached 10 7.4 TCID 50 /mL, 10 6.15 TCID 50 /mL, and 10 6.35 TCID 50 /mL at 7dpi, respectively. In conclusion, an immortal cell line derived from the fin tissue of M. salmoides was successfully developed and certain fish viruses can effectively propagated in the newly established MSF cell line that can be helpful for future gene manipulation and infectious viral mechanistic studies in the future.

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Elemental Imbalances After Manganese Exposure and the Regulatory Potential of Curcumin - Hua Zhao; Jia-Min Zeng; Yao Li; Chun-Yan Ao; Duo Liu; Jing-Peng Zhuo; Chun Yu; Jia-Qi Ban; Jun Li (Biological Trace Element Research, 2025)

Recombinant Bacillus subtilis displaying OmpA and cholera toxin B subunit fusion proteins on the spore surface: An orally delivered engineered probiotic against Edwardsiella tarda infection - Minggang Liu; Xixi Dai; Jianzhen Li; Dan Xiao; Bin Chen; Zhenhua Wang; Yicen Tang; Yan Zeng; Dongmei Zhang; Xueqin Ni; Kangcheng Pan (Aquaculture, 2025)

Enhanced iodinated disinfection byproducts formation in iodide/iodate-containing water undergoing UV-chloramine sequential disinfection: Machine learning-aided identification of reaction mechanisms - Zhen-Ning Luo; Huan He; Tian-Yang Zhang; Xiu-Li Wei; Zheng-Yu Dong; Meng-Yuan Xu; Heng-Xuan Zhao; Zheng-Xiong Zheng; Ren-Jie Pan; Chen-Yan Hu; Chao Zeng; Mohamed Gamal El-Din; et al. (Water Research, 2025)

Recombinant probiotic Escherichia coli delivers the polymeric protein of swine influenza virus for protection - Jin-Mei Sun; Wen-Qiang Zhang; Yan-Jin Li; Tian-Kui Guo; Rong-Rong Zhang; Yong-Lei Yang; Ying Zhao; Ling-Jiao Yu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; et al. (Veterinary Microbiology, 2025)

Urinary biomarkers of drinking water disinfection byproducts in relation to blood-based liver function parameters among reproductive-aged Chinese women - Ping-Ping Gui; Yan-Ling Deng; Min Zhang; Yu Miao; Peng-Hui Liu; Jia-Yue Zeng; Yang Wu; Cheng-Ru Li; Xiao-Ying Liu; Yang-Juan Li; Jin-Qin Zhu; A-Xue Liu; et al. (Science of The Total Environment, 2025)

Genome-wide identification and analysis of autophagy-related (ATG) genes in Lycium ruthenicum Murray reveals their crucial roles in salt stress tolerance - Yi Shi; Yan Wu; Mengling Li; Na Luo; Faqiang Li; Shaohua Zeng; Ying Wang; Chao Yang (Plant Science, 2025)

Genomic, transcriptomic, and metabolomic analyses reveal convergent evolution of oxime biosynthesis in Darwin’s orchid - Kai Jiang; Birger Lindberg Møller; Shaofan Luo; Yu Yang; David R. Nelson; Elizabeth Heather Jakobsen Neilson; Joachim Møller Christensen; Kai Hua; Chao Hu; Xinhua Zeng; Mohammed Saddik Motawie; Tao Wan; et al. (Molecular Plant, 2025)

Genomic analysis of Marinobacter sp. M5B reveals its role in alginate biosynthesis - Xiaoyu Si; Zhenhai Liu; Shuxin Cheng; Jingyao Xi; Bingrui Zeng; Meihui Li; Liping Zhu; Shigan Yan; Nan Zhang (Marine Genomics, 2025)

Olfactory bulb microglia activation mediates neuronal pyroptosis in ozone-exposed mice with olfactory and cognitive dysfunction - Ranhong Xu; Haiyu Chen; Yougang Wang; Haomin Qi; Yinuo Chen; Anqi Dai; Siqi Yang; Yue Wang; Yan Zeng; Jinquan Li (Journal of Hazardous Materials, 2025)

Superhydrophilic membrane coupled with hydroxide ion-assisted bubbles for efficient separation of surfactant-stabilized oil/water emulsions - Hui Li; Shaopeng Gan; Chuan Yue; Zechen Yan; Qingzhong Xue; Jianqiang Zhang; Tao Yan; Hongbo Zeng (Journal of Hazardous Materials, 2025)

Biomass moulding fuel for zero-emission agricultural waste management: A case study of tobacco curing in China - Tianbao Ren; Ding Yan; Youjian Zhang; Xiaolong Li; Jian Chen; Chuliang Wang; Chi Wang; Peiyan Li; Longfei Wang; Qiang Zeng; Xianjie Cai (Journal of Environmental Management, 2025)

Hydrogeochemical characteristics of hot springs in the Longriba fault, northeastern Tibetan Plateau: Tectonic implications for geothermal fluid circulation - Yuwen Wang; Xiaocheng Zhou; Jingchao Li; Yunfei Bai; Yucong Yan; Jiao Tian; Miao He; Zhaojun Zeng; Bingyu Yao; Gaoyuan Xing; Shihan Cui; Ying Li; et al. (Journal of Asian Earth Sciences, 2025)

A large-scale VHR parcel dataset and a novel hierarchical semantic boundary-guided network for agricultural parcel delineation - Hang Zhao; Bingfang Wu; Miao Zhang; Jiang Long; Fuyou Tian; Yan Xie; Hongwei Zeng; Zhaoju Zheng; Zonghan Ma; Mingxing Wang; Junbin Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Exploration of the regulatory mechanism of pulsed electric field on the aggregation behavior of soybean protein isolates - Rui Wang; Pei-Feng Guo; Jin-Peng Yang; Yan-Yan Huang; Lang-Hong Wang; Jian Li; Song-Yi Lin; Qing-Lin Sheng; Xin-An Zeng; Yong-Xin Teng (Food Hydrocolloids, 2025)

Long-term diversified cropping promotes wheat yield and sustainability across contrasting climates: Evidence from China and Switzerland - Zhengjun Yan; Yi Xu; Juncong Chu; Thomas Guillaume; Luca Bragazza; Hongjun Li; Yanjun Shen; Yadong Yang; Zhaohai Zeng; Huadong Zang (Field Crops Research, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Comprehensive analysis of spatiotemporal heterogeneity reveals the effects of physicochemical and biological factors on temperature rise during the Moutai-flavor Baijiu stacking fermentation process - Yuanbu Li; Xing Qin; Xianglian Zeng; Menglin She; Liangqiang Chen; Jianjun Lu; Ying Han; Fan Yang; Huabin Tu; Hai Du; Yan Xu (Chemical Engineering Journal, 2025)

Multifunctional MOF-808@PVDF microspheres for recovery of unidirectional flow phosphorus from either wastewater or fermented sludge - Long Chen; Mengcan Yan; Yanxia Ma; Aiyi Wang; Xiaohan Zhi; Xiawei Li; Nasir Ali Khan; Bizhen Zeng; Hongtao Zhu (Chemical Engineering Journal, 2025)

Behavioral studies of the abuse potential and anesthetic and sedative effects of etomidate in male rodents - Lixin Kuai; Xiangyu Li; Deli Xu; Linggao Zeng; Peng Xu; Bin Di; Fang Yan; Dan Wang (Psychopharmacology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Mortality-related health metrics in systemic autoimmune diseases: an epidemiological analysis of a nationwide register-based cohort - Mucong Li; Chanyuan Wu; Peng Yin; Junyan Qian; Jiuliang Zhao; Qian Wang; Dong Xu; Jinmei Su; Xiaomei Leng; Wenjie Zheng; Xinping Tian; Yan Zhao; et al. (Science Bulletin, 2025)

Efficient removal of cationic malachite green using co-pyrolyzed corn straw biochar-montmorillonite composites - Xiaodong Yang; Zhiyong Hou; Xuefei Yang; Minghui Li; Yuanxia Guo; Kai Wang; Shuaiqi Luo; Jin Zhao; Pengkai Sun; Qiang Yang; Rui Chen; Yan Yan; et al. (Journal of Environmental Management, 2025)

Hydrogeochemical characteristics of hot springs in the Daju Fault Zone of the SE Tibetan Plateau, China - Hongzhi Dong; Xiaocheng Zhou; Miao He; Zongjun Gao; Jinyuan Dong; Jiao Tian; Jingchao Li; Yucong Yan; Fengli Liu; Bingyu Yao; Yuwen Wang; Zhaojun Zeng; et al. (Journal of Asian Earth Sciences, 2025)

Molecular basis of E93-dependent tissue morphogenesis and histolysis during insect metamorphosis - Mei Zeng; Zi-Yu Yan; Ya-Nan Lv; Jia-Ming Zeng; Ning Ban; Dong-Wei Yuan; Sheng Li; Yun-Xia Luan; Yu Bai (Insect Biochemistry and Molecular Biology, 2025)

A highly sensitive and reusable magnetic nano-electrochemical biosensor for the detection of the liver cancer biomarker heat shock protein 70 - Ruming Liu; Ying Li; Yan Liu; Yixuan Wang; Qiuyue Si; Dorothy Araba Yakoba Agyapong; Juan Feng; Ruiqin Fang; Lixia Tang; Fei Cao; Hongjuan Zeng (Chemical Engineering Journal, 2025)

Effective and selective gold recovery based on synergistic bimetallic-hydroxyl metal–organic frameworks - Chaopeng Liu; Zhoujie Wang; Shishuang Zhang; Yan Xiang; Zhikao Li; Lei Xie; Hongbo Zeng (Chemical Engineering Journal, 2025)

Elevational patterns in the diversity and composition of soil archaeal and bacterial communities depend on climate, vegetation, and soil properties in an arid mountain ecosystem - Zhihao Zhang; Yan Lu; Li Li; Fanjiang Zeng; Xiangyi Li; Lei Li; Jian Yue (CATENA, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

Compound heterozygous mutation of AFG3L2 causes autosomal recessive spinocerebellar ataxia through mitochondrial impairment and MICU1 mediated Ca2+ overload - Hongyu Li; Qingwen Ma; Yan Xue; Linlin Cai; Liwen Bao; Lei Hong; Yitao Zeng; Shu-Zhen Huang; Richard H. Finnell; Fanyi Zeng (Science China Life Sciences, 2025)

Comparative analysis of the complete chloroplast genome of seven Wikstroemia taxa (Thymelaeaceae) provides insights into the genome structure and phylogenetic relationships - Chaoqiang Zhang; Jinglong Li; Fang Yan; Zhaofeng Wang; Xiucun Zeng; Jiayin Zhang (Planta, 2025)

Genome-wide analysis of the SPL family in Zanthoxylum armatum and ZaSPL21 promotes flowering and improves salt tolerance in transgenic Nicotiana benthamiana - Jianrong Li; Xiaofang Zeng; Zhengyu Jin; Tao Zhou; Chaoting Lang; Jin Qin; Qingqing Zhang; Haibo Lan; Yan Li; Huaming An; Degang Zhao (Plant Molecular Biology, 2025)

Deciphering the landscape and evolutionary trajectory of NLR immune receptors in Dioscorea alata - Yue Wang; Xing-Yu Feng; Wen-Qiang Wu; Ming-Han Li; Sai-Xi Li; Zhen Zeng; Zhu-Qing Shao; Yan-Mei Zhang (Plant Molecular Biology, 2025)

Association between post-COVID-19 sleep disturbance and neurocognitive function: a comparative study based on propensity score matching - Shixu Du; Leqin Fang; Yuanhui Li; Shuai Liu; Xue Luo; Shufei Zeng; Shuqiong Zheng; Hangyi Yang; Yan Xu; Dai Li; Bin Zhang (Journal of Zhejiang University-SCIENCE B, 2025)

Whole-body vibration elicits 40 Hz cortical gamma oscillations and ameliorates age-related cognitive impairment through hippocampal astrocyte synapses in male rats - Mingsong Liu; Lei Li; Ruizhe Chen; Qilin Wang; Tongfei Zeng; Junhong Hu; Changzhi Yan; Jing Xiao; Xuewei Xia (Biogerontology, 2025)

A transcriptome-wide association study integrating multi-omics bioinformatics and Mendelian randomization reveals the prognostic value of ADAMDEC1 in colon cancer - Cong Zhang; Dan Shi; Guichuan Lai; Kangjie Li; Yuan Zhang; Wenlong Li; Haijiao Zeng; Qiaoping Yan; Xiaoni Zhong; Biao Xie (Archives of Toxicology, 2025)

The impact of host genetics on microbe assemblages in three types of mrigal carp (Cirrhinus mrigala) - Wuhui Li; Yongchun Li; Shujuan Chen; Yan Miao; Ye Yuan; Rongxi Xiang; Liang Kai; Zexun Zhou; Hongqin Li; Jisen Su; Shi Wang; Zhongyuan Shen; et al. (Aquaculture, 2025)

The role of microorganisms in phosphorus cycling at river-lake confluences: Insights from a study on microbial community dynamics - Jie Liang; Min Yan; Ziqian Zhu; Lan Lu; Junjie Ding; Qinxue Zhou; Xiang Gao; Ning Tang; Shuai Li; Xiaodong Li; Guangming Zeng (Water Research, 2025)

Impacts of wind forcing on microplastics kinematic in a sensitive water area - Hua Wang; Yi Wu; Yanqing Deng; Xiaomao Wu; Xiaoying Li; Haosen Xu; Yichuan Zeng; Yuting Yan (Science of The Total Environment, 2025)

Methyl jasmonate activated regulatory module Ma14-3-3e-MbHLH130-MbACO13/MbACS7 promoting ethylene biosynthesis and fruit ripening in banana - Meiying Li; Yan Yan; Liwang Zeng; Zhengnan Xie; Zehong Ding; Jinghao Yang; Yu Wang; Jianxiang Ma; Kaisen Huo; Xiaoliang Yang; Qiyu Xia; Xiao xue Ye; et al. (Postharvest Biology and Technology, 2025)

The miR172a–SNB module orchestrates both induced and adult-plant resistance to multiple diseases via MYB30-mediated lignin accumulation in rice - He Wang; Zhe-Xu Wang; Hong-Yuan Tian; Yu-Long Zeng; Hao Xue; Wan-Ting Mao; Lu-Yue Zhang; Jun-Ni Chen; Xiang Lu; Yong Zhu; Guo-Bang Li; Zhi-Xue Zhao; et al. (Molecular Plant, 2025)

Allelic variation in the promoter of WRKY22 enhances humid adaptation of Arabidopsis thaliana - Ruyun Liang; Luna Tan; Xiang Guo; Shangling Lou; Xuming Dan; Yu Han; Cheng Zeng; Han Zhang; Kai Yang; Liyang Chen; Xin Liang; Meng Liu; et al. (Molecular Plant, 2025)

Spatiotemporal characteristics of hydrothermal volatiles from the Tengchong volcanic field in the southeastern Tibetan Plateau: A probable constraint on the genesis of intraplate volcanism - Yingchun Wang; Xiaocheng Zhou; Jiao Tian; Haoxin Jia; Xiaoyi Zhu; Jiang Li; Miao He; Zhaojun Zeng; Yucong Yan; Bingyu Yao; Yuwen Wang; Gaoyuan Xing; et al. (Journal of Volcanology and Geothermal Research, 2025)

Phthalate exposures, blood coagulation function, and assisted reproductive technology outcomes: Results from the TREE cohort study - Chong Liu; Chang-Jiang Liu; Wen-Qu Tian; Wen Yao; Yu Miao; Min Zhang; Xiao-Qiong Yuan; Yan-Ling Deng; Wen-Qing Lu; Yu-Feng Li; Qiang Zeng (Environmental Research, 2025)

Trimetallic synergy of Fe-Co-Mo cathode for efficient non-radical degradation in a heterogeneous photo-electro-Fenton process - Linsen Li; Wei Wang; Zhaoxi Shen; Xue Yan; Can Niu; Qingyi Zeng; Jiachen Wang; Yanbiao Liu (Chemical Engineering Journal, 2025)

Abundant surface adsorbed oxygen species originated from defect/vacancy sites during preferential CO oxidation - Yang Liu; Kunming Hou; Zhihua Guo; Yan Guo; Yue Jiang; Xinya Wu; Zewei Fu; Heng Zhang; Ping Li; Shanghong Zeng (Chemical Engineering Journal, 2025)

Neurotensin Modulates Emotional Valence Assignment in the Basolateral Amygdala Through Neuromodulator Gain - Maimaitishalijiang Abudureheman; Yu-Hao Xiao; Li-Zang Zeng; Hong-Yan Geng (Neuroscience Bulletin, 2025)

HEDN: multi-oriented hierarchical extraction and dual-frequency decoupling network for 3D medical image segmentation - Yu Wang; Guoheng Huang; Zeng Lu; Ying Wang; Xuhang Chen; Xiaochen Yuan; Yan Li; Jieni Liu; Yingping Huang (Medical & Biological Engineering & Computing, 2025)

Unveiling soil microbial dynamics: insights into bacterial community responses to solonetz dealkalinization - Wei Gao; Yuhan Song; Xiaobin Guo; Jun Zhao; Guanjun Zeng; Xinyi Ma; Lu Li; Yan Li; Xiangbi Chen; Lianfeng Wang; Zhongjun Jia; Jinshui Wu (Journal of Soils and Sediments, 2025)

ADAM10-mediated β-klotho degradation: a key to FGF21 resistance in senescent vascular endothelial cells - Yuzhen Huang; Yucong Zhang; Ni Yang; Zonghao Qian; Ziwei Fang; Lang Zeng; Yi Huang; Han Li; Mandi Luo; Jinhua Yan; Lei Ruan; Cuntai Zhang; et al. (GeroScience, 2024)

Pollution status and assessment of seven heavy metals in the seawater and sediments of Hangzhou Bay, China - Rong Zhu; Yan-Yan Zeng; Li-Min Liu; Lu Yin; Kai-Ping Xu; Wei-Feng Chen; Shang-Chun Li; Xiao-Feng Zhou (Marine Pollution Bulletin, 2024)

Eimeria tenella rhoptry neck protein 2 plays a key role in the process of invading the host intestinal epithelium - Yanning Li; Tongxuan Zhang; Xuanrui Liu; Tianxu Pan; Junyi Li; Wentao Yang; Xin Cao; Yanlong Jiang; Jianzhong Wang; Yan Zeng; Chunwei Shi; Haibin Huang; et al. (Veterinary Parasitology, 2024)

Efficient removal of aqueous ciprofloxacin antibiotic by ZnO/CuO-bentonite composites synthesized via carbon-bed pyrolysis of bentonite and metal co-precipitation - Xiaodong Yang; Xuefei Yang; Zhiyong Hou; Minghui Li; Shuaiqi Luo; Jin Zhao; Kai Wang; Yuanxia Guo; Pengkai Sun; Fang Tan; Yan Yan; Lulu Liu; et al. (Science of The Total Environment, 2024)

Mapping high-resolution global gridded population distribution from 1870 to 2100 - Haoming Zhuang; Xiaoping Liu; Bingjie Li; Changjiang Wu; Yuchao Yan; Li Zeng; Chunyan Zheng (Science of The Total Environment, 2024)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Insights of physicochemical structure changes of bituminous coal with acidification-assisted controlled electric pulse through SEM, XRD and FTIR - Fazhi Yan; Changjiong Gao; Shoujian Peng; Xuelin Yang; Ziwen Li; Mengmeng Yang; Tao Zeng; Yongdan Yang (Gas Science and Engineering, 2024)

Metagenomic insights into quorum sensing-associated microbial profiling and its correlations with flavor compounds of Maotai-flavor liquor: A case study of stacking fermented grains - Tao Li; Wentao Cao; Dounan Li; Chaoyang Wei; Yan Yan; Xiangyong Zeng (Food Research International, 2024)

Preparation and structural characterization of selenium nanoparticles from Lactobacillus reuteri and their protective effects on DSS-induced ulcerative colitis in mice - Li Sun; Si-meng Liu; Yan Ding; Ran Yang; Hua-jin Zeng (Food Bioscience, 2024)

Metagenomic and metatranscriptomic analyses of microbial genera and volatiles produced during the fermentation of doubanjiang meju - Liang Zhang; Yan Zeng; Jin Yu; Yufeng Li; Peibin Zeng (Food Bioscience, 2024)

Constituent-taste relationship of Kuding tea fermented by Aspergillus neoniger and Aspergillus cristatus: Unveiling taste characteristics through untargeted metabolomics - Zhaoxiang Zeng; Chengwu Song; Xiaoliu Hu; Xinchang Zhu; Yiping Li; Jingnan Ren; Yan Wang; Haijun Yang; Xing Huang; Min Zhao; Rongzeng Huang; Shuna Jin (Food Bioscience, 2024)

The roles of organic amendments and plant treatments in soil polychlorinated biphenyl dissipation under oxic and sequential anoxic–oxic conditions - Meng Yan; Tingting Peng; Ling Zhao; Qigang Li; Ruini Wu; Yiming Wang; Yucheng Wu; Ying Teng; Xingjia Xiang; Jun Zeng; Xiangui Lin (Environmental Research, 2024)

Exposure to PFOA, PFOS, and PFHxS induces Alzheimer's disease-like neuropathology in cerebral organoids - Shiya Lu; Xizhi Zhu; Pinli Zeng; Linxia Hu; Yan Huang; Xinhua Guo; Qiqi Chen; Yantang Wang; Li Lai; Aiqin Xue; Yanli Wang; Zhiqiu Wang; et al. (Environmental Pollution, 2024)

Fine mapping of QGPC.caas-7AL for grain protein content in bread wheat - Dehui Zhao; Jianqi Zeng; Hui Jin; Dan Liu; Li Yang; Xianchun Xia; Yubing Tian; Yan Zhang; Shuanghe Cao; Wei Zhu; Chunping Wang; Zhonghu He; et al. (Theoretical and Applied Genetics, 2024)

Transcriptional patterns of human retinal pigment epithelial cells under protracted high glucose - Hao Huang; Jingshu Zeng; Xielan Kuang; Fan He; Jianjun Yan; Bowen Li; Wei Liu; Huangxuan Shen (Molecular Biology Reports, 2024)

Carvedilol induces pyroptosis through NLRP3-caspase1-ASC inflammasome by nuclear migration of NF-κB in prostate cancer models - Yan Zeng; Mei-xi Li; Shi-qi Wu; Chen Xu (Molecular Biology Reports, 2024)

A cross-attention swin transformer network for EEG-based subject-independent cognitive load assessment - Zhongrui Li; Rongkai Zhang; Li Tong; Ying Zeng; Yuanlong Gao; Kai Yang; Bin Yan (Cognitive Neurodynamics, 2024)

Towards sustainable fruit production: Identifying challenges and optimization strategies - Liangquan Wu; Xiaojun Yan; Jiayi Huang; Xiuzhu Xu; Siwen Zhang; Shilei Cui; Xiaohui Chen; Zhixiong Zeng; Shuangyong Huang; Yingzhe Zeng; Yibin Weng; Bingkun Lu; et al. (Agricultural Systems, 2024)

Albiflorin Alleviates Severe Acute Pancreatitis-Associated Liver Injury by Inactivating P38MAPK/NF-κB Signaling Pathway - Haitao Li; Xiangpeng Zeng; Dongjie Sun; Xingfeng Qi; Dazhou Li; Wen Wang; Yan Lin (Biochemical Genetics, 2024)

Genome characterization of a novel fowl adenovirus serotype 8b isolate and construction of the reverse genetic system for rapid genome manipulation - Qilong Qiao; Panpan Yang; Junjie Liu; Minghe Xu; Yan Li; Xingyu Li; Mengjia Xiang; Yutao Zhu; Luyao Qiu; Chenghao Han; Dexin Bu; Boshun Zhang; et al. (Veterinary Microbiology, 2024)

Development of a recombinant Lactobacillus plantarum oral vaccine expressing VP2 protein for preventing feline panleukopenia virus - Jiakang Li; Yue Zeng; Luying Li; Jiajia Peng; Quanhui Yan; Zijun Ye; Yan Zhang; Weihui Li; Longlong Cao; Dengyuan Zhou; QiuYan Li; Youhui Si; et al. (Veterinary Microbiology, 2024)

CD36-mediated ROS/PI3K/AKT signaling pathway exacerbates cognitive impairment in APP/PS1 mice after noise exposure - Zan Zhou; Wen-jun Jiang; Yan-ping Wang; Jun-qiang Si; Xian-si Zeng; Li Li (Science of The Total Environment, 2024)

High emission of black carbon in heavy-duty diesel vehicles: Insights from microscopic operating conditions - Ting Chen; Xiao He; Liqiang He; Yan You; Lewei Zeng; Mingqiu Gao; Fengbin Wang; Yihuan Cao; Zhenhua Li; Xuan Zheng; Shaojun Zhang; Guangyi Xu; et al. (Science of The Total Environment, 2024)

Prospective study on the joint effect of persistent organic pollutants and glucose metabolism on chronic kidney disease: Modifying effects of lifestyle interventions - Dandan Wei; Jiayu Shi; Haoran Xu; Yao Guo; Xueyan Wu; Zhiwei Chen; Taimeng Chen; Huilin Lou; Erbao Han; Guozhen Han; Yumeng Yan; Xiaotian Liu; et al. (Science of The Total Environment, 2024)

Influence of cascade reservoirs on the distribution, transport, and retention patterns of biogenic elements in the Jinsha River - Baolong Zhao; Qinghui Zeng; Jianhua Wang; Yunzhong Jiang; Long Yan; Jiaming Hou; Jiaxuan Tang; Fengbo Zhang; Kang Zhao; Xinyu Li; Peng Hu (Science of The Total Environment, 2024)

Depth-dependent responses of soil bacterial communities to salinity in an arid region - Xinping Dong; Zhihao Zhang; Yan Lu; Li Li; Yi Du; Akash Tariq; Yanju Gao; Zhaobin Mu; Yuhe Zhu; Weiqi Wang; Jordi Sardans; Josep Peñuelas; et al. (Science of The Total Environment, 2024)

Multi-tracer evidence of hydrology and primary production controls on dissolved organic matter composition and stability in the semi-arid aquatic continuum - Mingyu Shao; Zaihua Liu; Hailong Sun; Haibo He; Qiang Li; Sibo Zeng; Junyao Yan; Yan Fang; Qiufang He; Hailong Liu; Liangxing Shi; Chaowei Lai (Geochimica et Cosmochimica Acta, 2024)

Accumulation and metabolism of selenium in the rare yeast Kazachstania unispora during the selenium enrichment process - Furong Wang; Xiaoben Li; Xian Wang; Ivan Kurtovic; Min Yan; Jianping Wei; Ting Zhang; Xuejun Zeng; Yahong Yuan; Tianli Yue (Food Chemistry, 2024)

Recent advance for animal-derived polysaccharides in nanomaterials - Meng-na Li; Xiang-ze Jia; Qing-bo Yao; Feng Zhu; Yan-yan Huang; Xin-An Zeng (Food Chemistry, 2024)

Cytology, metabolomics, and proteomics reveal the grain filling process and quality difference of wheat - Fang Li; Chao Cui; Chenyang Li; Yan Yu; Quan Zeng; Xiaoyan Li; Wanchun Zhao; Jian Dong; Xiang Gao; Jishan Xiang; Dingguo Zhang; Shanshan Wen; et al. (Food Chemistry, 2024)

Experimental and DFT calculation study on the efficient removal of high fluoride wastewater from metallurgical wastewater by kaolinite - Zhen Zeng; Qisheng Huang; Qian Li; Jia Yan; Xiaoyu Zhao; Lei Huang; Sijie Zhao; Hongguo Zhang (Environmental Research, 2024)

Intrauterine exposure to long-chain perfluorocarboxylic acids (PFCAs) were associated with reduced primary bile acids in three-year-old children: Findings from a prospective birth cohort study - Yu-Ting Guo; Jin-bo Huang; Jing-chuan Xue; Shuang-Jian Qin; Dan Cai; Qi-Zhen Wu; Chu Chu; Cui-lan Tang; Yan-qi Xie; Li-Zi Lin; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Pollution, 2024)

Classification and regression machine learning models for predicting the combined toxicity and interactions of antibiotics and fungicides mixtures - Li-Tang Qin; Jun-Yao Zhang; Qiong-Yuan Nong; Xia-Chang-Li Xu; Hong-Hu Zeng; Yan-Peng Liang; Ling-Yun Mo (Environmental Pollution, 2024)

Chitin nanocrystal Pickering emulsions for sustainable release pesticide microencapsulation with superior leaf adhesion and enhanced safety - Long Chen; Liang Li; Hongyan Chen; Bo Cui; Fei Gao; Jinming Gao; Xiang Zhao; Yan Wang; Haixin Cui; Zhanghua Zeng (Chemical Engineering Journal, 2024)

Enhanced removal of nanoplastics from freshwater using in-situ synthesized and anchored nano-Fe3O4 via two-step ferrous oxidation - Jiarong Li; Yan Zhang; Cuiyun Zeng; Qiang Xiong; Hua Zhang; Qiaohui Guo; Lu Wang; Jun Ma; Shuiliang Chen (Chemical Engineering Journal, 2024)

Plant allelochemicals inhibit the growth and colony formation of Microcystis - Xiao Ma; Xueli Wang; Shaoqi Zhou; Jianrong Ma; Jingfu Wang; Jingan Chen; Yan Zeng; Qiao Chen; Boqiang Qin; Ming Li (Journal of Oceanology and Limnology, 2024)

Microcystin-LR prenatal exposure induces coronary heart disease through macrophage polarization imbalance mediated by trophoblast-derived extracellular vesicles - Meihong Guo; Xinrui Li; Manhou Choi; Jingwen Zhang; Songci Yan; Danni Ma; Jing Zeng; Weidong Ding; Yanting Wen; Dongmei Li; Xiaodong Han; Yong Wang; et al. (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Enhancing demulsification efficiency and sustaining constant separation flux in oil/water emulsions via Janus membrane inspired by spider silk - Xiaojing Li; Shouping Xu; Xinjuan Zeng; Yuanyang Yan; Min Zhang; Jie Luo; Pihui Pi; Xiufang Wen (Journal of Environmental Chemical Engineering, 2024)

Elucidating the molecular mechanisms in phytohormones-induced alleviation of postharvest physiological deterioration in cassava tuberous roots - Xiaoxue Ye; Zhengnan Xie; Liwang Zeng; Zehong Ding; Weiwei Tie; Yan Yan; Kaisen Huo; Jianxiang Ma; Chaochao Li; Fei Yan; Yinhua Chen; Jianqiu Ye; et al. (Food Bioscience, 2024)

Advances in understanding the roles of plant HAT and HDAC in non-histone protein acetylation and deacetylation - Zihan Zhang; Yan Zeng; Jiaqi Hou; Lijia Li (Planta, 2024)

Correction to: PAH Pollution in Particulate Matter and Risk in Chinese Cities - Yongfu Wu; Ning Zhang; Yan Shi; Zetao Chen; Han Zhang; Jiaqiang Yin; Tao Zeng; Zhongyu Yuan; Ni Li; Yibin Ren; Liqun Cai; Yunzhao Li; et al. (Exposure and Health, 2024)

Rapid Real-Time Prediction Techniques for Ammonia and Nitrite in High-Density Shrimp Farming in Recirculating Aquaculture Systems - Fudi Chen; Tianlong Qiu; Jianping Xu; Jiawei Zhang; Yishuai Du; Yan Duan; Yihao Zeng; Li Zhou; Jianming Sun; Ming Sun (Fishes, 2024)
Water quality early warning is a key aspect in industrial recirculating aquaculture systems for high-density shrimp farming. The concentrations of ammonia nitrogen and nitrite in the water significantly impact the cultured animals and are challenging to measure in real-time, posing a substantial challenge to water quality early warning technology. This study aims to collect data samples using low-cost water quality sensors during the industrial recirculating aquaculture process and to construct predictive values for ammonia nitrogen and nitrite, which are difficult to obtain through sensors in the aquaculture environment, using data prediction techniques. This study employs various machine learning algorithms, including General Regression Neural Network (GRNN), Deep Belief Network (DBN), Long Short-Term Memory (LSTM), and Support Vector Machine (SVM), to build predictive models for ammonia nitrogen and nitrite. The accuracy of the models is determined by comparing the predicted values with the actual values, and the performance of the models is evaluated using Mean Absolute Error (MAE), Mean Absolute Percentage Error (MAPE), and Root Mean Square Error (RMSE) metrics. Ultimately, the optimized GRNN-based predictive model for ammonia nitrogen concentration (MAE = 0.5915, MAPE = 28.95%, RMSE = 0.7765) and the nitrite concentration predictive model (MAE = 0.1191, MAPE = 29.65%, RMSE = 0.1904) were selected. The models can be integrated into an Internet of Things system to analyze the changes in ammonia nitrogen and nitrite concentrations over time through aquaculture management and routine water quality conditions, thereby achieving the application of recirculating aquaculture system water environment early warning technology.

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Molecular insights into the catalytic mechanism of a phthalate ester hydrolase - Ning Wang; Nan Zhang; Mei-Ling Sun; Yan Sun; Qing-Yu Dong; Yu Wang; Zeng-Tian Gu; Hai-Tao Ding; Qi-Long Qin; Yong Jiang; Xiu-Lan Chen; Yu-Zhong Zhang; et al. (Journal of Hazardous Materials, 2024)

Endoplasmic reticulum stress response modulator OsbZIP39 regulates cadmium accumulation via activating the expression of defensin-like gene OsCAL2 in rice - Jian Li; Ling-Yan Wang; Huan-Chao Huang; Wu Yang; Guang-Yi Dai; Zhi-Qiang Fang; Jun-Liang Zhao; Kuai-Fei Xia; Xuan Zeng; Meng-Ling He; Nan Yao; Ming-Yong Zhang (Journal of Hazardous Materials, 2024)

A novel synthesized Vanillin-Based Deep Eutectic Agent (V-DEA) mitigates postharvest fungal decay and improve shelf life and quality of cherry tomatoes - Hafiz Umer Javed; Nuwan D. Kularathnage; Jiaxiu Du; Ruofan Liu; Zhiqing Yang; Sixia Zhong; Jiajie Zhou; Muzammil Hussain; Xugang Shu; Li-Yan Zeng (Food Chemistry, 2024)

The delayed senescence in harvested blueberry by hydrogen-based irrigation is functionally linked to metabolic reprogramming and antioxidant machinery - Zhiwei Jin; Huize Huang; Hehan Huang; Longna Li; Yan Zeng; Xu Cheng; Didier Pathier; Lijun Gan; Wenbiao Shen (Food Chemistry, 2024)

Preparation of gelatin-starch shell-yolk microspheres by water-in-water emulsion method: Effects of starch crystal type and cross-linking - Zhirenyong Zhang; Xiaoxue He; Ting Yan; Yuyu He; Chaoxi Zeng; Shiyin Guo; Qingming Li; Huiping Xia (Food Hydrocolloids, 2024)

Preparation of salicylic acid nano-protectant with dual synergistic mechanism: High direct fungicidal activity and plant defence toward cotton Verticillium wilt - Jiaming Yin; Jiajia Zhao; Zeng Wang; Fan Xue; Qi Wang; Huiming Guo; Hongmei Cheng; Jie Li; Jie Shen; Meizhen Yin; Xiaofeng Su; Shuo Yan (Chemical Engineering Journal, 2024)

Phase separation behavior and CO2 absorption kinetic analysis of DETA/DEA/DMAC biphasic absorbent - Zhipeng Chen; Tao Wang; Chao Li; Mengxiang Fang; Wei Chen; Ximing Hu; Yan Shao; Zhihao Liu; Wei Zhang; Li Zhang; Wenyang Fan; Shaojuan Zeng (Chemical Engineering Journal, 2024)

Carbonization of bacterial cellulose with structure retention and Nitrogen/Sulfur/Oxygen doping for application in supercapacitors electrode - Yan Wu; Bin Wang; Jinpeng Li; Daxian Cao; Jun Xu; Jinsong Zeng; Wenhua Gao; Xingxiang Ji; Kefu Chen (Chemical Engineering Journal, 2024)

Suppressing leakage current and charge accumulation via perovskite interface morphology regulation for efficient light-emitting diodes - Yongjian Chen; Xiankan Zeng; Cheng Yan; Shiyu Yang; Lunyao Pan; Chenglong Li; Maolin Mu; Wen Li; Guanqi Tang; Weiqing Yang (Chemical Engineering Journal, 2024)

Ionic liquid gel microspheres as multifunctional bi-component additives for the crystallinity manipulation and defect passivation in all-air-processed perovskite solar cells - Gangyi Zeng; Guangyao Liu; Tiantian Wang; Lingling Wen; Jiangning Li; Yan Meng; Xin Li (Chemical Engineering Journal, 2024)

Silencing MUC1 to regulate intracellular lipid metabolism: Overcoming sunitinib resistance and inhibiting metastasis in renal cell carcinoma - Xianhu Zeng; Tian Liu; Yi Teng; Zhipeng Li; Yan Liang; Dengshuai Wei; Guiming Zhang; Yong Sun; Shangcong Han (Chemical Engineering Journal, 2024)

In-situ forming carboxymethyl chitosan hydrogel containing Paeonia suffruticosa Andr. leaf extract for mixed infectious vaginitis treatment by reshaping the micro-biota - Shiami Jia; Shengting Huang; Rezhemu Jimo; Yongbu AXi; Yuanhui Lu; Ziling Kong; Jun Ma; Heran Li; Xiao Luo; Yan Qu; Kaijun Gou; Rui Zeng; et al. (Carbohydrate Polymers, 2024)

Research on heat dissipation optimization and energy conservation of supercapacitor energy storage tram - Yibo Deng; Sheng Zeng; Chushan Li; Ting Chen; Yan Deng (Waste Disposal & Sustainable Energy, 2024)

Genome-Wide Identification and Expression Analysis of WRKY Transcription Factor Genes in Passion Fruit (Passiflora edulis) - Shugang Xu; Xingcheng Zhu; Qian Zhang; Shixian Zeng; Yan Li; Yong Wang (Tropical Plant Biology, 2024)

Exogenous Application of Sorbitol-Chelated Calcium Enhances Salt Tolerance in Rapeseed (Brassica napus L.) - Huiting Tan; Wenxuan Sun; Li Zhao; Xiang Shi; Jing Zhang; Ziqi Zhang; Huanyang Zhang; Chuanhao Han; Fanhe Zeng; Dongyun Yan (Journal of Soil Science and Plant Nutrition, 2024)

Antibody-based near-infrared fluorogenic probes for wash-free imaging of cell-surface proteins - Haoting Wang; Jiaqi Yan; Wenchao Wang; Endong Chen; Di Chen; Su Zeng; Quan Li; Linghui Qian (Analytica Chimica Acta, 2024)

Molecular characterization of fad6 gene and its transcriptional changes in response to different initial diets and nutritional status in yellow catfish (Pelteobagrus fulvidraco) - Bo Zhou; Xiu-Ying Wei; Zheng-Yong Wen; Bin Wang; Yu-Ying Zhao; Wan-Hong Zeng; Yu He; Panita Prathomya; Yun-Yun Lv; Yan-Ping Li; Jun Wang; Rui Li; et al. (Frontiers in Marine Science, 2024)
Fatty acid desaturases (FADs) are rate-limiting enzymes for the biosynthesis of highly unsaturated fatty acids (HUFAs). As a new member of the FAD family, Fad6 and its roles remain unclear in various teleost fishes. In this study, we identified a fad6 gene from yellow catfish (yc fad6 ) and determined its spatiotemporal expression patterns and responses to different initial diets and nutritional status in yellow catfish. Our results showed that the open reading frame (ORF) of yc fad6 was 1,080 bp in length, encoding a protein of 359 amino acids. Multiple protein sequences alignment proved that fad6 is highly conserved among diverse vertebrates. Meanwhile, phylogenetic analysis revealed that Southern catfish and yellow catfish were clustered into one branch, supporting evolutionary consistence between the fad6 gene and fish morphology. Moreover, comparisons of genomic synteny and gene structure revealed functional and evolutionary conservation of the fad6 gene in various teleost fishes. Tissue distribution analysis by quantitative RT-PCR demonstrated that the yc fad6 gene was extensively expressed in examined tissues, with higher transcription levels in the heart and liver. Meanwhile, yc fad6 gene was widely expressed in various developmental stages, indicating Fad6 may play important roles in HUFA biosynthesis at early developmental stages in yellow catfish. Functional experiments verified that the transcription of yc fad6 decreased significantly with the extension of feeding time (with egg yolk or Artemia nauplii ) at the early developmental stages, indicating that a diet rich in HUFA can remarkably inhibit the transcription of yc fad6 in yellow catfish. In addition, yc fad6 transcription was significantly reduced after a short-term (24-h) or long-term food deprivation (1-week) and then continued to decrease during refeeding, suggesting that nutritional states can affect the transcription of yc fad6 , which further regulates the metabolism of HUFAs. Anyway, these fundamental findings provide basic references for further investigating evolutionary and physiological functions of the fad6 gene in yellow catfish as well as in other teleost fishes.

Activation of the NLRP3-CASP-1 inflammasome is restrained by controlling autophagy during Glaesserella parasuis infection - Chaoxiong Yue; Jinquan Li; Siming Zhang; Ruyi Ma; Mingjiao Suo; Yiwen Chen; Hui Jin; Yan Zeng; Yushan Chen (Veterinary Microbiology, 2024)

Evaluation of a new real-time source apportionment system of PM2.5 and its implication on rapid aging of vehicle exhaust - Pei-Ting Yao; Xing Peng; Li-Ming Cao; Li-Wu Zeng; Ning Feng; Ling-Yan He; Xiao-Feng Huang (Science of The Total Environment, 2024)

Natural aromatic extract of black tea improved the water retention of pork meat batter - Wen-ping Xu; Rui-ling Dong; Ao-jing Lv; Yu-cong Li; Li-ting Zeng; Xue-ling Gao; Jun Qi; Zhou Lin; Hui-min Yan; Chun-hui Zhang; Guo-yuan Xiong (Food Research International, 2024)

Encapsulation of roast beef flavor by soy protein isolate/chitosan complex Pickering emulsions to improve its releasing properties during the processing of plant-based meat analogues - Xiangquan Zeng; Yan Li; Pan Li; Jinling Zhao; Xuejie Li; Xuzeng Wang; Bangdi Liu; Laixue Ni; He Li; Yu Xi; Jian Li (Food Chemistry, 2024)

Exploration of carbonyl compounds in red-fleshed kiwifruit wine and perceptual interactions among non-volatile organic acids - Cen Li; Cui Tang; Xiangyong Zeng; Yi Zhang; Laping He; Yan Yan (Food Chemistry, 2024)

Teleost-specific TLR23 in Takifugu rubripes recruits MyD88 to trigger ERK pathway and promotes antibacterial defense - Yu-ting Du; Hong-qiang Zhang; Yan Li; Xue-peng Li; Zeng-zhi Yuan; Mo-fei Li (Fish & Shellfish Immunology, 2024)

Early arrival of the Réunion plume at the base of the Himalaya? - Yaying Wang; Lingsen Zeng; Li-E Gao; Linghao Zhao; Lilong Yan (Earth and Planetary Science Letters, 2024)

Functional connectivity related to road linear erosion at rainfall event scale in an agricultural watershed on the Loess Plateau - Qian Xu; Juying Jiao; Ziqi Zhang; Mengmeng Li; Xiqin Yan; Yulan Chen; Jun Liao; Zeng Yan (CATENA, 2024)

Sensitivity of atmospheric peroxyacetyl nitrate (PAN) formation and its impact on ozone pollution in a coastal city - Nan Fu; Li-Ming Cao; Shi-Yong Xia; Le-Wei Zeng; Li He; Ling-Yan He; Xiao-Feng Huang (Atmospheric Environment, 2024)

Temporal and Spatial Changes and Driving Forces of Carbon Stocks and Net Ecosystem Productivity: A Case Study of Zoige County, Sichuan Province, China - Xiyang Feng; Zhe Wang; Zhenlong Zhang; Jiaqian Zhang; Qiuping Zeng; Duan Tian; Chao Li; Li Jiang; Yong Wang; Bo Yuan; Yan Zhang; Jianmei Zhu (Journal of the Indian Society of Remote Sensing, 2024)

Correction: Sinomenine protects against atherosclerosis in apolipoprotein E-knockout mice by inhibiting of inflammatory pathway - Zhao Gao; Chao Yang; Guangwei Zeng; Ming Lin; Wei Li; Mengna Sun; Yantao Zhang; Beibei Fan; Yogesh Kumar; Kun Yan (Inflammopharmacology, 2024)

Hydrogen-based irrigation increases yield and improves quality of Chinese cabbage by enhancing nutrient composition and antioxidant capabilities - Ziyu Liu; Genmei Chen; Enxin Yang; Longna Li; Yan Zeng; Xu Cheng; Didier Pathier; Guoyi Xu; Wenbiao Shen (Horticulture, Environment, and Biotechnology, 2024)

A recombinase polymerase amplification–SYBR Green I assay for the rapid and visual detection of Brucella - Jiang Chang; Nan Wang; Jun-Peng Zhan; Shi-Jun Zhang; De-Ying Zou; Feng Li; Ying Zhang; Yan-Song Li; Pan Hu; Shi-Ying Lu; Zeng-Shan Liu; Hong-Lin Ren (Folia Microbiologica, 2024)

Rapid, sensitive, and visual detection of pseudorabies virus with an RPA-CRISPR/EsCas13d-based dual-readout portable platform - Dong You; Tong Xu; Bing-Zhou Huang; Fang Wu; Li-Shuang Deng; Zhe-Yan Liu; Liang-Peng Ge; Zuo-Hua Liu; Jing Sun; Xiu Zeng; Yuan-Cheng Zhou; Si-Yuan Lai; et al. (Analytica Chimica Acta, 2024)

Transcriptome analysis provided a new insight into the gene expression profiles of muscle after exercise training of juvenile Schizothorax wangchiachii - Mengsha Zeng; Maohua Li; Yan Lu; Xiaoshuai Liu; Wenxue Gao; Zhaobin Song (Aquaculture International, 2024)

Integrated analysis reveals a novel 5-fluorouracil resistance-based prognostic signature with promising implications for predicting the efficacy of chemotherapy and immunotherapy in patients with colorectal cancer - Yufang Hou; Fang Zhang; Jinbao Zong; Tiegang Li; Wenqiang Gan; Silin Lv; Zheng Yan; Zifan Zeng; Liu Yang; Mingxuan Zhou; Wenyi Zhao; Min Yang (Apoptosis, 2024)

Current and future trends in the biocontrol of postharvest diseases - Xiaojiao Li; Shixian Zeng; Michael Wisniewski; Samir Droby; Longfeng Yu; Fuquan An; Yan Leng; Chaowen Wang; Xiaojun Li; Min He; Qinhong Liao; Jia Liu; et al. (Critical Reviews in Food Science and Nutrition, 2024)

Probabilistic risk assessment of dietary exposure to lead in residents of Guangzhou, China - Shaofang Song; Yufei Liu; Weiwei Zhang; Yan Li; Yuhua Zhang; Yanyan Wang; Jinheng Zeng; Xinhong Pan (Food Additives & Contaminants: Part A, 2024)

Eco-health risks and main sources of persistent pollutants bound by bus stops dust in Qingyang city, an important energy base on the west side of the Ziwuling primitive Forest - Yongfu Wu; Lianglu Hao; Han Zhang; Tao Zeng; Yuan Meng; Dongbo Li; Yan Shi; Ni Qiao; Tongjun Wang (Marine Pollution Bulletin, 2024)

A 76-m per pixel global color image dataset and map of Mars by Tianwen-1 - Jianjun Liu; Xin Ren; Wei Yan; Wangli Chen; Xingguo Zeng; Xiaoxia Zhang; Xu Tan; Xingye Gao; Qiang Fu; Dingxin Liu; Lin Guo; Qing Zhang; et al. (Science Bulletin, 2024)

Biocontrol performance of a novel Bacillus velezensis L33a on tomato gray mold and its complete genome sequence analysis - Lixinyu Sun; Yu Chen; Shiyu Liu; Xiaogang Ou; Yangyang Wang; Zhengwu Zhao; Rong Tang; Yingzhe Yan; Xinyue Zeng; Shun Feng; Tao Zhang; Zhengguo Li; et al. (Postharvest Biology and Technology, 2024)

The non-linear associations between blood manganese level and sarcopenia in patients undergoing maintenance hemodialysis: A multicenter cross-sectional study - Rui Hu; Qiangying Zeng; Qingdong Xu; Hongmei Zhou; Rongshao Tan; Xiaoshi Zhong; Yan Liu; Yi Li; Yun Liu (Journal of Trace Elements in Medicine and Biology, 2024)

Quality enhancement and time reduction in soaking green plum wine using pulsed electric field - Lang-Hong Wang; Bing Yan; Danli Tang; Zhong Han; Jian Li; Xin-An Zeng (Journal of Food Engineering, 2024)

The effect of extraction methods on the components and quality of Camellia oleifera oil: Focusing on the flavor and lipidomics - Wenquan Zeng; Xudong Liu; Yan Chao; Yiying Wu; Shukun Qiu; Baining Lin; Rukuan Liu; Ruichang Tang; Suxi Wu; Zhihong Xiao; Changzhu Li (Food Chemistry, 2024)

Tetrabromobisphenol-A/S and their derivatives in surface particulates from workshop floors of three representative e-waste recycling sites in China - Hui Yang; Xiao-Jun Luo; Jia-Zhuo He; Yan-Hong Zeng; Bi-Xian Mai; Li-Zhong Wang; Xiang Bi (Environmental Research, 2024)

The association between PM2.5 components and blood pressure changes in late pregnancy: A combined analysis of traditional and machine learning models - Lijie Wang; Li Wen; Jianling Shen; Yi Wang; Qiannan Wei; Wenjie He; Xueting Liu; Peiyao Chen; Yan Jin; Dingli Yue; Yuhong Zhai; Huiying Mai; et al. (Environmental Research, 2024)

Two sex pheromone receptors for sexual communication in the American cockroach - Na Li; Renke Dong; Huanchao Zeng; Yan Zhang; Run Huang; Wei Liu; Fengming Cao; Jincong Yu; Mingtao Liao; Jingyou Chen; Wenlei Zhang; Zejian Huang; et al. (Science China Life Sciences, 2024)

Root metabolites remodeling regulated by γ-aminobutyric acid (GABA) improves adaptability to high temperature in creeping bentgrass - Zhou Li; Min Zhou; Weihang Zeng; Yan Zhang; Lin Liu; Wei Liu; Yan Peng (Plant and Soil, 2024)

Industrial effluents and N-nitrosamines in karst aquatic systems: a study on distribution and ecological implications - Xiaoyu Yan; Huanfang Huang; Wenwen Chen; Haixiang Li; Yingjie Chen; Yanpeng Liang; Honghu Zeng (Environmental Geochemistry and Health, 2024)

NLRP3 inflammasome activation triggers severe inflammatory liver injury in N, N-dimethylformamide-exposed mice - Xiu-Ning Zhang; Yan-Jing Zhang; Lin Wang; Shu-Jun Hong; Cui-Li Zhang; Xiu-Lan Zhao; Tao Zeng (Science of The Total Environment, 2024)

Urinary haloacetic acid concentrations and thyroid function among women: Results from the TREE study - Yang Wu; Yan-Ling Deng; Min Zhang; Yu Miao; Fei-Peng Cui; Jia-Yue Zeng; Xiao-Ying Liu; Cheng-Ru Li; A-Xue Liu; Jin-Qin Zhu; Yang-Juan Li; Chong Liu; et al. (Science of The Total Environment, 2024)

Mechanical protein polycystin-1 directly regulates osteoclastogenesis and bone resorption - Mei Huang; Jingxuan Zhou; Xiaoxiao Li; Ran Liu; Yangzi Jiang; Kaixuan Chen; Yurui Jiao; Xin Yin; Ling Liu; Yuchen Sun; Weishan Wang; Ye Xiao; et al. (Science Bulletin, 2024)

Three types of enzymes complete the furanocoumarins core skeleton biosynthesis in Angelica sinensis - Kaixuan Wang; Huihui Zeng; Yiqun Dai; Zixuan Wang; Huanying Tang; Junde Li; Xingchen Lu; Neng Jiang; Guoyong Xie; Yan Zhu; Yucheng Zhao; Minjian Qin (Phytochemistry, 2024)

Two new lignans from the fresh roots of Zhongsheng No.1 Rehmannia glutinosa - Xiang-Da Li; Yan-Gang Cao; Yu-Han Zhang; Ying-Jie Ren; Meng-Nan Zeng; Yan-Ling Liu; Xu Chen; Xin-Yi Ma; Bing-Xian Zhao; Xiao-Ke Zheng; Wei-Sheng Feng (Phytochemistry Letters, 2024)

Metals and polycyclic aromatic hydrocarbons pollutants in industrial parks under valley landforms in Tibetan Plateau: Spatial pattern, ecological risk and interaction with soil microorganisms - Chenyang Xue; Yan Du; Graeme Allinson; Xiangfeng Zeng; Xiaojun Li; Huajun Fang (Journal of Hazardous Materials, 2024)

Biomineralization-inspired porous calcium carbonate microspheres as a controlled release system of herbicides/pesticides - Yaoxun Zeng; Xinyi Li; Fangzheng Chen; Huiling Ye; Keyi Rong; Zhili Ran; Binhong Liu; Zhenxing Pan; Xiuxian Xie; Junze Tang; Xujie Liu; Yan He (Journal of Environmental Chemical Engineering, 2024)

Immobilization of a novel d-allulose 3-epimerase from Bacillus cihuensis within metal-organic frameworks - Ziyi Li; Tao Liu; Wenwen Pei; Yan Zeng; Yan Men; Xuegang Luo; Yueming Zhu; Yuanxia Sun (Food Bioscience, 2024)

Heterobimetallic praseodymium-nickel active sites with Pr-N4C2 and Ni-N4 moieties enabling synergistic catalysis of CO2 electroreduction - Heng Zhang; Yajie Cao; Min Sun; Yang Liu; Yan Wang; Haorun Li; Riguang Zhang; Xiaojun Gu; Shanghong Zeng (Chemical Engineering Journal, 2024)

COPD stage detection: leveraging the auto-metric graph neural network with inspiratory and expiratory chest CT images - Xingguang Deng; Wei Li; Yingjian Yang; Shicong Wang; Nanrong Zeng; Jiaxuan Xu; Haseeb Hassan; Ziran Chen; Yang Liu; Xiaoqiang Miao; Yingwei Guo; Rongchang Chen; et al. (Medical & Biological Engineering & Computing, 2024)

Correction to: Near‑global summer circulation response to the spring surface temperature anomaly in Tibetan Plateau –– the GEWEX/LS4P first phase experiment - Yang Zhang; Yan Pan; Yongkang Xue; Ismaila Diallo; Xubin Zeng; Shuting Li; J. David Neelin; William K. M. Lau; Aaron A. Boone; Frederic Vitart; Tandong Yao; Qi Tang; et al. (Climate Dynamics, 2024)

Single and mixed effects of multiple volatile organic compounds exposure on hematological parameters in the U.S. adult population - Yan Zhuang; Laifu Li; Yanqi Zhang; Xuna Liu; Beibei Zeng; Boxu Zhu; Fei Dai (Chemosphere, 2024)

Wavelength dependency and photosensitizer effects in UV-LED photodegradation of iohexol - Meng-Yuan Xu; Chao Zeng; Yi-Li Lin; Tian-Yang Zhang; Qi Fu; Heng-Xuan Zhao; Zhen-Ning Luo; Zheng-Xiong Zheng; Tong-Cheng Cao; Chen-Yan Hu; Bin Xu (Water Research, 2024)

Toxic interactions at the physiological and biochemical levels of green algae under stress of mixtures of three azole fungicides - Li-Tang Qin; Yu-Xue Lei; Min Liu; Hong-Hu Zeng; Yan-Peng Liang; Ling-Yun Mo (Science of The Total Environment, 2024)

Geochemical characteristics of hot springs in active fault zones within the northern Sichuan-Yunnan block: Geochemical evidence for tectonic activity - Yucong Yan; Zuocheng Zhang; Xiaocheng Zhou; Guangcai Wang; Miao He; Jiao Tian; Jinyuan Dong; Jingchao Li; Yunfei Bai; Zhaojun Zeng; Yuwen Wang; Bingyu Yao; et al. (Journal of Hydrology, 2024)

Resistance of Alicyclobacillus acidoterrestris spores to atmospheric cold plasma: Insights from sporulation temperature and mechanism analysis - Lang-Hong Wang; Bing Yan; Gui-Feng Wei; Jian Li; Zhong Han; Junhu Cheng; Xin-An Zeng (Innovative Food Science & Emerging Technologies, 2024)

Mapping hydrogen evolution activity trends of V-based A15 superconducting alloys - Peifeng Yu; Jie Zhan; Xiaobing Zhang; Kangwang Wang; Lingyong Zeng; Kuan Li; Chao Zhang; Longfu Li; Ying Liang; Kai Yan; Yan Sun; Huixia Luo (Chemical Engineering Journal, 2024)

In vitro degradation and dual responsively antibacterial zeolitic imidazolate frameworks-8@Rhein composite coating on magnesium alloy - Chen-Hui Duan; Kui Xue; Lan-Yue Cui; Xue-Wen Jiang; Yan-Yu Zhang; Cheng-Bao Liu; Shuo-Qi Li; Fen Zhang; Rong-Chang Zeng (Chemical Engineering Journal, 2024)

Response of road erosion to hydrological connectivity under a heavy rainstorm in an agricultural watershed on the Loess Plateau - Qian Xu; Juying Jiao; Zeng Yan; Jun Liao; Ziqi Zhang; Mengmeng Li; Xiqin Yan; Yulan Chen; Jianjun Li; Jinshi Jian (CATENA, 2024)

Rice N-biofertilization by inoculation with an engineered photosynthetic diazotroph - Yan Zeng; Mengmei Wang; Yunkai Yu; Lida Wang; Lingwei Cui; Chang Li; Ying Liu; Yanning Zheng (World Journal of Microbiology and Biotechnology, 2024)

Chinese Society of Cardiology guidelines on the diagnosis and treatment of adult fulminant myocarditis - Jiangang Jiang; Hongyang Shu; Dao Wen Wang; Rutai Hui; Chenze Li; Xiao Ran; Hong Wang; Jing Zhang; Shaoping Nie; Guanglin Cui; Dingcheng Xiang; Qun Shao; et al. (Science China Life Sciences, 2024)

High-fat diet impairs gut barrier through intestinal microbiota-derived reactive oxygen species - Nianyi Zeng; Fan Wu; Junqi Lu; Xiang Li; Shaomei Lin; Lang Zhou; Zhongwei Wang; Guangyan Wu; Qingfa Huang; Daowen Zheng; Jie Gao; Shan Wu; et al. (Science China Life Sciences, 2024)

8-OHdG mediates the association of co-exposure to fifty-five typical endocrine-disrupting chemicals with renal function: a cross-section investigation in Southern Chinese adults - Qingfei Chen; Qifei Deng; Qilong Liao; Yan Liu; Zhaorui Zhang; Dehua Wu; Yanrong Lv; Jingyao Qin; Qing Liu; Shuangqi Li; Zihao Long; Xiumei Xing; et al. (Environmental Science and Pollution Research, 2024)

Geochemistry and P-T-t evolution of Paleoproterozoic metapelites of the Zhengjiapo BIF-type iron mine, Jiaobei terrane, North China Craton - Yan-Rong Chen; Xu-Ping Li; Zeng-Sheng Li; Da-Peng Li; Fan-Mei Kong; Hans-Peter Schertl; Yan-Jing Chen (Precambrian Research, 2024)

Manure application amplified the co-selection of quaternary ammonium disinfectant and antibiotic on soil antibiotic resistome - Jie-Yi Zeng; Wei Li; Jian-Qiang Su; Yan-Zi Wang; Yaying Li; Huaiying Yao (Journal of Hazardous Materials, 2024)

Coagulation-centered three-step approach for removing by-product organic pollutants from tetrabromobisphenol A industrial wastewater: Experimental and theoretic investigations - Linlin Hao; Jingshuang Yan; Mingxuan Li; WeiMin Shao; Ming Zeng (Environmental Research, 2024)

The role of miR-222-2p in exosomes secreted by hexavalent chromium-induced premature senescent hepatocytes as a SASP component - Yu Ma; Siwen Li; Shuzi Ye; Sijia Luo; Lai Wei; Ying Su; Yuan Zeng; Yan Shi; Huanfeng Bian; Fang Xiao (Environmental Pollution, 2024)

Deep learning-based identification of vehicular moving forces for bridges without axle configurations - Yan Zeng; Dongming Feng; Jian-An Li; Baoquan Wang (Engineering Structures, 2024)

Manipulating single-crystal packing motifs via selenium substitution and end-group variation for high-performance n-type molecular semiconductors - Yuzhong Chen; Zeng Wu; Zekun Chen; Shuixin Zhang; Zhen Jiang; Wenhao Li; Yan Zhao; Yang Wang; Yunqi Liu (Chemical Engineering Journal, 2024)

High-performance spent coffee grounds-based 3D microporous biochar for the efficient capture of Cd2+ via a multi-pathway mechanism - Zhiwei Jin; Zhenluan Xue; Bo Li; Liying Ou; Linzhe Yan; Lixia Yang; Kai Yin; Jabrane Jouha; Penghui Shao; Zebing Zeng; Shenglian Luo (Chemical Engineering Journal, 2024)

A novel 2-iminobenzimidazole compound, XYA1353, displays in vitro and in vivo anti-myeloma activity via targeting NF-κB signaling - Jian Gao; Jian Zhou; Menghui Zhang; Yan Zhang; Yindi Zeng; Shihao Li; Kailin Xu; Ruosi Yao (Molecular and Cellular Biochemistry, 2024)

Sinomenine protects against atherosclerosis in apolipoprotein E-knockout mice by inhibiting of inflammatory pathway - Zhao Gao; Chao Yang; Guangwei Zeng; Ming Lin; Wei Li; Mengna Sun; Yantao Zhang; Beibei Fan; Yogesh Kumar; Kun Yan (Inflammopharmacology, 2024)

PAH Pollution in Particulate Matter and Risk in Chinese Cities - Yongfu Wu; Ning Zhang; Yan Shi; Zetao Chen; Han Zhang; Jiaqiang Yin; Tao Zeng; Zhongyu Yuan; Ni Li; Yibin Ren; Liqun Cai; Yunzhao Li; et al. (Exposure and Health, 2024)

Analysing N-nitrosamine occurrence and sources in karst reservoirs, Southwest China - Xiaoyu Yan; Bingquan Zhu; Huanfang Huang; Wenwen Chen; Haixiang Li; Yingjie Chen; Yanpeng Liang; Honghu Zeng (Environmental Geochemistry and Health, 2024)

Near-global summer circulation response to the spring surface temperature anomaly in Tibetan Plateau –– the GEWEX/LS4P first phase experiment - Yang Zhang; Yan Pan; Yongkang Xue; Ismaila Diallo; Xubin Zeng; Shuting Li; J. David Neelin; William K. M. Lau; Aaron A. Boone; Frederic Vitart; Tandong Yao; Qi Tang; et al. (Climate Dynamics, 2024)
Subseasonal to seasonal (S2S) prediction of droughts and floods is one of the major challenges of weather and climate prediction. Recent studies suggest that the springtime land surface temperature/subsurface temperature (LST/SUBT) over the Tibetan Plateau (TP) can be a new source of S2S predictability. The project “Impact of Initialized Land Surface Temperature and Snowpack on Subseasonal to Seasonal Prediction (LS4P)” was initiated to study the impact of springtime LST/SUBT anomalies over high mountain areas on summertime precipitation predictions. The present work explores the simulated global scale response of the atmospheric circulation to the springtime TP land surface cooling by 16 current state-of-the-art Earth System Models (ESMs) participating in the LS4P Phase I (LS4P-I) experiment. The LS4P-I results show, for the first time, that springtime TP surface anomalies can modulate a persistent quasi-barotropic Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train from the TP via the northeast Asia and Bering Strait to the western part of the North America, along with the springtime westerly jet from TP across the whole North Pacific basin. The TRC wave train modulated by the TP thermal anomaly play a critical role on the early summer surface air temperature and precipitation anomalies in the regions along the wave train, especially over the northwest North America and the southern Great Plains. The participant models that fail in capturing the TRC wave train greatly under-predict climate anomalies in reference to observations and the successful models. These results suggest that the TP LST/SUBT anomaly via the TRC wave train is the first order source of the S2S variability in the regions mentioned. Furthermore, the TP surface temperature anomaly can influence the Southern Hemispheric circulation by generating cross-equator wave trains. However, the simulated propagation pathways from the TP into the Southern Hemisphere show large inter-model differences. More dynamical understanding of the TRC wave train as well as its cross-equator propagation into the Southern Hemisphere will be explored in the newly launched LS4P phase II experiment.

Remote effects of Tibetan Plateau spring land temperature on global subseasonal to seasonal precipitation prediction and comparison with effects of sea surface temperature: the GEWEX/LS4P Phase I experiment - Yongkang Xue; Ismaila Diallo; Aaron A. Boone; Yang Zhang; Xubin Zeng; William K. M. Lau; J. David Neelin; Tandong Yao; Qi Tang; Tomonori Sato; Myung-Seo Koo; Frederic Vitart; et al. (Climate Dynamics, 2024)
The prediction skill for precipitation anomalies in late spring and summer months—a significant component of extreme climate events—has remained stubbornly low for years. This paper presents a new idea that utilizes information on boreal spring land surface temperature/subsurface temperature (LST/SUBT) anomalies over the Tibetan Plateau (TP) to improve prediction of subsequent summer droughts/floods over several regions over the world, East Asia and North America in particular. The work was performed in the framework of the GEWEX/LS4P Phase I (LS4P-I) experiment, which focused on whether the TP LST/SUBT provides an additional source for subseasonal-to-seasonal (S2S) predictability. The summer 2003, when there were severe drought/flood over the southern/northern part of the Yangtze River basin, respectively, has been selected as the focus case. With the newly developed LST/SUBT initialization method, the observed surface temperature anomaly over the TP has been partially produced by the LS4P-I model ensemble mean, and 8 hotspot regions in the world were identified where June precipitation is significantly associated with anomalies of May TP land temperature. Consideration of the TP LST/SUBT effect has produced about 25–50% of observed precipitation anomalies in most hotspot regions. The multiple models have shown more consistency in the hotspot regions along the Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train. The mechanisms for the LST/SUBT effect on the 2003 drought over the southern part of the Yangtze River Basin are discussed. For comparison, the global SST effect has also been tested and 6 regions with significant SST effects were identified in the 2003 case, explaining about 25–50% of precipitation anomalies over most of these regions. This study suggests that the TP LST/SUBT effect is a first-order source of S2S precipitation predictability, and hence it is comparable to that of the SST effect. With the completion of the LS4P-I, the LS4P-II has been launched and the LS4P-II protocol is briefly presented.

A proteomic study on gastric impairment in rats caused by microcystin-LR - Shang-Chun Li; Li-Hong Gu; Yan-Fang Wang; Li-Mei Wang; Liang Chen; John P. Giesy; Xun Tuo; Wen-Li Xu; Qian-Hui Wu; Yi-Qing Liu; Ming-Huo Wu; Yang-Yang Diao; et al. (Science of The Total Environment, 2024)

Late Cretaceous high Sr/Y rocks and local crustal thickening in the eastern Gangdese batholith, southern Tibet - Guangxu Li; Lingsen Zeng; Li-E Gao; Lilong Yan (Lithos, 2024)

Origins of volatiles and helium fluxes from hydrothermal systems in the Eastern Himalayan Syntaxis and constraints on regional heat and tectonic activities - Yiman Li; Xiaocheng Zhou; Tianming Huang; Jiao Tian; Miao He; Xiaoyi Zhu; Jiang Li; Yongxian Zhang; Zhongliang Wu; Bin Li; Yucong Yan; Yuwen Wang; et al. (Journal of Hydrology, 2024)

Bbhox2 is a key regulator for conidiation and virulence in Beauveria bassiana - Juanjuan Li; Yan Zhang; Shouhao Jiao; Lian He; Yanhua Fan; Xuemeng Han; Binda Sun; Wenqi Zhao; Yanlin Mei; Ning Wei; Haiyue Zeng; Dan Jin (Journal of Invertebrate Pathology, 2024)

Simultaneous removal of nitrate, oxytetracycline and copper by ferrous-manganese co-driven immobilized bioreactor - Peng Zhang; Liang Xu; Junfeng Su; Yuxin Zeng; Yan Liu; Xuan Li (Journal of Hazardous Materials, 2024)

Melatonin alleviates the toxic effect of di(2-ethylhexyl) phthalate on oocyte quality resulting from CEBPB suppression during primordial follicle formation - Jun-Jie Wang; Xiao-Yuan Zhang; Yue Zeng; Qing-Chun Liu; Xin-Lei Feng; Jia-Mao Yan; Ming-Hao Li; Russel J. Reiter; Wei Shen (Journal of Hazardous Materials, 2024)

Preparation of functional geopolymers from municipal solid waste incineration fly ash: An approach combining experimental and computational simulation studies - Mingyi Sun; Liping Ma; Quxiu Dai; Jie Yang; Longgui Xie; Yao Hu; Li Duan; Xiang Yan; Guanyun Zhou; Linglong Zeng; Lan Shao; Bo Hu; et al. (Journal of Environmental Management, 2024)

The promoting effect of electron beam irradiation on enzymatic saccharification and alcohol fermentation of sorghum meal: Related mechanisms - Mengting Yan; Chenyang Sun; Jiangtao Yu; Junqing Bai; Huishan Shen; Xiuyun Zhang; Yifan Lu; Zhuangzhuang Sun; Xiangzhen Ge; Wei Liang; Jie Zeng; Haiyan Gao; et al. (Journal of Cereal Science, 2024)

Spätzle maintains homeostasis of hemolymph microbiota in Scylla paramamosain through Toll2 - Zibo Wei; Ming Zhang; Yan Chen; Hang Hu; Xinshan Zhao; Yuqing Zheng; Ngoc Tuan Tran; Haipeng Feng; Chong Zeng; Shengkang Li (Fish & Shellfish Immunology, 2024)

Exposures to drinking water disinfection byproducts and kidney function in Chinese women - Cheng-Ru Li; Yan-Ling Deng; Yu Miao; Min Zhang; Jia-Yue Zeng; Xiao-Ying Liu; Yang Wu; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; Chong Liu; Qiang Zeng (Environmental Research, 2024)

Methyl jasmonate regulation of pectin polysaccharides in Cosmos bipinnatus roots: A mechanistic insight into alleviating cadmium toxicity - Chun-Yu Fan; Xiao-Fang Yu; Yu-Jia Liu; Xiao-Xuan Zeng; Fu-Wen Luo; Xian-Tong Wang; Xuan Yang; Xiao-Yu Wang; Xiao Xue; Li-Juan Yang; Ting Lei; Ming-Yan Jiang; et al. (Environmental Pollution, 2024)

Genetic Composition of the High-Quality Winter Wheat Varieties ‘Xinmai 26’ and ‘Xinmai 45’ - Li-Juan Yang; Jian Ma; Da-Le Zhang; Hai-Feng Yang; Yan-Qi Dong; Zeng-Jun Qi; Meng-Jiao Li; Zhi-Kai Jiang; Hua-Ping Ma (Plant Molecular Biology Reporter, 2024)

Foliar Application of Organic Sorbitol-Chelated Calcium Promotes Peanut (Arachis hypogaea L.) Growth and Changes Phyllosphere Bacterial Community Structure - Tengsheng Li; Qianqian Wei; Yuzhao Cui; Huiting Tan; Huanyang Zhang; Fanhe Zeng; Xiang Shi; Ziqi Zhang; Jing Zhang; Kezhong Liu; Dongyun Yan (Journal of Soil Science and Plant Nutrition, 2024)

Effect of different hydrogen evolution rates at cathode on bioelectrochemical reduction of CO2 to acetate - Huanying Liu; Yiwei Zeng; Wenwen Chen; Chuanqi Liu; Dezhi Sun; Zhen Hu; Pengsong Li; Haiyu Xu; Hongbin Wu; Bin Qiu; Xinying Liu; Yan Dang (Science of The Total Environment, 2024)

Polystyrene nanoplastics-induced lung apoptosis and ferroptosis via ROS-dependent endoplasmic reticulum stress - Qiumei Wu; Chao Liu; Dan Liu; Yougang Wang; Haomin Qi; Xudong Liu; Yuchao Zhang; Haiyu Chen; Yan Zeng; Jinquan Li (Science of The Total Environment, 2024)

Urinary biomarkers of drinking-water disinfection byproducts in relation to diminished ovarian reserve risk: A case-control study from the TREE cohort - Xiao-Ying Liu; Min Zhang; Xiao-Li Gu; Yan-Ling Deng; Chong Liu; Yu Miao; Yang Wu; Cheng-Ru Li; Jia-Yue Zeng; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; et al. (Science of The Total Environment, 2024)

Joint multi-objective optimization based on multitask and multi-fidelity Gaussian processes for flapping foil - Zhangyuan Wang; Yuqi Yan; Xinyu Zeng; Ruipeng Li; Weicheng Cui; Youzhi Liang; Dixia Fan (Ocean Engineering, 2024)

Fully distributed fiber-optic streamer with small channel spacing for marine seismic acquisition - Junfeng Chen; Hao Li; Xiangpeng Xiao; Zhichao Zeng; Kai Xiao; Pengfei Wen; Zhijun Yan; Qizhen Sun (Ocean Engineering, 2024)

Evaluation of compost quality and the environmental effects of semipermeable membrane composting with poultry manure using sawdust or mushroom residue as the bulking agent - Shuo Liu; Jing-Li Zeng; Zeng-Wen Cheng; Jun-Liang He; Yan-Li Pang; Xin-Di Liao; Si-Cheng Xing (Journal of Environmental Management, 2024)

Durability assessment of hybrid double-skin tubular columns (DSTCs) under simulated marine environments - Jun-Jie Zeng; Zhi-Hao Hao; Xiong-Chao Liang; Jia-Luo Li; Yan Zhuge; Feng Liu; Li-Juan Li (Engineering Structures, 2024)

Photocoupling multi-enzyme nanoreactor simultaneously synthesizes pentanediamine and formic acid - Chenxin Hou; Yan Chu; Jinlei Zeng; Yitong Wang; Ganlu Li; Kequan Chen; Hui Li (Chemical Engineering Journal, 2024)

The application of nanopore targeted sequencing for pathogen diagnosis in bronchoalveolar lavage fluid of patients with pneumonia: a prospective multicenter study - Qinqing Lin; Yake Yao; Xi Li; Shanshan Zhang; Huimin Guo; Xiaolong Ma; Wenyu Chen; Chuhui Ru; Limin Wang; Bin Wang; Qiang Ma; Junfei Zhu; et al. (Infectious Diseases, 2024)

Prenatal exposures to phthalates and bisphenols in relation to oxidative stress: single pollutant and mixtures analyses - Jia-Yue Zeng; Min Zhang; Xu-Hui Chen; Chong Liu; Yan-Ling Deng; Pan-Pan Chen; Yu Miao; Fei-Peng Cui; Tian Shi; Ting-Ting Lu; Xiao-Ying Liu; Yang Wu; et al. (Environmental Science and Pollution Research, 2024)

Induced and natural moss soil crusts accelerate the C, N, and P cycles of PbZn tailings - Kejun Liao; Yue Tao; Jiawei Tu; Yuyang Zeng; Yan Li; Panpan Wang; Xinyue Li; Fan He; Lanzhou Chen (Science of The Total Environment, 2024)

Photo-enhanced oxidation of arsenite by biochar: The effect of pH, kinetics and mechanisms - Tingting You; Shaofeng Wang; Yimei Xi; Shuhua Yao; Zelong Yan; Yu Ding; Yongbin Li; Xiangfeng Zeng; Yongfeng Jia (Journal of Hazardous Materials, 2024)

Associations between urinary biomarkers of exposure to disinfection byproducts and semen parameters: A repeated measures analysis - Min Zhang; Xiao-Ying Liu; Yan-Ling Deng; Chong Liu; Jia-Yue Zeng; Yu Miao; Yang Wu; Cheng-Ru Li; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; Qiang Zeng (Journal of Hazardous Materials, 2024)

Can bioenergy with carbon capture and storage deliver negative emissions? A critical review of life cycle assessment - Junyao Wang; Yawen Zheng; Song He; Jiahui Yan; Xuelan Zeng; Shuangjun Li; Zhipeng Tian; Libin Lei; Yin Chen; Shuai Deng (Journal of Cleaner Production, 2024)

Landscapes of the main components, metabolic and microbial signatures, and their correlations during pile-fermentation of Tibetan tea - Ziqi Wang; Hongyu Li; Weimin Huang; Songqi Duan; Yue Yan; Zhen Zeng; Zhengfeng Fang; Cheng Li; Bin Hu; Wenjuan Wu; Xiguo Lan; Yuntao Liu (Food Chemistry, 2024)

Riboflavin-loaded carbon cloth aids the anaerobic digestion of cow dung by promoting direct interspecies electron transfer - Yiwei Zeng; Huanying Liu; Wenwen Chen; Haoyong Li; He Dong; Hongbin Wu; Haiyu Xu; Dezhi Sun; Xinying Liu; Pengsong Li; Bin Qiu; Yan Dang (Environmental Research, 2024)

Exposure levels and determinants of placental polybrominated diphenyl ethers in Chinese pregnant women - Yijun Liu; Yan Xie; Yingkuan Tian; Juan Liao; Derong Fang; Linglu Wang; Rong Zeng; Shimin Xiong; Xingyan Liu; Qing Chen; Ya Zhang; Hongyu Yuan; et al. (Environmental Research, 2024)

Low-cost separator with dust-free fabric composite cellulose acetate toward stable dendrite-free aqueous zinc-ion batteries - Yusheng Lei; Qingning Li; Qifan Liu; Yanfei Zeng; Jia Li; Wei Huang; Feisheng Wang; Shengkui Zhong; Dongliang Yan (Chemical Engineering Journal, 2024)

Effect comparisons of different conditioners and microbial agents on the degradation of estrogens during dairy manure composting - Yan Li; Dong Zeng; Xiao-Lu Jiang; De-Chun He; Jia-Wu Hu; Zi-Wei Liang; Jia-Cheng Wang; Wang-Rong Liu (Chemosphere, 2023)

Analyzing the impact of various factors on leaf surface temperature based on a new tree-scale canopy energy balance model - Ruibin Li; Fanxing Zeng; Yi Zhao; Yan Wu; Jianlei Niu; Liangzhu (Leon) Wang; Naiping Gao; Haizhu Zhou; Xing Shi; Zishuo Huang (Sustainable Cities and Society, 2023)

Molecular hydrogen-based irrigation extends strawberry shelf life by improving the synthesis of cell wall components in fruit - Zhiwei Jin; Ziyu Liu; Genmei Chen; Longna Li; Yan Zeng; Xu Cheng; Didier Pathier; Guoyi Xu; Wenbiao Shen (Postharvest Biology and Technology, 2023)

Three point mutations in AaCYP51 combined with induced overexpression of AaCYP51 conferred low-level resistance to mefentrifluconazole in Alternaria alternata - Guixiang Li; Xiuhuan Li; Yan Zeng; Shuailin Liao; Yue Chen; Jianqiang Miao; Qin Peng; Xili Liu (Pesticide Biochemistry and Physiology, 2023)

Beyond filterability: Understanding the complexities of sludge dewatering through typical coagulation and advanced oxidation - Wen-Hui Liu; Hao Zhang; Ya-Li Zhang; Ping Sun; Yuan-Ping Zeng; Yun-Yan Gao; Hou-Feng Wang; Raymond Jianxiong Zeng (Journal of Cleaner Production, 2023)

Effects of long-term blue light irradiation on carotenoid biosynthesis and antioxidant activities in Chinese cabbage (Brassica rapa L. ssp. pekinensis) - Ruixing Zhang; Wenjing Yang; Qiming Pan; Qi Zeng; Chengtai Yan; Xue Bai; Yao Liu; Lugang Zhang; Baohua Li (Food Research International, 2023)

A simulated drier climate reduces growth and alters functional traits of Eucalyptus trees: A three-year experiment in South China - Ling Yang; Jiejun Kong; Yaqian Gao; Zetao Chen; Yubiao Lin; Shucai Zeng; Yan Su; Jiyue Li; Qian He; Quan Qiu (Forest Ecology and Management, 2023)

Allyl methyl disulfide (AMDS) prevents N,N-dimethyl formamide-induced liver damage by suppressing oxidative stress and NLRP3 inflammasome activation - Long-Xia Li; Lin Wang; Shuo Wang; Xiu-Ning Zhang; Hong Liu; Yan-Jing Zhang; Chuan-Tao Wu; Cui-Li Zhang; Tao Zeng (Food and Chemical Toxicology, 2023)

Cannabidiol protects the liver from α-Amanitin-induced apoptosis and oxidative stress through the regulation of Nrf2 - Haowei Wang; Genmeng Yang; Xiaoxing Zhang; Huijie Zhang; Yan Liu; Chan Wang; Lin Miao; Yi Li; Yizhen Huang; Hanxin Teng; Shangwen Wang; Hao Cheng; et al. (Food and Chemical Toxicology, 2023)

Improving Blood Monocyte Energy Metabolism Enhances Its Ability to Phagocytose Amyloid-β and Prevents Alzheimer’s Disease-Type Pathology and Cognitive Deficits - Zhi-Hao Liu; Yu-Di Bai; Zhong-Yuan Yu; Hui-Yun Li; Jie Liu; Cheng-Rong Tan; Gui-Hua Zeng; Yun-Feng Tu; Pu-Yang Sun; Yu-Juan Jia; Jin-Cai He; Yan-Jiang Wang; et al. (Neuroscience Bulletin, 2023)

17β-Estradiol Mediates Staphylococcus aureus Adhesion in Vaginal Epithelial Cells via Estrogen Receptor α-Associated Signaling Pathway - Lina Yan; Can Rui; Bin Zhuang; Xia Liu; Ting Luan; Lisha Jiang; Zhiyong Dong; Qing Wang; Aiwen Wu; Ping Li; Xinyan Wang; Xin Zeng (Current Microbiology, 2023)

The model and mechanism of adsorptive technologies for wastewater containing fluoride: A review - Zhen Zeng; Qian Li; Jia Yan; Lei Huang; Samuel Raj Babu Arulmani; Hongguo Zhang; Shaojian Xie; Wenghong Sio (Chemosphere, 2023)

Navigating the future: China’s photovoltaic roadmap challenges - Moisés Gómez; Guochang Xu; Yan Li; Jinhui Li; Xi Lu; Kebin He; Xianlai Zeng (Science Bulletin, 2023)

Salviamilthone A-O, diterpenoid quinones from Salvia miltiorrhiza - Ying-Jie Ren; Yan-Gang Cao; Meng-Nan Zeng; Qin-Qin Zhang; Yan-Ling Liu; Chen He; Xu Chen; Xi-Ling Fan; Xiang-Da Li; Xiao-Ke Zheng; Wei-Sheng Feng (Phytochemistry, 2023)

α-Terpineol affects social immunity, increasing the pathogenicity of entomopathogenic nematodes to subterranean termites (Isoptera) - Wenhui Zeng; Tong Chen; Yong Chen; Xun Yan; Wenjing Wu; Shijun Zhang; Zhiqiang Li (Pesticide Biochemistry and Physiology, 2023)

The fate of kyanite in ultrahigh-pressure metasedimentary rocks, southwestern Tianshan, NW China - Zeng Lü; Jun Yan; Jiabin Li (Lithos, 2023)

Enhancing data reliability in quantitative characterization of moisture distribution in sludge using DSC: Impact of sample attributes and test parameters - Ya-Li Zhang; Hao Zhang; Wen-Hui Liu; Ping Sun; Shao-Ming Zheng; Yun-Yan Gao; Yuan-Ping Zeng; Hou-Feng Wang; Raymond Jianxiong Zeng (Journal of Environmental Management, 2023)

Enhanced sequestration of CO2 from simulated electrolytic aluminum flue gas by modified red mud - Xingyuan Wang; Jiamin Qi; Hengxi Zhu; Jiancheng Wang; Heping Zeng; Bin Li; Si Yan (Journal of Environmental Management, 2023)

The burden of chronic kidney disease associated with dietary exposure to cadmium in China, 2020 - Jiao Huang; Lisha Luo; Yongbo Wang; Siyu Yan; Xuhui Li; Binghui Li; Qiao Huang; Yunyun Wang; Yuanyuan Zhang; Sheng Wei; Yibaina Wang; Xiantao Zeng (Environmental Pollution, 2023)

Behavior of 3D-printed HPC plates with FRP grid reinforcement under bending - Jun-Jie Zeng; Pei-Lin Li; Zi-Tong Yan; Jie-Kai Zhou; Wai-Meng Quach; Yan Zhuge (Engineering Structures, 2023)

Low-temperature degradation of lignin in aprotic solvent system for preparation of monophenolic platform chemicals - Xu Zeng; Yan Xu; Qiqi Dai; Jiaqi Li; Qixuan Lin; Jun Ye; Chuanfu Liu; Wu Lan (Chemical Engineering Journal, 2023)

Gas geochemical evidence for the India-Asia lithospheric transition boundary near the Karakorum fault in western Tibet - Yunfei Bai; Zheming Shi; Xiaocheng Zhou; Chen Wu; Guangcai Wang; Miao He; Jingchao Li; Jinyuan Dong; Jiao Tian; Yucong Yan; Fengli Liu; Shupei Ouyang; et al. (Chemical Geology, 2023)

Overview and countermeasures of cancer burden in China - Yian Wang; Qijia Yan; Chunmei Fan; Yongzhen Mo; Yumin Wang; Xiayu Li; Qianjin Liao; Can Guo; Guiyuan Li; Zhaoyang Zeng; Wei Xiong; He Huang (Science China Life Sciences, 2023)

JcSEUSS1 negatively regulates reproductive organ development in perennial woody Jatropha curcas - Jingxian Wang; Xue Bai; Yiqing Su; Hongjun Deng; Li Cai; Xin Ming; Yan-Bin Tao; Huiying He; Zeng-Fu Xu; Mingyong Tang (Planta, 2023)

A new modified pterocarpan glycoside from Sophora flavescens - Yan Lin; Jing-Jing Li; Lei He; Qi-Rui Li; Qing-De Long; Xu Zhang; Zhu Zeng (Natural Product Research, 2023)

First report of tea leaf spot disease caused by Bipolaris bicolor on tea plants (Camellia sinensis cv. Fenghuang Dancong) in China - Yu-Xian Zhong; Ying-Yao Liu; Min Li; Dylan O’Neill Rothenberg; Zhen Zeng; Ya-Hui Huang; Chang-Yu Yan (Journal of Plant Pathology, 2023)

Removal ibuprofen from aqueous solution by a noval Al-modified biochar - Dayang Yu; Siqi Zeng; Yifan Wu; Yuan Li; Hailong Tian; Tian Xie; Yan Yu (Environmental Science and Pollution Research, 2023)

Efficiently catalytic degradation of tetracycline via persulfate activation with plant-based biochars: Insight into endogenous mineral self-template effect and pyrolysis catalysis - Shaoyi Zeng; Kunquan Li; Xia Xu; Jiayong Zhang; Yan Xue (Chemosphere, 2023)

De novo artificial synthesis of hexoses from carbon dioxide - Jiangang Yang; Wan Song; Tao Cai; Yuyao Wang; Xuewen Zhang; Wangyin Wang; Peng Chen; Yan Zeng; Can Li; Yuanxia Sun; Yanhe Ma (Science Bulletin, 2023)

Analysis of the suitable ecological flow of benthic animals in the lower reaches of Xiangjiaba Reservoir in the upper reaches of the Yangtze River based on the physical habitat model - Dingxin Chen; Zefan Yang; Qinghui Zeng; Weize Wang; Long Yan; Pu Zhang; Xinyu Li; Peng Hu; Hao Wang (Journal of Hydrology, 2023)

Insight into the selection of oxidant in persulfate activation system: The effect of the target pollutant properties - Xuerong Zhou; Eydhah Almatrafi; Shiyu Liu; Huchuan Yan; Dengsheng Ma; Shixian Qian; Lei Qin; Huan Yi; Yukui Fu; Ling Li; Mingming Zhang; Fuhang Xu; et al. (Journal of Hazardous Materials, 2023)

Melatonin alleviates aluminum toxicity by regulating aluminum-responsive and nonresponsive pathways in hickory - Hao Zeng; Yaru Li; Weijie Chen; Jingwei Yan; Jiasheng Wu; Heqiang Lou (Journal of Hazardous Materials, 2023)

Surface modification of PVDF membranes with quaternized chitosan for selective separation of negatively charged polysaccharides – exemplified with heparin - Rui Zhang; Yahong Li; Jingjing Yan; Jianxian Zeng; Yuan Liu; Mingming Zhang; Pengfei Liu; Xiaoping Huang; Erdong Zhang; Kaipeng Cheng; Jingyu Chen; Jialin Sun (Journal of Environmental Chemical Engineering, 2023)

The g-C3N4 decorated carbon aerogel with integrated solar steam generation and photocatalysis for effective desalination and water purification - He Zhang; Wenmei Luo; Yuping Du; Hao Shi; Guangyong Zeng; Xinxing Yan; Xiaoke Li (Desalination, 2023)

Doubling the coating-substrate pull-off strength by growth of CaCO3 nano-crystals - Yuqing Dai; Yan Lan; Rongjia Wen; Chengji Xu; Ahmed Al-Mansour; Zhidong Zhang; Le Li; Qiang Zeng; Kefei Li (Chemical Engineering Journal, 2023)

A novel self-bonding 3D carbon particle bioanode derived from agricultural residue for improving the enrichment of electroactive bacteria in microbial fuel cell - Shujuan Liu; Zeng Li; Dandan Liang; Chen Yan; Weihua He; Yujie Feng (Chemical Engineering Journal, 2023)

Efficient hydrogenation of aliphatic acyclic amides to amines by bimetallic NiMo nitrides via heterogeneous catalysis - Huiru Yang; Linyuan Zhou; Honggang Chen; Yan Zeng; Dan Li; Changwei Hu (Chemical Engineering Journal, 2023)

Single Ru atoms confined into MOF/C3N4 for dual improved photocatalytic carbon dioxide reduction and nitrogen fixation - Zhu Ding; Xusheng Li; Chenxu Kang; Sai Yan; Dandan Zhao; Houzhi Cai; Su-Yun Zhang; Yu-Jia Zeng (Chemical Engineering Journal, 2023)

Developmental regulation of conserved non-coding element evolution provides insights into limb loss in squamates - Zeng Wang; Changjun Peng; Wei Wu; Chaochao Yan; Yunyun Lv; Jia-Tang Li (Science China Life Sciences, 2023)

Refined Spatialization of 10-Day Precipitation in China Based on GPM IMERG Data and Terrain Decomposition Using the BEMD Algorithm - Xiaochen Zhu; Qiangyu Li; Yan Zeng; Guanjie Jiao; Wenya Gu; Xinfa Qiu; Ailifeire Wumaer (Journal of Meteorological Research, 2023)

Deep UV-LED induced nitrate-to-nitrite conversion for total dissolved nitrogen determination in water samples through persulfate digestion and capillary electrophoresis - Dongmei Liu; Yu Xiong; Hui Zeng; Jin Xu; Biyu Tang; Yan Li; Min Zhang (Analytica Chimica Acta, 2023)

Evolutionary characterization and pathogenicity of Getah virus from pigs in Guangdong Province of China - Jinghua Pan; Haoquan Zhang; Xiuqiao Chen; Mengyi Zeng; Hui Han; Yajing Guo; Jiaming Li; Shicheng Luo; Guangzhi Yan; Shengnan Chen; Meilian Mo; Mingjie Liu; et al. (Archives of Virology, 2023)

Multi-target tracking in underwater multistatic AUV networks with a robust Poisson Multi-Bernoulli filter - Yuexing Zhang; Yiping Li; Shuo Li; Junbao Zeng; Yiqun Wang; Shuxue Yan (Ocean Engineering, 2023)

Damage detection of foundation pile in high-pile wharf based on statistical high-order moment of dynamic response under regular wave excitation - Rui-hu Zhu; Qi-ming Wang; Jin-hai Zheng; Hai-kun Zeng; Jia-bao Zhang; Yan Hu; Cheng-ming Li (Ocean Engineering, 2023)

Thallium release from biochar-amended soil to runoff in laboratory experiments - Lezhang Wei; Dafeng Cai; Fangqing Li; Yu Liu; Linwei Zeng; Dinggui Luo; Xuexia Huang; Tangfu Xiao; Hang Shi; Haiqi Yan (Environmental Pollution, 2023)

Individual and joint associations of urinary phthalate metabolites with polycystic ovary and polycystic ovary syndrome: Results from the TREE cohort - Min Zhang; Chong Liu; Xiao-Qiong Yuan; Fei-Peng Cui; Yu Miao; Wen Yao; Dan-Yu Qin; Yan-Ling Deng; Pan-Pan Chen; Jia-Yue Zeng; Xiao-Ying Liu; Yang Wu; et al. (Environmental Toxicology and Pharmacology, 2023)

Formation and distribution of landslides controlled by thrust-strike-slip fault zones and fluvial erosion in the Western Qinling Mountains, China - Tianjun Qi; Xingmin Meng; Yan Zhao; Xiaojun Su; Guan Chen; Runqiang Zeng; Yi Zhang; Yajun Li; Dongxia Yue (Engineering Geology, 2023)

Associations of Blood and Cerebrospinal Fluid Aβ and tau Levels with Renal Function - Hao-Lun Sun; Xiu-Qing Yao; Li Lei; Wang-Sheng Jin; Yu-Di Bai; Gui-Hua Zeng; An-Yu Shi; Jun Liang; Li Zhu; Yu-Hui Liu; Yan-Jiang Wang; Xian-Le Bu (Molecular Neurobiology, 2023)

Non-monotonic Association Between Chlorinated Polyfluorinated Ether Sulfonic Acids Exposure and the Risk of Overweight/Obesity Status in Adults - Chu Chu; Qiu-Ling Fang; Xin-Xin Cui; Peng-Xin Dong; Zhengmin Qian; Stephen Edward McMillin; Steven W. Howard; Yan-Qiu Ou; Qing-Qing Li; Lu-Yin Wu; Li-Xia Liang; Shuang-Jian Qin; et al. (Exposure and Health, 2023)

A nosocomial Pseudomonas aeruginosa ST3495 isolated from a wild Burmese python (Python bivittatus) with suppurative pneumonia and bacteremia in Hainan, China - Roushan Li; Bo Ling; Jifeng Zeng; Xin Wang; Nuo Yang; Lixia Fan; Guiying Guo; Xuesong Li; Fei Yan; Jiping Zheng (Brazilian Journal of Microbiology, 2023)

Development of a mid-Neoproterozoic arched rift in eastern South China as a response to the Rodinia breakup - Xinqi Yu; Junlai Liu; Jun Hu; Yan Zeng; Linghui Meng; Wei Li (Precambrian Research, 2023)

The Tartary buckwheat bHLH gene ALCATRAZ contributes to silique dehiscence in Arabidopsis thaliana - Wenjun Sun; Ying Chen; Jing Zeng; Chenglei Li; Min Yao; Moyang Liu; Zhaotang Ma; Li Huang; Jun Yan; Junyi Zhan; Hui Chen; Tongliang Bu; et al. (Plant Science, 2023)

Prolonged fluoride exposure induces spatial-memory deficit and hippocampal dysfunction by inhibiting small heat shock protein 22 in mice - Jinge Xin; Bin Zhu; Hesong Wang; Yong Zhang; Ning Sun; Xi Cao; Liqin Zheng; Yanxi Zhou; Jing Fang; Bo Jing; Kangcheng Pan; Yan Zeng; et al. (Journal of Hazardous Materials, 2023)

Branched DNA switchable CRISPR-Cas12a system for sensing FEN1 activity - Xingrong Li; Decai Zhang; Xiaoying Cai; Xiaojia Shu; Zijie Zeng; Shijia Ding; Yurong Yan (Chemical Engineering Journal, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Soil extracellular enzymes characteristics and their controlling factors along the elevation gradient in Qinghai-Tibet Plateau, China - Yan-xia Pan; Xin-rong Li; Zeng-ru Wang; Li Feng; Lei Huang; Bing-yao Wang; Jing-yao Sun (Applied Soil Ecology, 2023)

Relationship between anthropogenic factors and freshwater quality in Hainan Province, south China - Jianrong Ma; Qiao Chen; Xianliang Wu; Hans W Paerl; Justin D. Brookes; Guangyu Li; Yan Zeng; Jingfu Wang; Jingan Chen; Boqiang Qin (Environmental Science and Pollution Research, 2023)

Petrogenesis of Sn-related granitoids and implications for the formation of the world-class Gejiu Sn district, South China: Insights from whole-rock and accessory mineral geochemistry - Xin Li; Yuan-chuan Zheng; Yang Shen; Chang-da Wu; Pei-yan Xu; Yan-shen Yang; Lu Wang; Zeng-qian Hou (Lithos, 2023)

Melting a melt-metasomatized subcontinental lithospheric mantle: Evidence from Oligocene lamproites within the Gangdese batholith, southern Tibet - Yihong Tian; Lingsen Zeng; Yu Shen; Lilong Yan; Linghao Zhao; Qian Xu; Guangxu Li; Yinglong Di (Lithos, 2023)

Oral exposure to polystyrene nanoplastics reduced male fertility and even caused male infertility by inducing testicular and sperm toxicities in mice - Wenqing Xu; Yangyang Yuan; Yan Tian; Cheng Cheng; Ying Chen; Lianjie Zeng; Yuan Yuan; Dandan Li; Liping Zheng; Tao Luo (Journal of Hazardous Materials, 2023)

Pyrolysis/combustion potential and heavy metal risk of oily sludge and derived products in industrial scale - Hongdi Yu; Jiantao Li; Fawei Lin; Menglan Zeng; Rundong Li; Beibei Yan; Guanyi Chen (Fuel, 2023)

Culture-dependent and culture-independent approaches to reveal the aflatoxin B1-producing fungi in Pixian Doubanjiang, a typical condiment in Chinese cuisine - Fengjiao Yang; Liang Zhang; Yuqi Zhang; Yan Zeng; Yufeng Li; Peibin Zeng (Food Control, 2023)

Fine mapping and characterization of a major QTL for plant height on chromosome 5A in wheat - Lingli Li; Dengan Xu; Yingjie Bian; Bingyan Liu; Jianqi Zeng; Lina Xie; Siyang Liu; Xiuling Tian; Jindong Liu; Xianchun Xia; Zhonghu He; Yan Zhang; et al. (Theoretical and Applied Genetics, 2023)

Gene–allele system of shade tolerance in southern China soybean germplasm revealed by genome-wide association study using gene–allele sequence as markers - Yanzhu Su; Zhipeng Zhang; Jianbo He; Weiying Zeng; Zhaoyan Cai; Zhenguang Lai; Yongpeng Pan; Xiaoshuai Hao; Guangnan Xing; Wubin Wang; Jiaoping Zhang; Yan Li; et al. (Theoretical and Applied Genetics, 2023)

3D printed cartridge for high-speed capillary electrophoresis with sheath liquid thermostatting and contactless conductivity detection - Xing Liu; Wenshan Liang; Hui Zeng; Yiyu Jiang; Yan Li; Min Zhang (Analytica Chimica Acta, 2023)

Transcriptional regulation of MbACO2-mediated ethylene synthesis during postharvest banana ripening - Yuqi Tang; Yan Yan; Weiwei Tie; Xiaoxue Ye; Liwang Zeng; Liming Zeng; Jinghao Yang; Biyu Xu; Meiying Li; Yu Wang; Zhengnan Xie; Zhiqiang Jin; et al. (Postharvest Biology and Technology, 2023)

Genesis of the Yawan Sb deposit, West Qinling Orogen, Central China: Constraints from S–Pb–C–O isotopes and Sm Nd geochronology - Zhao-yang Song; Yan-chen Yang; Shi-jiong Han; Bao-yi Li; Zi-jian Zeng; Tian-wen Chen (Journal of Geochemical Exploration, 2023)

Synergistic adsorption and degradation of sulfamethazine by tobacco stalk-derived activated biochar: Preparation, mechanism insight and application - Mengcan Ju; Pinhua Rao; Lili Yan; Dungang Gu; Guanghui Li; Qincheng Chen; Shanliang Liu; Zhihong Zeng; Min Zhang; Wenjuan Zhang (Journal of Environmental Chemical Engineering, 2023)

Advanced nitrogen removal from low carbon nitrogen ratio domestic sewage via continuous plug-flow anaerobic/oxic/anoxic system: Enhanced by endogenous denitrification - Huaguang Liu; Wenyi Dong; Zilong Zhao; Hongjie Wang; Zilong Hou; Yanchen Li; Zhiwei Zeng; Jin Xie; Fupeng Wang; Xueyon Liu; Yu Yan; Yanhui Qu (Bioresource Technology, 2023)

Effects of Antimicrobial Peptides Gal-13 on the Growth Performance, Intestinal Microbiota, Digestive Enzyme Activities, Intestinal Morphology, Antioxidative Activities, and Immunity of Broilers - Yufei Wang; Jianzhen Li; Xixi Dai; Zhenhua Wang; Xueqin Ni; Dong Zeng; Yan Zeng; Dongmei Zhang; Kangcheng Pan (Probiotics and Antimicrobial Proteins, 2023)

A Retrospective Study of Clinical and Immunological Features of a Pediatric Population with Talaromyces marneffei Infection - Huishan Chen; Muxia Yan; Haowei He; Li Zhang; Huasong Zeng; Yiqian Wang (Mycopathologia, 2023)

ADGB variants cause asthenozoospermia and male infertility - Ronggui Qu; Zhihua Zhang; Ling Wu; Qun Li; Jian Mu; Lin Zhao; Zheng Yan; Wenjing Wang; Yang Zeng; Ruyi Liu; Jie Dong; Qiaoli Li; et al. (Human Genetics, 2023)

Can planned control measures for private passenger vehicles achieve China's carbon peak goal and mitigate the environmental impact? - Dan Zeng; Yan Dong; Huajun Cao; Yuke Li; Bernard Hon; Cuimei Ma; Chris Yuan; Michael Z. Hauschild (Resources, Conservation and Recycling, 2023)

Histone demethylase MaJMJ15 is involved in the regulation of postharvest banana fruit ripening - Jing Zeng; Guoxiang Jiang; Hanzhi Liang; Huiling Yan; Xiangjin Kong; Xuewu Duan; Zhiwei Li (Food Chemistry, 2023)

Development and mechanical properties of soy protein fibrils-chitin nanowhiskers complex gel - Xie-ying Huang; Yu-yan Huang; Qing-zhu Zeng; Peng Liu; Jian Li; Yang Yuan (Food Hydrocolloids, 2023)

Early 7,8-Dihydroxyflavone Administration Ameliorates Synaptic and Behavioral Deficits in the Young FXS Animal Model by Acting on BDNF-TrkB Pathway - Yu-shan Chen; Si-ming Zhang; Wei Tan; Qiong Zhu; Chao-xiong Yue; Peng Xiang; Jin-quan Li; Zhen Wei; Yan Zeng (Molecular Neurobiology, 2023)

Genetic diversity of Toll‐like receptor 9 in swamp eels ( Monopterus albus ) - Caifei Huo; Haifeng Tian; Han Rao; Bo Zeng; Debing Li; Zhong Li; Yan Li (Journal of Fish Biology, 2023)
The swamp eel, Monopterus albus , is an important aquaculture species in Asia (mainly China) whose production has seriously suffered from infectious diseases. In spite of the critical requirement for aquaculture practices, to date there is scant information on its immune defence. Here, the genetic characteristics of Toll‐like receptor 9 (TLR9), which plays crucial roles in the initiation of host defence against microbial invasion, were analysed. It exhibits a striking lack of genetic variation resulting from a recent demographic bottleneck. A comparison with the homologue of M. javanensis revealed that replacement but not silent differences have nonrandomly accumulated in the coding sequences at the early stage following their split from a common ancestor. Furthermore, the replacements relevant to the type II functional divergence have mainly occurred in structural motifs mediating ligand recognition and receptor homodimerization. These results provide hints to understand the diversity‐based strategy of TLR9 in the arms race against pathogens. Furthermore, the findings reported here give credence to the importance of basic immunology knowledge, especially for the key elements, in genetic engineering and breeding for disease resistance in the eel and other fishes.

Multi-Target Tracking in Multi-Static Networks with Autonomous Underwater Vehicles Using a Robust Multi-Sensor Labeled Multi-Bernoulli Filter - Yuexing Zhang; Yiping Li; Shuo Li; Junbao Zeng; Yiqun Wang; Shuxue Yan (Journal of Marine Science and Engineering, 2023)
This paper proposes a centralized MTT method based on a state-of-the-art multi-sensor labeled multi-Bernoulli (LMB) filter in underwater multi-static networks with autonomous underwater vehicles (AUVs). The LMB filter can accurately extract the number of targets and trajectories from measurements affected by noise, missed detections, false alarms and port–starboard ambiguity. However, its complexity increases as the number of sensors increases. In addition, due to the time-varying underwater environment, AUV detection probabilities are time-varying, and their mismatches often lead to poor MTT performance. Consequently, we detail a robust multi-sensor LMB filter that estimates detection probabilities and multi-target states simultaneously in real time. Moreover, we derive an effective approximate form of the multi-sensor LMB filter using Kullback–Leibler divergence and develop an efficient belief propagation (BP) implementation of the multi-sensor LMB filter. Our method scales linearly with the number of AUVs, providing good scalability and low computational complexity. The proposed method demonstrates superior performance in underwater multi-AUV network MTT simulations.

Earthquakes evoked by lower crustal flow: Evidence from hot spring geochemistry in Lijiang-Xiaojinhe fault - Zebin Luo; Xiaocheng Zhou; Miao He; Jinlong Liang; Jingchao Li; Jinyuan Dong; Jiao Tian; Yucong Yan; Ying Li; Fengli Liu; Shupei Ouyang; Kaiyi Liu; et al. (Journal of Hydrology, 2023)

In-situ construction of Mn0.2Cd0.8S/NiB composite for highly efficient full spectrum-driven photocatalytic H2 evolution - Ya Li; Ya-Nan Wu; Yi Yang; Yan Xiong; Yi-Ke Li; Qun-Zeng Huang (Journal of Environmental Chemical Engineering, 2023)

The diverging epigenomic landscapes of honeybee queens and workers revealed by multiomic sequencing - Yong Zhang; Xu Jiang He; Andrew B. Barron; Zhen Li; Meng Jie Jin; Zi Long Wang; Qiang Huang; Li Zhen Zhang; Xiao Bo Wu; Wei Yu Yan; Zhi Jiang Zeng (Insect Biochemistry and Molecular Biology, 2023)

The effect of clay type and solid wettability on bitumen extraction from Canadian oil sands - An Li; Rui Li; Ci Yan; Han Wang; Qingxia Liu; Jacob H. Masliyah; Hongbo Zeng; Zhenghe Xu (Fuel, 2023)

Lipopolysaccharide-induced endotoxaemia during adolescence promotes stress vulnerability in adult mice via deregulation of nuclear factor erythroid 2-related factor 2 in the medial prefrontal cortex - Yan-chen Chen; Yan-hua Huang; Li Song; Xiao-han Tong; Jun-feng Li; Song Lin; Xi Chen; Ji-chun Zhang; Zi-li Zhang; Qi-yi Zeng (Psychopharmacology, 2023)

Production of MSTN knockout porcine cells using adenine base-editing-mediated exon skipping - Shuai-peng Yang; Xiang-xing Zhu; Zi-xiao Qu; Cai-yue Chen; Yao-bing Wu; Yue Wu; Zi-dan Luo; Xin-yi Wang; Chu-yu He; Jia-wen Fang; Ling-qi Wang; Guang-long Hong; et al. (In Vitro Cellular & Developmental Biology - Animal, 2023)

Joint effects of temperature and copper exposure on developmental and gene-expression responses of the marine copepod Tigriopus japonicus - Adela Jing Li; Racliffe Weng Seng Lai; Guang-Jie Zhou; Priscilla To Yan Leung; Eddy Y. Zeng; Kenneth Mei Yee Leung (Ecotoxicology, 2023)

Accurate and rapid quantification of PD-L1 positive exosomes by a triple-helix molecular probe - Zhichao Fan; Qin Weng; Yingxue Li; Tian Zeng; Junyi Wang; Honglan Zhang; Hua Yu; Yan Dong; Xiang Zhao; Jianjun Li (Analytica Chimica Acta, 2023)

Effect of feeding level on growth, digestive and metabolic enzymes and antioxidant capacity in juvenile Yangtze sturgeon (Acipenser dabryanus) - Bin He; Bo Zhou; Hang Xie; Zeng-Tan Hu; Bin Wang; Jun-Lin Zhang; Qing-Zhi Li; Feng-Qi Zhao; Xing Liu; Qian-Dong Li; Tao Yan (Aquaculture, 2023)

Energetic and Life Cycle Assessment of Direct Air Capture: A Review - Junyao Wang; Shuangjun Li; Shuai Deng; Xuelan Zeng; Kaixiang Li; Jianping Liu; Jiahui Yan; Libin Lei (Sustainable Production and Consumption, 2023)

Unveiling the roles of dissolved organic matters derived from different biochar in biochar/persulfate system: Mechanism and toxicity - Xuerong Zhou; Cui Lai; Eydhah Almatrafi; Shiyu Liu; Huchuan Yan; Shixian Qian; Hanxi Li; Lei Qin; Huan Yi; Yukui Fu; Ling Li; Mingming Zhang; et al. (Science of The Total Environment, 2023)

Heterogeneous chemistry of ozone with floor cleaning agent: Implications of secondary VOCs in the indoor environment - Jinli Xu; Huifan Deng; Yiqun Wang; Pan Li; Jianqiang Zeng; Hongwei Pang; Xin Xu; Xue Li; Yan Yang; Sasho Gligorovski (Science of The Total Environment, 2023)

Associations of per- and polyfluoroalkyl substances and their alternatives with bone mineral density levels and osteoporosis prevalence: A community-based population study in Guangzhou, Southern China - Shujun Fan; Yan Wu; Michael S. Bloom; Jiayun Lv; Li Chen; Weiping Wang; Zhi Li; Qinqin Jiang; Li Bu; Jie Shi; Tongxing Shi; Xiaowen Zeng; et al. (Science of The Total Environment, 2023)

Associations between trace level thallium and multiple health effects in rural areas: Chinese Exposure and Response Mapping Program (CERMP) - Yun-Jiang Yu; Zhen-Chi Li; Yang Zhou; Chen-Yin Dong; Hong-Xuan Kuang; Tong Zheng; Ming-Deng Xiang; Xi-Chao Chen; Hong-Yan Li; Xiao-Wen Zeng; Shu-Li Xu; Li-Wen Hu; et al. (Science of The Total Environment, 2023)

The impact of smart cities on entrepreneurial activity: Evidence from a quasi-natural experiment in China - Chengming Li; Xinyi Zhang; Xiaoqi Dong; Qiangming Yan; Liangen Zeng; Zeyu Wang (Resources Policy, 2023)

Silicotungstic acid as electron transfer mediator in Z-scheme g-C3N4/H4SiW12O40/Ag3PO4: Accelerated charge interface transportation for high-efficient photocatalysis - Yun Zhong; Jie Shi; Kexin Li; Huiqin Guo; Liushui Yan; Zhenxing Zeng (Process Safety and Environmental Protection, 2023)

Variations in oolong tea key characteristic floral aroma compound contents among tea (Camellia sinensis) germplasms exposed to postharvest stress - Shuhua Wu; Dachuan Gu; Yuzhen Chen; Feng Wang; Jiajia Qian; Lanting Zeng; Jinchi Tang; Ying Yan; Changsong Chen; Jianlong Li (Postharvest Biology and Technology, 2023)

Characterization of the aroma profiles of cold and hot break tomato pastes by GC-O-MS, GC × GC-O-TOF-MS, and GC-IMS - Xuejie Li; Xiangquan Zeng; Huanlu Song; Yu Xi; Yan Li; Bowen Hui; He Li; Jian Li (Food Chemistry, 2023)

Overexpressing SIRT6 can Attenuate the Injury of Intracerebral Hemorrhage by Down-Regulating NF-kB - Jing Cheng; Yan-Qin Fan; Wen-Fei Zhang; Guo Zhang; Kuo Zeng; Zhang Ye; Dan Zhao; Li-Quan Wu; Zhi-Biao Chen (NeuroMolecular Medicine, 2023)

A chitin synthase mutation confers widespread resistance to buprofezin, a chitin synthesis inhibitor, in the brown planthopper, Nilaparvata lugens - Bin Zeng; Fu-Rong Chen; Ya-Ting Liu; Di Guo; Yi-Jie Zhang; Ze-Rui Feng; Li-Xiang Wang; John Vontas; Shun-Fan Wu; Kun Yan Zhu; Cong-Fen Gao (Journal of Pest Science, 2023)

Experimental and theoretical study on the onset of nucleate boiling in non-uniform heating tube bundle channel - Yiming Yan; Meng Wang; Guangming Fan; Xiaobo Zeng; Zongkun Li (Annals of Nuclear Energy, 2023)

Risk assessment and environmental determinants of urinary phthalate metabolites in pregnant women in Southwest China - Nian Wu; Lin Tao; Kunming Tian; Xia Wang; Caidie He; Songlin An; Yingkuan Tian; Xiang Liu; Wei Chen; Haonan Zhang; Pei Xu; Dengqing Liao; et al. (Environmental Science and Pollution Research, 2023)

The adverse impact on lifespan, immunity, and forage behavior of worker bees (Apis mellifera Linnaeus 1758) after exposure to flumethrin - Xiaobo Wu; Zhen Li; Heyan Yang; Xujiang He; Weiyu Yan; Zhijiang Zeng (Science of The Total Environment, 2023)

Volatile characteristics and fluxes of He-CO2 systematics in the southeastern Tibetan Plateau: Constraints on regional seismic activities - Yingchun Wang; Xiaocheng Zhou; Jiao Tian; Jinlin Zhou; Miao He; Jingchao Li; Jinyuan Dong; Yucong Yan; Fengli Liu; Bingyu Yao; Yuwen Wang; Zhaojun Zeng; et al. (Journal of Hydrology, 2023)

Photo-thermal catalytic pyrolysis of waste plastics: Investigation into light-induced metal-support interaction - Haiping Yang; Shuai Yan; Dingding Yao; Hao Luo; Kuo Zeng; Jun Li; Dian Zhong; Haoyu Xiao; Hanping Chen (Fuel, 2023)

A comprehensive overview of emerging techniques and chemometrics for authenticity and traceability of animal-derived food - Huiping Ye; Juan Yang; Gengsheng Xiao; Yan Zhao; Zhanming Li; Weidong Bai; Xiaofang Zeng; Hao Dong (Food Chemistry, 2023)

Joint effects of per- and polyfluoroalkyl substance alternatives and heavy metals on renal health: A community-based population study in China - Li-Xia Liang; Pengxin Dong; Yang Zhou; Lin Zhang; Zhengmin Qian; Sarah Dee Geiger; Elizabeth Bingheim; Xiaojiang Tang; Yan Wu; Jiayun Lv; Li-Zi Lin; Mohammed Zeeshan; et al. (Environmental Research, 2023)

IFI44L as a novel epigenetic silencing tumor suppressor promotes apoptosis through JAK/STAT1 pathway during lung carcinogenesis - Yong Zeng; Hong-qiang Chen; Zhe Zhang; Jun Fan; Jing-zhi Li; Shi-meng Zhou; Na Wang; Su-peng Yan; Jia Cao; Jin-yi Liu; Zi-yuan Zhou; Wen-bin Liu (Environmental Pollution, 2023)

Supramolecular peptide hydrogel doped with nanoparticles for local siRNA delivery and diabetic wound healing - Liangyan Wu; Yanbo Chen; Gang Zeng; Na Mao; Na Li; Lanlan Li; Xiaoding Xu; Li Yan (Chemical Engineering Journal, 2023)

Engineering demonstration of the remediation of urban water using a novel MES enhanced ecological floating bed: From construction to long-term performance - Ye Qiu; Yunlong Ji; Yan Tian; Henan Li; Jiannan Li; Zeng Li; Menglong Liao; Guohong Liu; Yujie Feng (Chemical Engineering Journal, 2023)

Sequential melting of deep crustal source rocks in a rift system: An example from southern Tibet - Li-E Gao; Lingsen Zeng; Linghao Zhao; Lilong Yan (Chemical Geology, 2023)

CFD simulations of the tree effect on the outdoor microclimate by coupling the canopy energy balance model - Ruibin Li; Fanxing Zeng; Yi Zhao; Yan Wu; Jianlei Niu; Liangzhu (Leon) Wang; Naiping Gao; Xing Shi (Building and Environment, 2023)

Elevated Levels of Naturally-Occurring Autoantibodies Against the Extracellular Domain of p75NTR Aggravate the Pathology of Alzheimer’s Disease - Chen-Yang He; Ding-Yuan Tian; Si-Han Chen; Wang-Sheng Jin; Yuan Cheng; Jia-Yan Xin; Wei-Wei Li; Gui-Hua Zeng; Cheng-Rong Tan; Jie-Ming Jian; Dong-Yu Fan; Jun-Rong Ren; et al. (Neuroscience Bulletin, 2023)

Evaluating the Genetic Role of Circadian Clock Genes in Parkinson’s Disease - Yaqin Xiang; JuanJuan Huang; Yige Wang; XiuRong Huang; Qian Zeng; Lizhi Li; Yuwen Zhao; Hongxu Pan; Qian Xu; Zhenhua Liu; Qiying Sun; Junling Wang; et al. (Molecular Neurobiology, 2023)

Two new cycloartane triterpenoid glycosides from the rhizomes of Actaea vaginata - Shunqin Zeng; Xiangyuan Li; Zixuan Zhao; Yan Lin; Yindi Zhu; Guoxu Ma; Xiaohong Zhao; Xudong Xu; Meichun Wu; Haifeng Wu; Qiongyu Zou; Yongtao Li (Natural Product Research, 2023)

Minor iridoid glycosides from the fruits of Cornus officinalis Sieb. et Zucc. and their anti-diabetic bioactivities - Zhi-You Hao; Xiao-Lan Wang; Meng Yang; Bing Cao; Meng-Nan Zeng; Shi-Qi Zhou; Meng Li; Yan-Gang Cao; Shuang-Shuang Xie; Xiao-Ke Zheng; Wei-Sheng Feng (Phytochemistry, 2023)

Urinary phthalate metabolites and the risk of endometrial polyp: A pilot study from the TREE cohort - Min Zhang; Chong Liu; Xiao-Qiong Yuan; Wen Yao; Qing-Yun Yao; Yong Huang; Ni-Jie Li; Yan-Ling Deng; Pan-Pan Chen; Yu Miao; Fei-Peng Cui; Yu-Feng Li; et al. (Environmental Pollution, 2023)

Molecularly understanding and regulating carrier injection behavior of ETL/perovskite towards high performance PeLEDs - Qungui Wang; Keli Wang; Cheng Yan; Xiankan Zeng; Xuehai Fu; Jingjing Cao; Shiyu Yang; Wen Li; Xiangrong Chen; Weiqing Yang (Chemical Engineering Journal, 2023)

Coupled carbon structure and iron species for multiple periodate-based oxidation reaction - Ling Xiang; Eydhah Almatrafi; Hailan Yang; Haoyang Ye; Fanzhi Qin; Huan Yi; Yukui Fu; Xiuqin Huo; Wu Xia; Hong Li; Ming Yan; Chengyun Zhou; et al. (Chemical Engineering Journal, 2023)

Reduction/pH-responsive disassemblable MOF-microbial nanohybrid for targeted tumor penetration and synergistic therapy - Xuemei Zeng; Pengjie Li; Shuangqian Yan; Bi-Feng Liu (Chemical Engineering Journal, 2023)

Near-ultraviolet emitters based on carbazole-imidazole for highly efficient solution-processed organic light-emitting diodes - Siyang Liu; Junzi Li; Huibo Yan; Fanghao Ye; Fangfang Niu; Bin Zhang; Guoping Wang; Guijun Li; Pengju Zeng (Chemical Engineering Journal, 2023)

Characterization and expression analysis of basic leucine zipper (bZIP) transcription factors responsive to chilling injury in peach fruit - Muhammad Muzammal Aslam; Li Deng; Junren Meng; Yan Wang; Lei Pan; Liang Niu; Zhenhua Lu; Guochao Cui; Wenfang Zeng; Zhiqiang Wang (Molecular Biology Reports, 2023)

Exposure–response relationship between temperature, relative humidity, and varicella: a multicity study in South China - Yihan Li; Jialing Li; Zhihua Zhu; Weilin Zeng; Qi Zhu; Zuhua Rong; Jianxiong Hu; Xing Li; Guanhao He; Jianguo Zhao; Lihua Yin; Yi Quan; et al. (Environmental Science and Pollution Research, 2023)

A new insight into the emission source of DDT in indoor environment from rural area of South China and comprehensive human health exposure assessment - Yin-Zhi Lv; Xiao-Jun Luo; Qi-Qi Li; Yan Yang; Yan-Hong Zeng; Bi-Xian Mai (Environmental Science and Pollution Research, 2022)

Effective Adsorption of Pb2+ on Porous Carbon Derived from Functional Octadecahedron ZIF-8 - Menglan Chen; Hongxia Wang; Fangxiang Song; Xian Zeng; Nian Wu; Honghuan Luo; Xiaoqin Cai; Yan Li (Water Conservation Science and Engineering, 2022)

Development and Application of Three-Dimensional Bioprinting Scaffold in the Repair of Spinal Cord Injury - Dezhi Lu; Yang Yang; Pingping Zhang; Zhenjiang Ma; Wentao Li; Yan Song; Haiyang Feng; Wenqiang Yu; Fuchao Ren; Tao Li; Hong Zeng; Jinwu Wang (Tissue Engineering and Regenerative Medicine, 2022)

Whole-genome sequencing and comparative analysis of Helicobacter pylori GZ7 strain isolated from China - Xiaoyan Zeng; Lin Xiong; Wenling Wang; Yan Zhao; Yuan Xie; Qinrong Wang; Qifang Zhang; Leilei Li; Cencen Jia; Yonghui Liao; Jianjiang Zhou (Folia Microbiologica, 2022)

Immunogenicity and protective efficacy of a DNA vaccine inducing optimal expression of the SARS-CoV-2 S gene in hACE2 mice - Zhuo-xin Li; Sheng Feng; He Zhang; Xin-yu Zhuang; Chao Shang; Shi-yu Sun; Ji-cheng Han; Yu-biao Xie; Jin-yong Zhang; Wei Wang; Cheng-hui Li; Guan-yu Zhao; et al. (Archives of Virology, 2022)

Circular RNA circCCNB1 inhibits the migration and invasion of nasopharyngeal carcinoma through binding and stabilizing TJP1 mRNA - Mengyao Zhao; Yian Wang; Fenghua Tan; Lingyun Liu; Xiangchan Hou; Chunmei Fan; Le Tang; Yongzhen Mo; Yumin Wang; Qijia Yan; Zhaojian Gong; Zheng Li; et al. (Science China Life Sciences, 2022)

Study on the Effectiveness and Mechanism of Mercapto-Modified Attapulgite for Remediation of Cadmium-Contaminated Paddy Soil - Guangxi He; Xiaping Zhu; Yan An; Yuying Chen; Cheng Fu; Ningfei Lei; Ying Zeng; Junya Li; Zepeng Wang; Ping Zhao (Water, Air, & Soil Pollution, 2022)

Integrated genetic mapping and transcriptome analysis reveal the BnaA03.IAA7 protein regulates plant architecture and gibberellin signaling in Brassica napus L. - Xiaoke Ping; Qianjun Ye; Mei Yan; Jianyan Zeng; Xingying Yan; Haitao Li; Jiana Li; Liezhao Liu (Theoretical and Applied Genetics, 2022)

Complete chloroplast genome sequence and variation analysis of Brassica oleracea L. - Yuanyuan Xu; Miaomiao Xing; Jiaqing Li; Aisong Zeng; Lixiao Song; Jiyong Yan (Acta Physiologiae Plantarum, 2022)

Genetically predicted tobacco consumption and risk of intracranial aneurysm: a Mendelian randomization study - Chudai Zeng; Zheng Huang; Wengui Tao; Langchao Yan; Dong Tang; Fenghua Chen; Shifu Li (Environmental Science and Pollution Research, 2022)

α-Enolase inhibits apoptosis and promotes cell invasion and proliferation of skin cutaneous melanoma - Kun Zhang; Ruoxi Tian; Wancong Zhang; Yishuai Li; Ning Zeng; Yan Liang; Shijie Tang (Molecular Biology Reports, 2022)
Background The glycolytic enzyme, α-Enolase (ENO1), catalyzes the production of phosphoenolpyruvate from 2-phosphoglycerate, thereby enhancing glycolysis and contributing to tumor progression. In the present study, we aimed to determine the role of ENO1 in skin cutaneous melanoma (SKCM) and the potential underlying mechanism. Methods The Sangerbox database was used to analyze the mRNA expression of ENO1 in SKCM. Western blotting was used to assess the levels of ENO1, c-Myc, β-catenin, MMP-9, PGAM1, and MMP-13 in SKCM-derived cell lines or tumor tissues from patients with SKCM. The pCMV-SPORT6-ENO1 and pET-28a-ENO1siRNA plasmids were used to overexpress and knockdown ENO1 in SKCM cells, respectively. To determine the function of ENO1 in the malignant behavior of SKCM cells, we performed a wound-healing assay, cell counting kit 8 assay, and transwell chamber analyses. The production of pyruvate and lactic acid in tumor cells was evaluated using their respective kits. Results Compared with non-tumor tissues, ENO1 was found to be overexpressed in SKCM tissues. In SKCM cells, ENO1 overexpression promoted invasion, migration, and proliferation of tumor cells; increased pyruvate and lactate production; and increased β-catenin, MMP-9, MMP-13, and c-Myc levels. The opposite effects were observed in SKCM cells silenced for ENO1. Conclusions These results indicate that ENO1 is involved in SKCM progression by enhancing the invasion and proliferation of tumor cells. In addition, ENO1 might have an important function in tumor cell glycolysis. Therefore, ENO1 represents a potential therapeutic target for treatment of SKCM.

Genetic Analysis of HSP40/DNAJ Family Genes in Parkinson’s Disease: a Large Case-Control Study - Kailin Zhang; Hongxu Pan; Yuwen Zhao; Yige Wang; Qian Zeng; Xun Zhou; Runcheng He; Xiaoxia Zhou; Yaqin Xiang; Zhou Zhou; Yu Li; Qian Xu; et al. (Molecular Neurobiology, 2022)

Correction to: Inhibition of Dectin-1 Ameliorates Neuroinflammation by Regulating Microglia/Macrophage Phenotype After Intracerebral Hemorrhage in Mice - Xiongjie Fu; Hanhai Zeng; Jikuang Zhao; Guoyang Zhou; Hang Zhou; Jianfeng Zhuang; Chaoran Xu; Jianru Li; Yucong Peng; Yang Cao; Yin Li; Huaijun Chen; et al. (Translational Stroke Research, 2022)

Population-Average Brain Templates and Application to Automated Voxel-Wise Analysis Pipelines for Cynomolgus Macaque - Fubing Ouyang; Xinran Chen; Jiahui Liang; Jianle Li; Zimu Jiang; Yicong Chen; Zhicong Yan; Jinsheng Zeng; Shihui Xing (Neuroinformatics, 2022)

The involvement of a floral scent in plant-honeybee interaction - Yi Bo Liu; Zhi Jiang Zeng; Andrew B. Barron; Ye Ma; Yu Zhu He; Jun Feng Liu; Zhen Li; Wei Yu Yan; Xu Jiang He (The Science of Nature, 2022)

Probiotic Potential of Bacillus licheniformis and Bacillus pumilus Isolated from Tibetan Yaks, China - Zhibo Zeng; Jiabin Zhang; Yan Li; Kewei Li; Saisai Gong; Feiran Li; Pengpeng Wang; Mudassar Iqbal; Muhammad Fakhar-e-Alam Kulyar; Jiakui Li (Probiotics and Antimicrobial Proteins, 2022)

Mitigation of microbial corrosion by Cu addition to X65 pipeline steel by Pseudomonas aeruginosa MCCC 1A00099 - Yuchen Li; Xianbo Shi; Jiguang Li; Yunpeng Zeng; Minggang Shen; Wei Yan; Ke Yang (Archives of Microbiology, 2022)

Isolation, Identification and Characteristics of Aeromonas caviae from Diseased Largemouth Bass (Micropterus salmoides) - Mingyang Xue; Zidong Xiao; Yiqun Li; Nan Jiang; Wenzhi Liu; Yan Meng; Yuding Fan; Lingbing Zeng; Yong Zhou (Fishes, 2022)
The largemouth bass (Micropterus salmoides) is one of the most economically valuable fish species in China. In this study, a bacterial pathogen was isolated from the internal organs of diseased M. salmoides, and the strain was named WH21406. This isolate was identified as Aeromonas caviae on the basis of its morphology, biochemical features and 16S rDNA phylogenetic analysis. Four virulence genes related to pathogenicity, namely, flagella (fla), elastase (ela), haemolysin (hly) and aerolysin (aer), were detected in this isolate. The median lethal dosage (LD50) of A. caviae WH21406 for M. salmoides was calculated to be 3.46 × 105 CFU mL−1. The histopathological analysis showed obvious tissue damage in the gill, liver, kidney, spleen and gut of the diseased fish. The antibiotic susceptibility test demonstrated that strain WH21406 was highly sensitive to enrofloxacin, norfloxacin, streptomycin and amikacin. The results of this study provide a foundation for the diagnosis, prevention and treatment of A. caviae infection in M. salmoides.

Development and characterization of 123 SNPs in an endangered fish Semilabeo obscurus - Shikai Li; Wei Wang; Mingju Yang; Fujiang Huang; Xue Wang; Sheng Zeng; Yan Xiang; Lu Zhou (Conservation Genetics Resources, 2022)

PdeHCA2 affects biomass in Populus by regulating plant architecture, the transition from primary to secondary growth, and photosynthesis - Biligen-Gaowa Zhao; Guo Li; Yue-Feng Wang; Zhen Yan; Feng-Qin Dong; Ying-Chang Mei; Wei Zeng; Meng-Zhu Lu; Hong-Bin Li; Qing Chao; Bai-Chen Wang (Planta, 2022)

Application of blockchain technology in food safety control：current trends and future prospects - Yan Xu; Xiangxin Li; Xiangquan Zeng; Jiankang Cao; Weibo Jiang (Critical Reviews in Food Science and Nutrition, 2022)

Microtubules play a crucial role in regulating actin organization and cell initiation in cotton fibers - Jianyan Zeng; Jing Xi; Baoxia Li; Xingying Yan; Yonglu Dai; Yiping Wu; Yuehua Xiao; Yan Pei; Mi Zhang (Plant Cell Reports, 2022)

Functional characterization of tyrosine decarboxylase genes that contribute to acteoside biosynthesis in Rehmannia glutinosa - Yan Hui Yang; Mu Rong Yang; Jian Yu Zhu; Ke Wei Dong; Yan Jie Yi; Rui Fang Li; Lei Zeng; Chang Fu Zhang (Planta, 2022)

Impacts of Nitrogen Fertilizer Substitution on Greenhouse Gas Emission in a Paddy Field of South China Under Ridge Irrigation - Yan Zeng; Fusheng Li (Journal of Soil Science and Plant Nutrition, 2022)

Neutrophil Extracellular Traps may be a Potential Target for Treating Early Brain Injury in Subarachnoid Hemorrhage - Hanhai Zeng; Xiongjie Fu; Jing Cai; Chenjun Sun; Mengyan Yu; Yucong Peng; Jianfeng Zhuang; Jingyin Chen; Huaijun Chen; Qian Yu; Chaoran Xu; Hang Zhou; et al. (Translational Stroke Research, 2022)

Evolution of research topics on the Tibetan Plateau environment and ecology from 2000 to 2020: a paper mining - Keke Chang; Junyu Tao; Cheng Fang; Jian Li; Wenwu Zhou; Xutong Wang; Beibei Yan; Dan Zeng; Guanyi Chen (Environmental Science and Pollution Research, 2022)

Association Between Low-Level Blood Cadmium Exposure and Hyperuricemia in the American General Population: a Cross-sectional Study - Aihui Zeng; Sai Li; Yan Zhou; Datong Sun (Biological Trace Element Research, 2022)

Susceptibility of a cell line derived from the kidney of Chinese rice‐field eel, Monopterus albus to the infection of rhabdovirus, CrERV - Wenzhi Liu; Yuding Fan; Yong Zhou; Nan Jiang; Yiqun Li; Yan Meng; Mingyang Xue; Zhong Li; Lingbing Zeng (Journal of Fish Diseases, 2022)
Chinese rice‐field eels rhabdovirus (CrERV), belonging to the genus Perhabdovirus in the family Rhabdoviridae , is the causative agent of the haemorrhagic disease of Chinese rice‐field eels, Monopterus albus . The present study aims to establish a cell line derived from the kidney of Chinese rice‐field eel (CrEK) for the further study of the pathogenic virus. CrEK cells were epithelioid‐like and grew well in M199 medium supplemented with 10% foetal bovine serum at 28°C, and the cell line has been subcultured for more than 80 times. Karyotyping analysis of CrEK cells at 25th passage indicated a modal chromosome number of 24. Significant cytopathic effect (CPE) was observed in CrEK cells after infection with CrERV, and the virus titre reached 10 7.8 ± 0.45 TCID 50 /mL. The transmission electron microscopy revealed that there were a large number of virus particles in the cytoplasm of cells. The virus infection in cells was also assayed by using indirect immunofluorescence assay (IFA), fluorescence in situ hybridization (FISH), reverse transcription PCR (RT‐PCR) and quantitative real‐time reverse transcription‐PCR (qRT‐PCR). In experimental infection, CrERV cultured by cells could cause over 90% mortality in fish. CrEK represents the first kidney cell line originated from Chinese rice‐field eels and be a potential material for investigating the mechanism of virus infection in this fish and the control methods for the disease.

Effects of Dietary Enterococcus faecalis YFI-G720 on the Growth, Immunity, Serum Biochemical, Intestinal Morphology, Intestinal Microbiota, and Disease Resistance of Crucian Carp (Carassius auratus) - Yan Xu; Yiqun Li; Mingyang Xue; Zidong Xiao; Yuding Fan; Lingbing Zeng; Yong Zhou (Fishes, 2022)
Diseases of crucian carp (Carassius auratus) are closely related to intestinal parameters. Enterococcus faecalis has strong colonization ability in the intestinal tract, and produces natural antibiotics, bacteriocin, and other bacteriostatic substances, which can effectively inhibit some pathogenic bacteria and improve the intestinal microenvironment. This study aimed to assess the effects of E. faecalis YFI-G720 which was isolated from the intestinal of crucian carp on the growth, immunity, intestinal health, and disease resistance of crucian carp. Fish (48.16 ± 0.55 g) were fed four diets, commercial diet or diet containing E. faecalis at 105 CFU/g (EF1), 106 CFU/g (EF2), or 107 CFU/g (EF3) for 28 days. The results showed that supplementation of E. faecalis significantly improved the weight gain ratio (WGR) and the specific growth rate (SGR) compared with control group (p

Retraction Note to: Revisiting the male genetic landscape of China: a multi-center study of almost 38,000 Y-STR haplotypes - Michael Nothnagel; Guangyao Fan; Fei Guo; Yongfeng He; Yiping Hou; Shengping Hu; Jiang Huang; Xianhua Jiang; Wook Kim; Kicheol Kim; Chengtao Li; Hui Li; et al. (Human Genetics, 2022)

Maternal intake of caffeinated products and birth defects: a systematic review and meta-analysis of observational studies - Yan Yue; Wenxing Li; Jun Tang; Yan Zeng; Tao Xiong; Xia Qiu; Jing Shi; Hua Wang; Bin Xia; Lili Luo; Yi Qu; Dezhi Mu (Critical Reviews in Food Science and Nutrition, 2021)

Investigation of factors influencing the release of chloropropanols (3-MCPD and 1,3-DCP) from food contact paper - Huai-ning Zhong; Ying Zeng; Dao-yuan Yang; Ze-chun Wu; Dan Li; Hai-xia Sui; Jie Gao; Yan-fen Chen; Ce-Hui Mo (Food Additives & Contaminants: Part A, 2021)

Genomic Analysis of the Principal Members of Antioxidant Enzymes in Simulated Stresses Response and Postharvest Physiological Deterioration in Cassava - Sang Shang; Yuqi Tang; Jing Dai; Chunlai Wu; Yan Yan; Weiwei Tie; Meiying Li; Jinghao Yang; Jian Zeng; Mingjie Chen; Wei Hu (Tropical Plant Biology, 2021)

Inhibition of Dectin-1 Ameliorates Neuroinflammation by Regulating Microglia/Macrophage Phenotype After Intracerebral Hemorrhage in Mice - Xiongjie Fu; Hanhai Zeng; Jikuang Zhao; Guoyang Zhou; Hang Zhou; Jianfeng Zhuang; Chaoran Xu; Jianru Li; Yucong Peng; Yang Cao; Yin Li; Huaijun Chen; et al. (Translational Stroke Research, 2021)

Economic Evaluation of Water-Saving Irrigation Practices for Sustainable Sugarcane Production in Guangxi Province, China - Shan-Shan He; Yuan Zeng; Zhao-Xu Liang; Yan Jing; ShiYun Tang; Baoqing Zhang; Haifeng Yan; Song Li; Tinglin Xie; Fang Tan; Ming Li (Sugar Tech, 2021)

Fine mapping and validation of a major QTL for grain weight on chromosome 5B in bread wheat - Dehui Zhao; Li Yang; Dan Liu; Jianqi Zeng; Shuanghe Cao; Xianchun Xia; Jun Yan; Xiyue Song; Zhonghu He; Yong Zhang (Theoretical and Applied Genetics, 2021)

In vitro and in vitro toxicity study of diesel exhaust particles using BEAS-2B cell line and the nematode Caenorhabditis elegans as biological models - Chenzhi Yan; Xuan Wu; Xue Cao; Meng Li; Lei Zhou; Guangli Xiu; Jiayi Zeng (Environmental Science and Pollution Research, 2021)

Melatonin antagonizes ozone-exacerbated asthma by inhibiting the TRPV1 channel and stabilizing the Nrf2 pathway - Yushan Chen; Xiaoyu Wu; Xu Yang; Xudong Liu; Yan Zeng; Jinquan Li (Environmental Science and Pollution Research, 2021)

Directional arrangement of phyllite fragments in phyllite talus slope at the eastern margin of the Tibetan Plateau - Yu-hao Wan; Xiao-yan Zhao; Si-xiang Ling; Jin Li; Cai-yun Zeng; Wünnemann Bernd (Journal of Mountain Science, 2021)

Pharmacological Activation of RXR-α Promotes Hematoma Absorption via a PPAR-γ-dependent Pathway After Intracerebral Hemorrhage - Chaoran Xu; Huaijun Chen; Shengjun Zhou; Chenjun Sun; Xiaolong Xia; Yucong Peng; Jianfeng Zhuang; Xiongjie Fu; Hanhai Zeng; Hang Zhou; Yang Cao; Qian Yu; et al. (Neuroscience Bulletin, 2021)

Influence of sedimentation rate on the environmental capacity of total nitrogen in the water of Bohai Bay, China - Yan Zhang; Anding Li; Ye Tian; Bin Zhou; Man Chai; Hui Li; Qiongqiong Liu; Hui Zeng; Weijie Xu (Journal of Soils and Sediments, 2021)

Two new norsesquiterpenoids with estrogenic activity from the stems and leaves of Dioscorea oppositifolia L - Ying-Jie Ren; Yan-Gang Cao; Meng-Nan Zeng; Bei-Bei Zhang; Yan-Ling Liu; Meng-Na Wang; Yan-Li Zhang; Wei-Sheng Feng; Xiao-Ke Zheng (Natural Product Research, 2021)

Biomarkers of fatty acids and risk of type 2 diabetes: a systematic review and meta-analysis of prospective cohort studies - Gengdong Chen; Yan Li; Fangfang Zeng; Guifang Deng; Jingjing Liang; Jue Wang; Yixiang Su; Yuming Chen; Limei Mao; Zhengping Liu; Wei Bao; Zheqing Zhang (Critical Reviews in Food Science and Nutrition, 2021)

Design of overburden thickness for underground arsenals based on numerical simulation of underground explosion caves - Xingui Zhang; Jiaxiong Zhu; Li’e Yan; Yi Zeng; Qingsheng Chen; Mangyuan Li (Arabian Journal of Geosciences, 2021)

Wogonin Accelerates Hematoma Clearance and Improves Neurological Outcome via the PPAR-γ Pathway After Intracerebral Hemorrhage - Jianfeng Zhuang; Yucong Peng; Chi Gu; Huihui Chen; Zheng Lin; Hang Zhou; Xiao Wu; Jianru Li; Xiaobo Yu; Yang Cao; Hanhai Zeng; Xiongjie Fu; et al. (Translational Stroke Research, 2021)

Restricted Feeding Resets Endogenous Circadian Rhythm in Female Mice Under Constant Darkness - Yue Mei; Huajing Teng; Zhigang Li; Cheng Zeng; Yuanyuan Li; Wei Song; Kaifan Zhang; Zhong Sheng Sun; Yan Wang (Neuroscience Bulletin, 2021)

Antifungal Effect of Long Noncoding RNA 9708-1 in the Vulvovaginal Candidiasis Murine Model - Ying Wu; Lisha Jiang; Lingling Zhang; Xia Liu; Lina Yan; Ting Luan; Can Rui; Zhiyuan Mao; Chong Fan; Yu Liu; Ping Li; Xin Zeng (Mycopathologia, 2021)
Vulvovaginal candidiasis (VVC) caused by Candida spp. affects 70–75% of women at least once during their lives. We aim to elucidate the potential mechanism of VVC and investigate the therapeutic effects of long noncoding RNA 9708-1. Female BALB/c mice were randomized to four treatment groups, including the blank control group, VVC control group, vehicle control group and lncRNA 9708-1-overexpressed group. Mice were euthanized on Day 4, Day 7 and Day 14 after treatment. Colony-forming unit (CFU) was measured, and the inflammation was detected by hematoxylin and eosin (H&E). Gene and protein expression levels of lncRNA 9708-1 and FAK were determined by real-time PCR, Western blot and immunohistochemistry. The overexpression of lncRNA 9708-1 significantly decreased the fungal load from Day 4 to 7. H&E staining indicated that the impaired histological profiles were improved in lncRNA 9708-1-overexpressed group. LncRNA 9708-1 led to a significant increase in FAK level of vagina tissue which is expressed mainly in epithelial basal layer. This study suggests that lncRNA 9708-1 played a protective role on murine experimental VVC by upregulating the expression levels of FAK.

Clinical and microbiological characteristics of adults with hospital-acquired pneumonia: a 10-year prospective observational study in China - Yuyao Yin; Chunjiang Zhao; Henan Li; Longyang Jin; Qi Wang; Ruobing Wang; Yawei Zhang; Jiangang Zhang; Hui Wang; Chunxia Yang; Bin Cao; Yingmei Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Subseasonal prediction and predictability of summer rainfall over eastern China in BCC_AGCM2.2 - Yunyun Liu; Zeng-Zhen Hu; Renguang Wu; Bhaskar Jha; Qiaoping Li; Lijuan Chen; Jinghui Yan (Climate Dynamics, 2021)

Development of a real‐time recombinase polymerase amplification assay for rapid detection of Aeromonas hydrophila - Yang Qu; Qing Wang; Yingying Li; Yingying Wang; Jiyuan Yin; Yan Ren; Chun Liu; Xiaofang Liu; Yahui Wang; Weiwei Zeng (Journal of Fish Diseases, 2021)
Aeromonas hydrophila is ubiquitous in the aquaculture industry and a constant cause of severe disease and economic losses. The early diagnosis of these infections is crucial for disease surveillance and prevention. We developed a real‐time recombinase polymerase amplification (real‐time RPA) assay for detection of A. hydrophila using the haemolysin gene. The assay was performed at 37°C for 20 min and was highly specific with no cross‐reaction with other fish pathogens or with other Aeromonas species. The assay detection limit was 10 2 copies of the Aeromonas hydrophila per reaction. Compared with traditional culture‐based method or real‐time PCR, the diagnostic sensitivity and specificity of the real‐time RPA were 73.7 and 100%, as well as 64.7 and 93%. Our newly developed real‐time RPA was specific and sensitive and can be used in large‐scale and point‐of‐care field investigations of A. hydrophila infections to enable earlier diagnoses.

Validation of suitable reference genes for qRT-PCR in cabbage (Brassica oleracea L.) under different abiotic stress experimental conditions - Aisong Zeng; Yuanyuan Xu; Lixiao Song; Jiaqing Li; Jiyong Yan (Journal of Plant Biochemistry and Biotechnology, 2021)

Effects of Chronic Stress on the Fecal Microbiome of Malayan Pangolins (Manis javanica) Rescued from the Illegal Wildlife Trade - Dingyu Yan; Defu Hu; Kaixiang Li; Baocai Li; Xiangyan Zeng; Jinyan Chen; Yimeng Li; Torsten Wronski (Current Microbiology, 2021)

A Rehmannia glutinosa cinnamate 4-hydroxylase promotes phenolic accumulation and enhances tolerance to oxidative stress - Yan Hui Yang; Heng Yang; Rui Fang Li; Cui Xiang Li; Lei Zeng; Chao Jie Wang; Na Li; Zhuang Luo (Plant Cell Reports, 2021)

Identification and expression of the BAHD family during development, ripening, and stress response in banana - Yun Xu; Weiwei Tie; Yan Yan; Biyu Xu; Juhua Liu; Meiying Li; Jinghao Yang; Jian Zeng; Wei Hu; Zhiqiang Jin (Molecular Biology Reports, 2021)

Dominant factor of dry‐wet change in China since 1960s - Jinqin Xu; Dandan Wang; Xinfa Qiu; Yan Zeng; Xiaochen Zhu; Mengxi Li; Yongjian He; Guoping Shi (International Journal of Climatology, 2021)
The dry‐wet climate conditions of an area are mainly determined by the water input (e.g., precipitation, P) and output (e.g., potential evapotranspiration, PET). Based on three dry‐wet indices and the differential equation, this study designed a new attribution method to quantify the contributions of P and PET to the dry‐wet change, so as to determine the dominant factors of the dry‐wet change over whole China (CHINA) and various hydroclimate regions (i.e., arid region, AR; semi‐arid region, SAR; semi‐humid region, SHR; and humid region, HR) during 1960–2018 and six interdecadal periods. Results showed that the overall weak drying in CHINA was dominated by an increase in PET, while climate humidification in AR and HR was dominated by an increase in P, climate drying in SHR was dominated by the reduced P, and the weak drying in SAR was co‐dominated by P and PET during 1960–2018. The dominant factors of dry‐wet change over CHINA and each hydroclimate region varied in different decades. Briefly, climate humidification in CHINA and various hydroclimate regions was basically dominated by P in different decades, and the drying was mainly dominated by P in the 1960s–1980s, but the contribution of PET to climate drying began to become prominent after the 1980s. Besides, we found that P contributed more to dry‐wet change than PET on the station and regional scales, but the contribution of P to climate drying on a national scale was underestimated to some extent due to the regional offset effect of the increase/decrease in P during 1960–2018, as well as in the 1990s. These findings implied that the importance of research on the regional or local scale, and equal attention should be paid to the effects of P and PET changes in the future drought or dry‐wet change research.

The relationships of serum homocysteine levels and traditional lipid indicators with disease activity and coronary artery involvement in Takayasu arteritis - Si Chen; Haixia Luan; Jianxun He; Yan Wang; Xiaoli Zeng; Yongzhe Li; Hui Yuan (Immunologic Research, 2020)

Association of in-hospital intensive statins dosage and death in arteriosclerotic cardiovascular disease with percutaneous coronary intervention: insights of multicentre cohort from China - Peng-yuan Chen; Yuan-hui Liu; Chong-yang Duan; Hua-lin Fan; Li-huan Zeng; Wei Guo; Lei Jiang; Xue-biao Wei; Wen-fei He; Sha Tao; Zhi-qiang Guo; Ji-yan Chen; et al. (European Journal of Clinical Pharmacology, 2020)

Rho GTPases in cancer radiotherapy and metastasis - Rui-Jie Zeng; Chun-Wen Zheng; Wan-Xian Chen; Li-Yan Xu; En-Min Li (Cancer and Metastasis Reviews, 2020)

SNP of AHSA2 gene in three cattle breeds using snapshot technology - Shu-Zhu Cheng; E. Guang-Xin; Cheng-Li Liu; Wang-Dui Basang; Yan-Bin Zhu; Ri-Su Na; Yan-Guo Han; Yan Zeng; Xiao Wang; Wei-Wei Ni; Bai-Gao Yang; Xing-Hai Duan; et al. (Journal of Genetics, 2020)

Fasudil attenuates glial cell-mediated neuroinflammation via ERK1/2 and AKT signaling pathways after optic nerve crush - Wei Huang; Qianqian Lan; Li Jiang; Wenya Yan; Fen Tang; Chaolan Shen; Hui Huang; Haibin Zhong; Jian Lv; Siming Zeng; Min Li; Zhongxiang Mo; et al. (Molecular Biology Reports, 2020)

New cadinane sesquiterpenoids from Mikania micrantha - Yao Zhang; You-Mei Zeng; You-Kai Xu; Shu-Qi Wu; Shen Li; Hai-Yan Tian; Sheng Yin (Natural Product Research, 2020)

Verticillin A inhibits colon cancer cell migration and invasion by targeting c-Met - Qian-qian Liu; Xue-li Zeng; Yue-lin Guan; Jing-xin Lu; Kai Tu; Fei-yan Liu (Journal of Zhejiang University-SCIENCE B, 2020)

The anti-inflammatory drug dimethyl itaconate protects against colitis-associated colorectal cancer - Qian Wang; Xin Ling Li; Yan Mei; Jia-Chong Ye; Wei Fan; Guang-Hui Cheng; Mu-Sheng Zeng; Guo-Kai Feng (Journal of Molecular Medicine, 2020)

Variation in Gut Microbiota of Captive Bengal Slow Lorises - Qingyong Ni; Xin He; Bo Zeng; Xiangyun Meng; Huailiang Xu; Ying Li; Mingyao Yang; Diyan Li; Yongfang Yao; Mingwang Zhang; Yan Li; Xiaolan Fan; et al. (Current Microbiology, 2020)

Chemical characterization of constituents from Polygonatum cyrtonema Hua and their cytotoxic and antioxidant evaluation - Ting Zeng; Yan-Ran Tang; Bin Li; Shumaila Tasneem; Han-Wen Yuan; Yan-Zhe Jia; Muhammad Daniyal; Nusrat Hussain; Wen-Miao Wang; Da-Lei Zuo; Li-Min Gong; Bin Liu; et al. (Natural Product Research, 2020)

Fumonisin B1 Affects the Biophysical Properties, Migration and Cytoskeletal Structure of Human Umbilical Vein Endothelial Cells - Xue Zhao; Yun Wang; Jiang-Li Liu; Jian-Hua Zhang; Shi-Chao Zhang; Yan Ouyang; Jiang-Tao Huang; Xiao-Yan Peng; Zhu Zeng; Zu-Quan Hu (Cell Biochemistry and Biophysics, 2020)

Transcriptome Analysis of Two Strains of Proteus mirabilis with Swarming Migration Deficiency Isolated from Patients with Urinary Tract Infection - Liang Peng; Ding-Qiang Chen; Guan-Ming Jiang; Jing-Yi Ou; Qiao Jiang; Li-Ting Zeng; Yi Xiao; Qiong-Yan Jiang; Ling Yang; Ning Sun (Current Microbiology, 2020)

Association of Polygenic Risk Score with Age at Onset and Cerebrospinal Fluid Biomarkers of Alzheimer’s Disease in a Chinese Cohort - Wei-Wei Li; Zhen Wang; Dong-Yu Fan; Ying-Ying Shen; Dong-Wan Chen; Hui-Yun Li; Ling Li; Heng Yang; Yu-Hui Liu; Xian-Le Bu; Wang-Sheng Jin; Fan Zeng; et al. (Neuroscience Bulletin, 2020)

New insight into the molecular phylogeny of the genus Liparis s.l. (Orchidaceae: Malaxideae) with a new generic segregate: Blepharoglossum - Lin Li; Shih-Wen Chung; Bo Li; Song-Jun Zeng; Hai-Fei Yan; Shi-Jin Li (Plant Systematics and Evolution, 2020)
Molecular studies have shown that Liparis s.l. is polyphyletic, with the epiphytic Liparis alliance well separated from the clade representing Liparis in its restricted sense and further forming a phylogenetically heterogeneous assemblage. The generic status of Cestichis , as the key member of the epiphytic Liparis alliance, remains contentious, and the relationships between Cestichis , Stichorkis and Platystyliparis are still unclear and in need of further studies. We herein employ DNA sequence data from nuclear ITS and plastid mat K regions to clarify the generic boundaries of Cestichis and its relationship to the allied genera. Results from both Bayesian inference and maximum likelihood analysis congruently indicate that Cestichis as currently circumscribed is not monophyletic. The Blepharoglossum clade, corresponding to commonly recognized sect. Blepharoglossum , forms a monophyletic lineage closely related to the genus Oberonia instead of the core Cestichis clade. A re-evaluation of the diagnostic morphological characters reveals that this lineage represents a morphologically distinct group. Based on these results, Blepharoglossum is removed from Cestichis and elevated to generic status. Our study also sheds light on the homoplastic nature of some diagnostic morphological characters used traditionally in the taxonomy of the Malaxidinae.

The Role of 17β-Estrogen in Candida albicans Adhesion on Human Vaginal Epithelial Cells via FAK Phosphorylation - Ting Luan; Xia Liu; Pengyuan Mao; Xinyan Wang; Can Rui; Lina Yan; Yiquan Wang; Chong Fan; Ping Li; Xin Zeng (Mycopathologia, 2020)

Biocontrol potential of Bacillus subtilis IBFCBF-4 against Fusarium wilt of watermelon - Jiuxiang Zhu; Taimeng Tan; Airong Shen; Xiebin Yang; Yongting Yu; Chunsheng Gao; Zhimin Li; Yi Cheng; Jia Chen; Litao Guo; Xiangping Sun; Zhun Yan; et al. (Journal of Plant Pathology, 2020)

The Potential Role of PKA/CREB Signaling Pathway Concerned with Gastrodin Administration on Methamphetamine-Induced Conditioned Place Preference Rats and SH-SY5Y Cell Line - Gen-Meng Yang; Lu Li; Feng-Lin Xue; Chen-Li Ma; Xiao-Feng Zeng; Yong-Na Zhao; Dong-Xian Zhang; Yang Yu; Qian-Wen Yan; Yi-Qing Zhou; Shi-Jun Hong; Li-Hua Li (Neurotoxicity Research, 2020)

Phytoextraction of cobalt (Co)-contaminated soils by sweet alyssum (Lobularia maritima (L.) Desv.) is enhanced by biodegradable chelating agents - Li Chen; Chao Zeng; Dan Wang; Jin-yan Yang (Journal of Soils and Sediments, 2020)

Potent antitumor activity of oncolytic adenovirus expressing C/EBPβ against hepatocellular carcinoma - Yan Zeng; Feng-di Li; Jiang-long Du; Yu-jia Xue; Jing Liu; Xin Cao; Hai-zhen Wang (Apoptosis, 2020)

Developmental basis for flower sex determination and effects of cytokinin on sex determination in Plukenetia volubilis (Euphorbiaceae) - Yan Luo; Bang-Zhen Pan; Lu Li; Chen-Xuan Yang; Zeng-Fu Xu (Plant Reproduction, 2020)
Key message Cytokinin might be an important factor to regulate floral sex at the very early stage of flower development in sacha inchi. Abstract Sacha inchi ( Plukenetia volubilis , Euphorbiaceae) is characterized by having female and male flowers in a thyrse with particular differences. The mechanisms involved in the development of unisexual flowers are very poorly understood. In this study, the inflorescence and flower development of P. volubilis were investigated using light microscopy and scanning electron microscopy. We also investigated the effects of cytokinin on flower sex determination by exogenous application of 6-benzyladenine (BA) in P. volubilis . The floral development of P. volubilis was divided into eight stages, and the first morphological divergence between the male and female flowers was found to occur at stage 3. Both female and male flowers can be structurally distinguished by differences in the shape and size of the flower apex after sepal primordia initiation. There are no traces of gynoecia in male flowers or of androecia in female flowers. Exogenous application of BA effectively induced gynoecium primordia initiation and female flower development, especially at the early flower developmental stages. We propose that flower sex is determined earlier and probably occurs before flower initiation, either prior to or at inflorescence development due to the difference in the position of the female and male primordia in the inflorescence and in the time of the female and male primordia being initiated. The influence of cytokinin on female primordia during flower development in P. volubilis strongly suggests a feminization role for cytokinin in sex determination. These results indicate that cytokinin could modify the fate of the apical meristem of male flower and promote the formation of carpel primordia in P. volubilis.

Permeability dynamic variation of coal under various confining pressures using LFNMR relaxation method - Peng Xia; Fangui Zeng; Xiaoxia Song; Beilei Sun; Taotao Yan; Wei Li; Yanjun Meng (Arabian Journal of Geosciences, 2020)

Co-expression Network of mRNAs and lncRNAs Regulated by Stress-Linked Behavioral Assays - Jianghong Zhang; Meiying Xue; Yue Mei; Zhigang Li; Zeng Ceng; Yuanyuan Li; Yi Zhang; Na Li; Huajing Teng; Zhong Sheng Sun; Yan Wang (Psychopharmacology, 2020)

Correction to: NaCl-induced stress: physiological responses of six halophyte species in in vitro and in vivo culture - Yuping Xiong; Hanzhi Liang; Haifeng Yan; Beiyi Guo; Meiyun Niu; Shuangyan Chen; Shuguang Jian; Hai Ren; Xinhua Zhang; Yuan Li; Songjun Zeng; Kunlin Wu; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

The expression and role of PIDD in retina after optic nerve crush - Fen Tang; Fan Xu; Ling Cui; Wei Huang; Li Jiang; Lifei Chen; Wenya Yan; Wenjing He; Chaolan Shen; Hui Huang; Jian Lv; Xin Zhao; et al. (Journal of Molecular Histology, 2020)

cDNA-AFLP analysis of differentially expressed genes during microspore embryogenesis in non-heading Chinese cabbage - Ya Zhang; Su-yan Gao; Huan-huan Liu; Xi-lin Zhang; Ai-song Zeng; Jian-jun Wang; Xi-lin Hou; Ying Li (In Vitro Cellular & Developmental Biology - Plant, 2020)

Development and Characterization of PCL Electrospun Membrane-Coated Bletilla striata Polysaccharide-Based Gastroretentive Drug Delivery System - Zhouying Li; Rui Zeng; Ling Yang; Xiaodong Ren; Katherine G. Maffucci; Yan Qu (AAPS PharmSciTech, 2020)

Marker-free lines of phytase-transgenic Brassica napus show enhanced ability to utilize phytate - Li Xu; Lingyi Zeng; Li Ren; Wang Chen; Fan Liu; Huan Yang; Ruibing Yan; Kunrong Chen; Xiaoping Fang (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Cytological, genetic, and proteomic analysis of a sesame (Sesamum indicum L.) mutant Siyl-1 with yellow–green leaf color - Tong-Mei Gao; Shuang-Ling Wei; Jing Chen; Yin Wu; Feng Li; Li-Bin Wei; Chun Li; Yan-Juan Zeng; Yuan Tian; Dong-Yong Wang; Hai-Yang Zhang (Genes & Genomics, 2020)
Background Both photosynthetic pigments and chloroplasts in plant leaf cells play an important role in deciding on the photosynthetic capacity and efficiency in plants. Systematical investigating the regulatory mechanism of chloroplast development and chlorophyll (Chl) content variation is necessary for clarifying the photosynthesis mechanism for crops. Objective This study aims to explore the critical regulatory mechanism of leaf color mutation in a yellow–green leaf sesame mutant Siyl - 1 . Methods We performed the genetic analysis of the yellow-green leaf color mutation using the F 2 population of the mutant Siyl - 1 . We compared the morphological structure of the chloroplasts, chlorophyll content of the three genotypes of the mutant F 2 progeny. We performed the two-dimensional gel electrophoresis (2-DE) and compared the protein expression variation between the mutant progeny and the wild type. Results Genetic analysis indicated that there were 3 phenotypes of the F 2 population of the mutant Siyl - 1 , i.e., YY type with light-yellow leaf color (lethal); Yy type with yellow-green leaf color, and yy type with normal green leaf color. The yellow-green mutation was controlled by an incompletely dominant nuclear gene, Siyl - 1 . Compared with the wild genotype, the chloroplast number and the morphological structure in YY and Yy mutant lines varied evidently. The chlorophyll content also significantly decreased ( P < 0.05 ). The 2-DE comparison showed that there were 98 differentially expressed proteins (DEPs) among YY, Yy, and yy lines. All the 98 DEPs were classified into 5 functional groups. Of which 82.7% DEPs proteins belonged to the photosynthesis and energy metabolism group. Conclusion The results revealed the genetic character of yellow-green leaf color mutant Siyl - 1 . 98 DEPs were found in YY and Yy mutant compared with the wild genotype. The regulation pathway related with the yellow leaf trait mutation in sesame was analyzed for the first time. The findings supplied the basic theoretical and gene basis for leaf color and chloroplast development mechanism in sesame.

Deltamethrin Impairs Honeybees (Apis mellifera) Dancing Communication - Zu Yun Zhang; Zhen Li; Qiang Huang; Xue Wen Zhang; Li Ke; Wei Yu Yan; Li Zhen Zhang; Zhi Jiang Zeng (Archives of Environmental Contamination and Toxicology, 2020)

A new Doppler centroid estimation method for high-squint curved-trajectory airborne synthetic aperture radar - Zhichao Zhou; Zegang Ding; Yan Wang; Linghao Li; Kaiwen Zhu; Tao Zeng (International Journal of Remote Sensing, 2019)

NaCl-induced stress: physiological responses of six halophyte species in in vitro and in vivo culture - Yuping Xiong; Hanzhi Liang; Haifeng Yan; Beiyi Guo; Meiyun Niu; Shuangyan Chen; Shuguang Jian; Hai Ren; Xinhua Zhang; Yuan Li; Songjun Zeng; Kunlin Wu; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Land–atmosphere interaction over the Indo-China Peninsula during spring and its effect on the following summer climate over the Yangtze River basin - Chujie Gao; Haishan Chen; Gen Li; Hedi Ma; Xinyu Li; Shangmin Long; Bei Xu; Xing Li; Xinmin Zeng; Hong Yan; Ziqian Wang; Song Yang (Climate Dynamics, 2019)

Genetic Association Between NGFR, ADAM17 Gene Polymorphism, and Parkinson’s Disease in the Chinese Han Population - Wei-Wei Li; Ying-Ying Shen; Dong-Wan Chen; Hui-Yun Li; Qian-Qian Shi; Jing Mei; Heng Yang; Fa-Ying Zhou; An-Yu Shi; Tao Zhang; Xiu-Qing Yao; Zhi-Qiang Xu; et al. (Neurotoxicity Research, 2019)

Joint toxicity of six common heavy metals to Chlorella pyrenoidosa - Ling-Yun Mo; Dan-Na Zhao; Meng Qin; Li-Tang Qin; Hong-Hu Zeng; Yan-Peng Liang (Environmental Science and Pollution Research, 2019)

A CNN-based prototype method of unstructured surgical state perception and navigation for an endovascular surgery robot - Yan Zhao; Shuxiang Guo; Yuxin Wang; Jinxin Cui; Youchun Ma; Yuwen Zeng; Xinke Liu; Yuhua Jiang; Youxinag Li; Liwei Shi; Nan Xiao (Medical & Biological Engineering & Computing, 2019)

Senescence-induced expression of ZmSUT1 in cotton delays leaf senescence while the seed coat-specific expression increases yield - Xiaoyan Ding; Jianyan Zeng; Liang Huang; Xianbi Li; Shuiqing Song; Yan Pei (Plant Cell Reports, 2019)

Correction to: Elevated expression of CST1 promotes breast cancer progression and predicts a poor prognosis - Da-nian Dai; Yan Li; Bo Chen; Yong Du; Shi-bing Li; Shi-xun Lu; Zhi-ping Zhao; Ai-jun Zhou; Ning Xue; Tian-liang Xia; Mu-sheng Zeng; Qian Zhong; et al. (Journal of Molecular Medicine, 2019)

Lasting days contributed most to the variation of ≥ 10 °C accumulated temperature from 1961 to 2010 in China - Jinqin Xu; Xinfa Qiu; Yan Zeng; Mengxi Li; Guoping Shi; Zhe Wang; Xiaochen Zhu; Dandan Wang (Theoretical and Applied Climatology, 2019)

Neurotrophin Receptor p75 mRNA Level in Peripheral Blood Cells of Patients with Alzheimer’s Disease - Yali Xu; Wei-Wei Li; Jun Wang; Chi Zhu; Ying-Ying Shen; An-Yu Shi; Gui-Hua Zeng; Zhi-Qiang Xu; Xin-Fu Zhou; Yan-Jiang Wang (Neurotoxicity Research, 2019)

Evaluation of the association between urinary cadmium levels below threshold limits and the risk of diabetes mellitus: a dose-response meta-analysis - Fei-Fei Guo; Zhi-Yong Hu; Bing-Yan Li; Li-Qiang Qin; Chunling Fu; Huifang Yu; Zeng-Li Zhang (Environmental Science and Pollution Research, 2019)

Predicting the cytotoxicity of disinfection by-products to Chinese hamster ovary by using linear quantitative structure–activity relationship models - Li-Tang Qin; Xin Zhang; Yu-Han Chen; Ling-Yun Mo; Hong-Hu Zeng; Yan-Peng Liang; Hua Lin; Dun-Qiu Wang (Environmental Science and Pollution Research, 2019)

Development of a simple and rapid reverse transcription–loopmediated isothermal amplification (RT‐LAMP) assay for sensitive detection of tilapia lake virus - Jiyuan Yin; Qing Wang; Yingying Wang; Yingying Li; Weiwei Zeng; Jiexing Wu; Yan Ren; Yafang Tang; Caixia Gao; Huzi Hu; Sven M. Bergmann (Journal of Fish Diseases, 2019)
Recently, substantial mortality of farmed and wild tilapia caused by tilapia lake virus (TiLV) infection has been observed worldwide. However, sensitive and reliable diagnostic method is limited. A reverse transcription–loopmediated isothermal amplification (RT‐LAMP) assay has been applied for the detection of TiLV nucleotide sequence. Six primers targeting two locations on the target gene based on a highly conserved sequence in the segment 1 (S1) region of the TiLV genome have been designed. The optimized RT‐LAMP reaction was maintained at the isothermal condition of 63°C for 45 min. And the amplifications could be verified by turbidity or a colour change with the addition of SYBR Green I. Subsequently, RT‐LAMP products could be observed by a ladder pattern following gel electrophoresis. The species‐specific assay showed that the method was sensitive enough to detect as low as 1.6 copies of viral particle, and the assay was highly specific because no cross‐reactivity was observed with other pathogens, and had a diagnostic sensitivity and specificity of 100% when TiLV‐positive samples and non‐target virus were tested. In summary, all the results demonstrate that this RT‐LAMP is a rapid, effective and sensitive method for TiLV detection in tilapia aquaculture.

Comparative transcriptomics analysis uncovers alternative splicing events and molecular markers in cabbage (Brassica oleracea L.) - Yuanyuan Xu; Aisong Zeng; Lixiao Song; Jiaqing Li; Jiyong Yan (Planta, 2019)

Expression of a novel PSK-encoding gene from soybean improves seed growth and yield in transgenic plants - Liangliang Yu; Yumin Liu; Shuang Zeng; Junhui Yan; Ertao Wang; Li Luo (Planta, 2019)

β-Glucanase specific expression in the intestine of transgenic pigs - Li-zeng Guan; Shuai Zhao; Gang Shu; Qing-yan Jiang; Geng-yuan Cai; Zhen-fang Wu; Qian-yun Xi; Yong-liang Zhang (Transgenic Research, 2019)

Effects of anthropogenic nitrogen discharge on dissolved inorganic nitrogen transport in global rivers - Shuang Liu; Zhenghui Xie; Yujin Zeng; Bin Liu; Ruichao Li; Yan Wang; Longhuan Wang; Peihua Qin; Binghao Jia; Jinbo Xie (Global Change Biology, 2019)
Excess nutrients from fertilizer application, pollution discharge, and water regulations outflow through rivers from lands to oceans, seriously impacting coastal ecosystems. A reasonable representation of these processes in land surface models and River Transport Models (RTMs) is very important for understanding human–environment interactions. In this study, the schemes of riverine dissolved inorganic nitrogen (DIN) transport and human activities including nitrogen discharge and water regulation, were synchronously incorporated into a land surface model coupled with a RTM. The effects of anthropogenic nitrogen discharge on the DIN transport in rivers were studied based on simulations of the period 1991–2010 throughout the entire world, conducted using the developed model, which had a spatial resolution of about 1° for land processes and 0.5° for river transport, and data on fertilizer application, point source pollution, and water use. Our results showed that rivers in western Europe and eastern China were seriously polluted, on average, at a rate of 5,000–15,000 tons per year. In the Yangtze River Basin, the amount of point source pollution in 2010 was about four times more than that in 1991, while the amount of fertilizer used in 2010 doubled, which resulted in the increased riverine DIN levels. Further comparisons suggested that the riverine DIN in the USA was affected primarily by nitrogen fertilizer use, the changes in DIN flow rate in European rivers was dominated by point source pollution, and rivers in China were seriously polluted by both the two pollution sources. The total anthropogenic impact on the DIN exported to the Pacific Ocean has increased from 10% to 30%, more significantly than other oceans. In general, our results indicated that incorporating the schemes of nitrogen transport and human activities into land surface models could be an effective way to monitor global river water quality and diagnose the performance of the land surface modeling.

Over-expression of Peach PpIAA19 in Tomato Alters Plant Growth, Parthenocarpy, and Fruit Shape - Yifeng Ding; Wenfang Zeng; Xiaobei Wang; Yan Wang; Liang Niu; Lei Pan; Zhenhua Lu; Guochao Cui; Guohuai Li; Zhiqiang Wang (Journal of Plant Growth Regulation, 2019)

Isolation and identification of a Bacillus subtilis HZ-72 exhibiting biocontrol activity against flax seedling blight - Taimeng Tan; Jiuxiang Zhu; Airong Shen; Jilie Li; Yongting Yu; Mengjun Zhang; Mengrui Zhao; Zhimin Li; Jia Chen; Chunsheng Gao; Yi Cheng; Litao Guo; et al. (European Journal of Plant Pathology, 2019)

Novel Crayfish Shell Biochar Nanocomposites Loaded with Ag-TiO2 Nanoparticles Exhibit Robust Antibacterial Activity - Yifan Zeng; Yingwen Xue; Li Long; Jinpeng Yan (Water, Air, & Soil Pollution, 2019)

Chinese society of cardiology expert consensus statement on the diagnosis and treatment of adult fulminant myocarditis - Daowen Wang; Sheng Li; Jiangang Jiang; Jiangtao Yan; Chunxia Zhao; Yan Wang; Yexin Ma; Hesong Zeng; Xiaomei Guo; Hong Wang; Jiarong Tang; Houjuan Zuo; et al. (Science China Life Sciences, 2019)

Role of prefrontal cortex in the extinction of drug memories - Wen-Hua Zhang; Ke-Xin Cao; Zeng-Bo Ding; Jian-Li Yang; Bing-Xing Pan; Yan-Xue Xue (Psychopharmacology, 2019)

Garnet amphibolites from the Ganzi–Litang fault zone, eastern Tibetan Plateau: mineralogy, geochemistry, and implications for evolution of the eastern Palaeo-Tethys Realm - Qiu-Huan Li; Yu-Xiu Zhang; Kai-Jun Zhang; Li-Long Yan; Lu Zeng; Xin Jin; Jin-Feng Sun; Xiao-Yao Zhou; Xian-Chun Tang; Lu Lu (International Geology Review, 2018)

A targeted sequencing approach to find novel pathogenic genes associated with sporadic aortic dissection - Zongzhe Li; Chengming Zhou; Lun Tan; Peng Chen; Yanyan Cao; Xianqing Li; Jiangtao Yan; Hesong Zeng; Dao-Wu Wang; Dao-Wen Wang (Science China Life Sciences, 2018)

Clinical Research on Alzheimer’s Disease: Progress and Perspectives - Bin-Lu Sun; Wei-Wei Li; Chi Zhu; Wang-Sheng Jin; Fan Zeng; Yu-Hui Liu; Xian-Le Bu; Jie Zhu; Xiu-Qing Yao; Yan-Jiang Wang (Neuroscience Bulletin, 2018)

Adsorptive removal of As(V) by crawfish shell biochar: batch and column tests - Jinpeng Yan; Yingwen Xue; Li Long; Yifan Zeng; Xiaolan Hu (Environmental Science and Pollution Research, 2018)

Altered gray matter volume in primary insomnia patients: a DARTEL-VBM study - Meng Li; Jianhao Yan; Shumei Li; Tianyue Wang; Hua Wen; Yi Yin; Shishun Fu; Luxian Zeng; Junzhang Tian; Guihua Jiang (Brain Imaging and Behavior, 2018)

Establishment and characterization of a cell line from tilapia brain for detection of tilapia lake virus - Yingying Wang; Qing Wang; Weiwei Zeng; Jiyuan Yin; Yingying Li; Yan Ren; Cunbin Shi; Sven M. Bergmann; Xinping Zhu (Journal of Fish Diseases, 2018)
Tilapia lake virus (TiLV) is an emerging disease threatening tilapia culture in many parts of the world. A cell line from the brain of tilapia, which was named TiB, was established, characterized and subcultured with more than 100 passages. The TiB cell line was optimally maintained at 27°C using medium 199 (M199) supplemented with 10% foetal bovine serum (FBS). Chromosome analysis revealed that 60% of TiB cells at passage 5 maintained the modal chromosome number 2 n = 44, while at passage 60, there were 43% of TiB cells with the diploid chromosome number 2 n = 50. A significant cytopathic effect was observed in TiB cells after infection with tilapia lake virus (TiLV‐2017A), and the viral replication in the cells was confirmed by transmission electron microscopy, immunofluorescence assays and viral titres, indicating the susceptibility of TiB cells to TiLV‐2017A. The viral titres of TiLV‐2017A in TiB cells reached 10 7.43 TCID 50 /ml within 10 days. The stable growth and susceptibility to fish viruses make TiB cells a useful tool for fish virus–host cell interaction and for immune response of fish.

Development of a VP 38 recombinant protein‐based indirect ELISA for detection of antibodies against grass carp reovirus genotype II (iELISA for detection of antibodies against GCRV II) - Weiwei Zeng; Yingying Wang; Yanmin Guo; Sven M. Bergmann; Jiyuan Yin; Yingying Li; Yan Ren; Cunbin Shi; Qing Wang (Journal of Fish Diseases, 2018)
Currently, serological assays for grass carp reovirus genotype II ( GCRV ‐II) diagnosis are not available. In this study, an indirect enzyme‐linked immunosorbent assay ( ELISA ) for the detection of antibodies against GCRV ‐II was developed. The structural protein VP 38 of GCRV ‐II was used as the coating antigen. Monoclonal antibodies ( mA b) against IgM of grass carp labelled with HRP were used as a secondary antibody. The antigen concentration and serum dilution were optimized using chess board titration. Furthermore, the specificity of indirect ELISA assay was confirmed by cross check with sera positive for other grass carp pathogens. In comparison with results obtained from indirect immunofluorescence assay ( IFA ) and Western blot by testing of 60 serum samples to evaluate the sensitivity and specificity of the ELISA , agreement between 90% and 96.7% was reached, respectively. A serological survey was performed using the assay with grass carp field serum samples. The seropositive rate of the 242 serum samples was 69.8%. In conclusion, the developed indirect ELISA is a very specific and sensitive test that will be useful for large‐scale serological surveys to detect indirectly GCRV II infections as well as to monitor the changes of antibody level after immunization.

8-isopentenyl isoflavone derivatives from the whole herb of Sphaerophysa salsula - Li-Jin Jiao; Wei-Dong Wang; Yan-Duo Tao; Yun Shao; Li-Juan Mei; Zeng-Gen Liu; Qi-Lan Wang; Jun Dang (Natural Product Research, 2018)

Selective Inhibition on Organic Cation Transporters by Carvedilol Protects Mice from Cisplatin-Induced Nephrotoxicity - Dong Guo; Hong Yang; Qing Li; Hyo Jung Bae; Obinna Obianom; Sujuan Zeng; Tong Su; James E. Polli; Yan Shu (Pharmaceutical Research, 2018)

CYP46A1 and the APOEε4 Allele Polymorphisms Correlate with the Risk of Alzheimer’s Disease - Ling Li; Fan Zeng; Yu-Hui Liu; Hui-Yun Li; Shu-Yang Dong; Ze-Yan Peng; Yan-Jiang Wang; Hua-Dong Zhou (Molecular Neurobiology, 2018)

Research on Lateral Scale Effect and Constitutive Model of Rock Damage Energy Evolution - Xi Yan; Li Jun; Zeng Yijin; Ding Shidong; Jiang Tingxue (Geotechnical and Geological Engineering, 2018)

Regional differences of urbanization in China and its driving factors - WenQi Lin; MengHe Wu; Yue Zhang; RongJun Zeng; XiaoJin Zheng; Lei Shao; LuYun Zhao; ShaoXing Li; Yan Tang (Science China Earth Sciences, 2018)

BDNF/TrkB Pathway Mediates the Antidepressant-Like Role of H2S in CUMS-Exposed Rats by Inhibition of Hippocampal ER Stress - Le Wei; Li-Yuan Kan; Hai-Ying Zeng; Yi-Yun Tang; Hong-Lin Huang; Ming Xie; Wei Zou; Chun-Yan Wang; Ping Zhang; Xiao-Qing Tang (NeuroMolecular Medicine, 2018)

Synaptobrevin-2 facilitates the trafficking and function of atrial SK2 channel - Tao Li; Xuehui Fan; Yiyan Yu; Linlin Chen; Wenjun Huang; Yan Yang; Jimin Cao; Xiaorong Zeng; Xiaoqiu Tan (Science China Life Sciences, 2018)

Epidemiology and clinical characteristics of human coronaviruses OC43, 229E, NL63, and HKU1: a study of hospitalized children with acute respiratory tract infection in Guangzhou, China - Zhi-Qi Zeng; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Huan-Xi Liang; Mei-Xin Chen; Xiao Li; Zheng-Shi Lin; Wen-Kuan Liu; Rong Zhou (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Xylastriasan A, a new cytochalasan from the fungus Xylaria striata - Chuan-Wen Lei; Zhi-Qin Yang; Yan-Ping Zeng; Yun Zhou; Yi Huang; Xin-Sheng He; Guo-You Li; Xiao-Hong Yuan (Natural Product Research, 2018)

Gender-Related Hippocampal Proteomics Study from Young Rats After Chronic Unpredicted Mild Stress Exposure - Lin-Na Ning; Teng Zhang; Jiang Chu; Na Qu; Li Lin; Ying-Yan Fang; Yan Shi; Peng Zeng; Er-Li Cai; Xiao-Ming Wang; Qun Wang; You-Ming Lu; et al. (Molecular Neurobiology, 2018)

Phenolic constituents from Rheum nobile and their antioxidant activity - Ye Fei; Juan Wang; Bing Peng; Jiangnan Peng; Jing-Hong Hu; Zu-Ping Zeng; Jing Chen; Qi-En Li; Zeng-Ping Gao; Xing-Li Yan (Natural Product Research, 2017)

CASCIRE surveillance network and work on avian influenza viruses - Yuhai Bi; Weifeng Shi; Jianjun Chen; Quanjiao Chen; Zhenghai Ma; Gary Wong; Wenxia Tian; Renfu Yin; Guanghua Fu; Yongchun Yang; William J. Liu; Chuansong Quan; et al. (Science China Life Sciences, 2017)

Identification of a novel envelope protein encoded by ORF 136 from Cyprinid herpesvirus 3 - Shucheng Zheng; Yingying Li; Qing Wang; Jiexing Wu; Yingying Wang; Weiwei Zeng; Sven M. Bergmann; Yan Ren; Cunbin Shi (Archives of Virology, 2017)

Saikosaponin D relieves unpredictable chronic mild stress induced depressive-like behavior in rats: involvement of HPA axis and hippocampal neurogenesis - Hong-Yan Li; Ying-Hua Zhao; Min-Jie Zeng; Fang Fang; Min Li; Ting-Ting Qin; Lu-Yu Ye; Hong-Wei Li; Rong Qu; Shi-Ping Ma (Psychopharmacology, 2017)

Agrobacterium deltaense sp. nov., an endophytic bacteria isolated from nodule of Sesbania cannabina - Jun Yan; Yan Li; Xiao Zeng Han; Wen Feng Chen; Wen Xiu Zou; Zhihong Xie; Meng Li (Archives of Microbiology, 2017)

Elevated expression of CST1 promotes breast cancer progression and predicts a poor prognosis - Da-nian Dai; Yan Li; Bo Chen; Yong Du; Shi-bing Li; Shi-xun Lu; Zhi-ping Zhao; Ai-jun Zhou; Ning Xue; Tian-liang Xia; Mu-sheng Zeng; Qian Zhong; et al. (Journal of Molecular Medicine, 2017)
Cystatin SN (CST1) belongs to the type 2 cystatin (CST) superfamily, which restricts the proteolytic activities of cysteine proteases. CST1 has been recently considered to be involved in the development of several human cancers. However, the prognostic significance and function of CST1 in breast cancer remains unknown. In the current study, we found that CST1 was generally upregulated in breast cancer at both mRNA and protein level. Furthermore, overall survival (OS) and disease-free survival (DFS) in the low CST1 expression subgroup were significantly superior to the high CST1 expression subgroup (OS, p < 0.001; DFS, p < 0.001), which indicated that CST1 expression level was closely correlated to the survival risk of these patients. Univariate and multivariate analyses demonstrated that CST1 expression was an independent prognostic factor, the same as ER status and nodal status. Next, CST1 overexpression promoted breast cancer cell proliferation, clonogenicity, migration, and invasion abilities. By contrast, knockdown of CST1 attenuated these malignant characteristics in breast cancer cells. Collectively, our study indicates that CST1 cannot only serve as a significant prognostic indicator but also as a potential therapeutic target for breast cancer. Key messages High CST1 expression is negatively correlated with survival of breast cancer patients. CST1 promotes cell proliferation, clone formation, and metastasis in breast cancer cells. CST1 is a novel potential prognostic biomarker and therapeutic target for breast cancer.

Expression-based genotyping of the rice blast resistance genes in the elite maintainer line Yixiang1B - Li Wang; Xiao-Hong Hu; Gang Lin; De-Ming Zhao; Jun Shi; Zhi-Xue Zhao; Rui Zeng; Heng-Jing Li; De-Qiang Li; Jing Fan; Yan Li; Fu Huang; et al. (European Journal of Plant Pathology, 2017)

Altered white matter microstructure identified with tract-based spatial statistics in irritable bowel syndrome: a diffusion tensor imaging study - Jin Fang; Shumei Li; Meng Li; Queenie Chan; Xiaofen Ma; Huanhuan Su; Tianyue Wang; Wenfeng Zhan; Jianhao Yan; Ming Xu; Yaxi Zhang; Luxian Zeng; et al. (Brain Imaging and Behavior, 2017)

Two-Stage Prediction on Effects of Mixtures Containing Phenolic Compounds and Heavy Metals on Vibrio qinghaiensis sp. Q67 - Ling-Yun Mo; Jie Liu; Li-Tang Qin; Hong-Hu Zeng; Yan-Peng Liang (Bulletin of Environmental Contamination and Toxicology, 2017)

Two ultraviolet radiation datasets that cover China - Hui Liu; Bo Hu; Yuesi Wang; Guangren Liu; Liqin Tang; Dongsheng Ji; Yongfei Bai; Weikai Bao; Xin Chen; Yunming Chen; Weixin Ding; Xiaozeng Han; et al. (Advances in Atmospheric Sciences, 2017)

RETRACTED ARTICLE: Revisiting the male genetic landscape of China: a multi-center study of almost 38,000 Y-STR haplotypes - Michael Nothnagel; Guangyao Fan; Fei Guo; Yongfeng He; Yiping Hou; Shengping Hu; Jiang Huang; Xianhua Jiang; Wook Kim; Kicheol Kim; Chengtao Li; Hui Li; et al. (Human Genetics, 2017)

Cd Content in Sugarcane and Its Relationship with Soil Factors - Hui-Ping Ou; Liu-Qiang Zhou; Xi-Hui Liu; Jin-Sheng Huang; Yan Zeng; Ru-Lin Xie; Xiao-Hui Zhu; Hong-Wei Tan; Yang-Rui Li (Sugar Tech, 2017)

Associations Between Hepatic Functions and Plasma Amyloid-Beta Levels—Implications for the Capacity of Liver in Peripheral Amyloid-Beta Clearance - Ye-Ran Wang; Qing-Hua Wang; Tao Zhang; Yu-Hui Liu; Xiu-Qing Yao; Fan Zeng; Jing Li; Fa-Yin Zhou; Lin Wang; Jia-Chuan Yan; Hua-Dong Zhou; Yan-Jiang Wang (Molecular Neurobiology, 2017)

Establishment of mouse leukemia cell lines expressing human CD4/CCR5 using lentiviral vectors - Ya-jing Li; Fu-yan ZhuGe; Chang-chun Zeng; Jin-yang He; Ning Tan; Juan Liang (Virus Genes, 2017)

Genetic characterization of H9N2 avian influenza virus in plateau pikas in the Qinghai Lake region of China - Yan Yan; Jin-Yan Gu; Zhuang-Chuan Yuan; Xin-Yu Chen; Zeng-Kui Li; Jing Lei; Bo-li Hu; Li-Ping Yan; Gang Xing; Min Liao; Ji-Yong Zhou (Archives of Virology, 2017)

Variation in accumulation and translocation of di-n-butyl phthalate (DBP) among rice (Oryza sativa L.) genotypes and selection of cultivars for low DBP exposure - Quan-Ying Cai; Pei-Yun Xiao; Hai-Ming Zhao; Huixiong Lü; Qiao-Yun Zeng; Yan-Wen Li; Hui Li; Lei Xiang; Ce-Hui Mo (Environmental Science and Pollution Research, 2017)

Characterization of the complete chloroplast genome of Platycarya strobilacea (Juglandaceae) - Jing Yan; Kai Han; Shuyun Zeng; Peng Zhao; Keith Woeste; Jianfang Li; Zhan-Lin Liu (Conservation Genetics Resources, 2017)

Identification of a New Rice Low-Tiller Mutant and Association Analyses Based on the SLAF-seq Method - Yan Li; Xiao-Fang Zeng; Yi-Chen Zhao; Jian-Rong Li; De-Gang Zhao (Plant Molecular Biology Reporter, 2017)

Improvement of anti-nutritional effect resulting from β-glucanase specific expression in the parotid gland of transgenic pigs - Li-zeng Guan; Jin-shun Cai; Shuai Zhao; Yu-ping Sun; Jing-lan Wang; Yong Jiang; Gang Shu; Qing-yan Jiang; Zhen-fang Wu; Qian-yun Xi; Yong-liang Zhang (Transgenic Research, 2017)

Early Cretaceous porphyry copper mineralization in Northeast China: the Changfagou example - Yong Zhang; Shu–Wen Xing; Chao Li; Shi–Fu Liang; Zheng–Tao Yu; Xiao–Hui Du; Yan Wang; Zeng–Jie Zhang; Yu–Bo Ma (International Geology Review, 2017)

Petrology and geochemistry of Early Cretaceous A-type granitoids and late Mesozoic mafic dikes and their relationship to adakitic intrusions in the lower Yangtze River belt, Southeast China - Yi-Zeng Yang; Yan Wang; Ri-Sheng Ye; Shuang-Qing Li; Jian-Feng He; Wolfgang Siebel; Fukun Chen (International Geology Review, 2017)

Variants of genes encoding collagens and matrix metalloproteinase system increased the risk of aortic dissection - Zongzhe Li; Chengming Zhou; Lun Tan; Peng Chen; Yanyan Cao; Chenze Li; Xianqing Li; Jiangtao Yan; Hesong Zeng; Dao-Wu Wang; Dao-Wen Wang (Science China Life Sciences, 2017)

Incentive effect of bentonite and concrete admixtures on stabilization/solidification for heavy metal-polluted sediments of Xiangjiang River - Ming Yan; Guangming Zeng; Xiaoming Li; Jianmin He; Guiqiu Chen; Danlian Huang; Lin Tang; Cui Lai; Chang Zhang; Xiaodong Li; Lichao Wang; Zhi Guo; et al. (Environmental Science and Pollution Research, 2017)

Rhizobium hidalgonense sp. nov., a nodule endophytic bacterium of Phaseolus vulgaris in acid soil - Jun Yan; Hui Yan; Li Xue Liu; Wen Feng Chen; Xiao Xia Zhang; Myrthala M. Verástegui-Valdés; En Tao Wang; Xiao Zeng Han (Archives of Microbiology, 2017)

New Labdane diterpenes from Hedychium yunnanense with cytotoxicity and inhibitory effects on nitric oxide production - Yu-Peng Li; Si-Meng Zhao; Jun-Ju Xu; Guang-Zhi Zeng; Yan Li; Ning-Hua Tan; Ye Yang (Natural Product Research, 2016)

Influence of genetic polymorphisms in cytochrome P450 oxidoreductase on the variability in stable warfarin maintenance dose in Han Chinese - Wu-Tao Zeng; Qing Xu; Cheng-Hsun Li; Wei-Yan Chen; Xiu-Ting Sun; Xiang Wang; Yi-Ying Yang; Hui Shi; Zhi-Sheng Yang (European Journal of Clinical Pharmacology, 2016)

Clitocine potentiates TRAIL-mediated apoptosis in human colon cancer cells by promoting Mcl-1 degradation - Jian-guo Sun; Feng Ruan; Xue-li Zeng; Jun Xiang; Xia Li; Ping Wu; Kwok Pui Fung; Fei-yan Liu (Apoptosis, 2016)

Characterization of the complete mitochondrial genome of the myrmicine ant Vollenhovia emeryi (Insecta: Hymenoptera: Formicidae) - Nian Liu; Xiao-Yu Duan; Zeng-Qiang Qian; Xin-Yue Wang; Xiu-Ling Li; Mei-Yan Ding (Conservation Genetics Resources, 2016)

Common Aging Signature in the Peripheral Blood of Vascular Dementia and Alzheimer’s Disease - Hongbo Luo; Guangchun Han; Jiajia Wang; Fan Zeng; Yuanming Li; Shaoju Shao; Fuhai Song; Zhouxian Bai; Xing Peng; Yan-Jiang Wang; Xiangqun Shi; Hongxing Lei (Molecular Neurobiology, 2016)

IGF-I stimulates ERβ and aromatase expression via IGF1R/PI3K/AKT-mediated transcriptional activation in endometriosis - Yan Zhou; Cheng Zeng; Xin Li; Pei-Li Wu; Ling Yin; Xiao-Lan Yu; Ying-Fang Zhou; Qing Xue (Journal of Molecular Medicine, 2016)

Expression of HIV-encoded microRNA-TAR and its inhibitory effect on viral replication in human primary macrophages - Li Li; Haimin Feng; Qin Da; Honglin Jiang; Lang Chen; Linlin Xie; Qiuling Huang; Hairong Xiong; Fan Luo; Lei Kang; Yan Zeng; Haitao Hu; et al. (Archives of Virology, 2016)

Study on the removal of elemental mercury from simulated flue gas by Fe2O3-CeO2/AC at low temperature - Yan Wang; Caiting Li; Lingkui Zhao; Yin’e Xie; Xunan Zhang; Guangming Zeng; Huiyu Wu; Jie Zhang (Environmental Science and Pollution Research, 2016)

Global patterns and climate drivers of water‐use efficiency in terrestrial ecosystems deduced from satellite‐based datasets and carbon cycle models - Yan Sun; Shilong Piao; Mengtian Huang; Philippe Ciais; Zhenzhong Zeng; Lei Cheng; Xiran Li; Xinping Zhang; Jiafu Mao; Shushi Peng; Benjamin Poulter; Xiaoying Shi; et al. (Global Ecology and Biogeography, 2016)
Aim To investigate how ecosystem water‐use efficiency ( WUE ) varies spatially under different climate conditions, and how spatial variations in WUE differ from those of transpiration‐based water‐use efficiency ( WUE t ) and transpiration‐based inherent water‐use efficiency ( IWUE t ). Location Global terrestrial ecosystems. Methods We investigated spatial patterns of WUE using two datasets of gross primary productivity ( GPP ) and evapotranspiration ( ET ) and four biosphere model estimates of GPP and ET . Spatial relationships between WUE and climate variables were further explored through regression analyses. Results Global WUE estimated by two satellite‐based datasets is 1.9 ± 0.1 and 1.8 ± 0.6 g C m −2 mm −1 lower than the simulations from four process‐based models (2.0 ± 0.3 g C m −2 mm −1 ) but comparable within the uncertainty of both approaches. In both satellite‐based datasets and process models, precipitation is more strongly associated with spatial gradients of WUE for temperate and tropical regions, but temperature dominates north of 50° N . WUE also increases with increasing solar radiation at high latitudes. The values of WUE from datasets and process‐based models are systematically higher in wet regions (with higher GPP ) than in dry regions. WUE t shows a lower precipitation sensitivity than WUE , which is contrary to leaf‐ and plant‐level observations. IWUE t , the product of WUE t and water vapour deficit, is found to be rather conservative with spatially increasing precipitation, in agreement with leaf‐ and plant‐level measurements. Main conclusions WUE , WUE t and IWUE t produce different spatial relationships with climate variables. In dry ecosystems, water losses from evaporation from bare soil, uncorrelated with productivity, tend to make WUE lower than in wetter regions. Yet canopy conductance is intrinsically efficient in those ecosystems and maintains a higher IWUE t . This suggests that the responses of each component flux of evapotranspiration should be analysed separately when investigating regional gradients in WUE , its temporal variability and its trends.

The Influence of wave state and sea spray on drag coefficient from low to high wind speeds - Jian Shi; Zhong Zhong; Xunqiang Li; Guorong Jiang; Wenhua Zeng; Yan Li (Journal of Ocean University of China, 2016)

Assessing the influence of water level on schistosomiasis in Dongting Lake region before and after the construction of Three Gorges Dam - Zhongwu Li; Xiaodong Nie; Yan Zhang; Jinquan Huang; Bin Huang; Guangming Zeng (Environmental Monitoring and Assessment, 2016)

Synthesis and Application of Modified Zero-Valent Iron Nanoparticles for Removal of Hexavalent Chromium from Wastewater - Dan-Lian Huang; Guo-Min Chen; Guang-Ming Zeng; Piao Xu; Ming Yan; Cui Lai; Chen Zhang; Ning-Jie Li; Min Cheng; Xiao-Xiao He; Yan He (Water, Air, & Soil Pollution, 2015)

An efficient protocol for Agrobacterium-mediated transformation of the biofuel plant Jatropha curcas by optimizing kanamycin concentration and duration of delayed selection - Qiantang Fu; Chaoqiong Li; Mingyong Tang; Yan-Bin Tao; Bang-Zhen Pan; Lu Zhang; Longjian Niu; Huiying He; Xiulan Wang; Zeng-Fu Xu (Plant Biotechnology Reports, 2015)

Differential protein expression analysis following olfactory learning in Apis cerana - Li-Zhen Zhang; Wei-Yu Yan; Zi-Long Wang; Ya-Hui Guo; Yao Yi; Shao-Wu Zhang; Zhi-Jiang Zeng (Journal of Comparative Physiology A, 2015)

In vitro interaction between coxsackievirus B3 VP1 protein and human pleckstrin homology domain retinal protein (PHR1) - Ying Zhou; Zhiqin Zhang; Hongluan Wang; Yanhua Xia; Xiuzhen Li; Yan Yan; Weiwen Zou; Lingbing Zeng; Xiaotian Huang (Virus Genes, 2015)

Phylogenic diversity and tissue specificity of fungal endophytes associated with the pharmaceutical plant, Stellera chamaejasme L. revealed by a cultivation-independent approach - Hui Jin; Xiaoyan Yang; Dengxue Lu; Chunjie Li; Zhiqiang Yan; Xiuzhuang Li; Liming Zeng; Bo Qin (Antonie van Leeuwenhoek, 2015)

Upregulation and Diverse Roles of TRPC3 and TRPC6 in Synaptic Reorganization of the Mossy Fiber Pathway in Temporal Lobe Epilepsy - Chang Zeng; Pinting Zhou; Ting Jiang; Chunyun Yuan; Yan Ma; Li Feng; Renkai Liu; Weiting Tang; Xiaoyan Long; Bo Xiao; Fafa Tian (Molecular Neurobiology, 2015)

Linear regression model for predicting interactive mixture toxicity of pesticide and ionic liquid - Li-Tang Qin; Jie Wu; Ling-Yun Mo; Hong-Hu Zeng; Yan-Peng Liang (Environmental Science and Pollution Research, 2015)

Response of extracellular carboxylic and thiol ligands (oxalate, thiol compounds) to Pb2+ stress in Phanerochaete chrysosporium - Ningjie Li; Guangming Zeng; Danlian Huang; Chao Huang; Cui Lai; Zhen Wei; Piao Xu; Chen Zhang; Min Cheng; Ming Yan (Environmental Science and Pollution Research, 2015)

Toxic metals in topsoil under different land uses from Xiandao District, middle China: distribution, relationship with soil characteristics, and health risk assessment - Fei Li; Jinhui Huang; Guangming Zeng; Wenchu Liu; Xiaolong Huang; Bin Huang; Yanling Gu; Lixiu Shi; Xiaoxiao He; Yan He (Environmental Science and Pollution Research, 2015)

Age, petrogenesis and tectonic significance of the ferrobasalts in the Chagangnuoer iron deposit, western Tianshan - Ning-Bo Li; He-Cai Niu; Xing-Chun Zhang; Qiao-Song Zeng; Qiang Shan; Cong-Ying Li; Shuang Yan; Wu-Bin Yang (International Geology Review, 2015)

Diversity and space–time dynamics of endophytic archaea from sugar beet in the north slope of Tianshan Mountain revealed by 454 pyrosequencing and T-RFLP - YingWu Shi; MuSi TaPa; Chun Li; HongMei Yang; Tao Zhang; Yan Gao; Jian Sun; Jun Zeng; Qing Lin; ZhenHua Cao; KuEr OuTi; YuGuo Li; et al. (World Journal of Microbiology and Biotechnology, 2015)

Focal mechanisms of the Lushan earthquake sequence and spatial variation of the stress field - Yan Luo; Li Zhao; XiangFang Zeng; Yuan Gao (Science China Earth Sciences, 2015)

Elevated follicular helper T Cells and expression of IL-21 in thyroid tissues are involved in the pathogenesis of Graves’ disease - Jin Zhang; Meng Ren; Hua Zeng; Ying Guo; Zhenwu Zhuang; Zhimei Feng; Haiyan Yan; Mingtong Xu; Weiwen Liang; Chuan Yang; Hua Cheng; Helin Ding; et al. (Immunologic Research, 2015)

Induction and development of microspore-derived embryos in broccoli × white-headed cabbage hybrids microspore culture - Aisong Zeng; Jiyong Yan; Lixiao Song; Bing Gao; Yunxia Zhang; Jianqi Li; Huanhuan Liu; Xilin Hou; Ying Li (Euphytica, 2015)

Genetic Association Between APP, ADAM10 Gene Polymorphism, and Sporadic Alzheimer’s Disease in the Chinese Population - Fan Zeng; Cheng Shen; Yu-Hui Liu; Jing Li; Jie Zhu; Ye-Ran Wang; Jia-Chuan Yan; Chang-Yue Gao; Hua-Dong Zhou; Juan Deng; Yan-Jiang Wang (Neurotoxicity Research, 2015)

Serum Aβ is Predictive for Short-Term Neurological Deficits After Acute Ischemic Stroke - Yu-Hui Liu; Hong-Yuan Cao; Ye-Ran Wang; Shu-Sheng Jiao; Xian-Le Bu; Fan Zeng; Qing-Hua Wang; Jing Li; Juan Deng; Hua-Dong Zhou; Yan-Jiang Wang (Neurotoxicity Research, 2015)

The Marginal Division of the Striatum and Hippocampus Has Different Role and Mechanism in Learning and Memory - Si-Yun Shu; Gang Jiang; Qi-Yi Zeng; Bin Wang; Hong Li; Lin Ma; Harry Steinbusch; Cai Song; Wood-Yee Chan; Xu-Hong Chen; Yon-Ming Wu; Rong Bao; et al. (Molecular Neurobiology, 2015)

Co-transplantation of Hematopoietic Stem Cells and Cxcr4 Gene-Transduced Mesenchymal Stem Cells Promotes Hematopoiesis - Wei Chen; Miao Li; Guizhen Su; Yu Zang; Zhiling Yan; Hai Cheng; Bin Pan; Jiang Cao; Qingyun Wu; Kai Zhao; Feng Zhu; Lingyu Zeng; et al. (Cell Biochemistry and Biophysics, 2015)

Genetic analysis of the Holliday junction resolvases Hje and Hjc in Sulfolobus islandicus - Qihong Huang; Yansheng Li; Chaoning Zeng; Tengteng Song; Zhou Yan; Jinfeng Ni; Qunxin She; Yulong Shen (Extremophiles, 2015)

Seismic design or retrofit of buildings with metallic structural fuses by the damage-reduction spectrum - Gang Li; Yi Jiang; Shuchuan Zhang; Yan Zeng; Qiang Li (Earthquake Engineering and Engineering Vibration, 2015)

Nutritional Quality and Safety of the Important Commercial Cuttlefish Sepia lycidas - Jing Wen; Daohai Chen; Ling Zeng; Yan Wang; Li Tian; Jiancai Lai (Journal of Aquatic Food Product Technology, 2015)

Global trends of research on emerging contaminants in the environment and humans: a literature assimilation - Lian-Jun Bao; Yan-Li Wei; Yao Yao; Qin-Qin Ruan; Eddy Y. Zeng (Environmental Science and Pollution Research, 2015)

Effect of auxin, cytokinin and nitrogen on anthocyanin biosynthesis in callus cultures of red-fleshed apple (Malus sieversii f.niedzwetzkyana) - Xiao-Hao Ji; Yan-Ting Wang; Rui Zhang; Shu-Jing Wu; Meng-Meng An; Min Li; Chuan-Zeng Wang; Xiao-Liu Chen; Yan-Min Zhang; Xue-Sen Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Determination of multiple elements in samples of the medicinal plant Marsdenia tenacissima and estimation of geographic origin via pattern recognition techniques - Chao Li; Qiao-sheng Guo; Sheng-chao Yang; Kai-yan Zheng; Wang-ping Li; Zhen-gui Meng; Xiang-zeng Xu (Journal of Natural Medicines, 2015)

Contamination of commercially available seafood by key diarrhetic shellfish poisons along the coast of China - Chao Lin; Zeng-Shan Liu; Cai-Yun Tan; Yi-Ping Guo; Lin Li; Hong-Lin Ren; Yan-Song Li; Pan Hu; Sheng Gong; Yu Zhou; Shi-Ying Lu (Environmental Science and Pollution Research, 2015)

Isolation and characterization of polymorphic microsatellites in the perennial herb Euphorbia kansui using paired-end Illumina shotgun sequencing - Xiao-Hao Yan; Min-Feng Fang; Zeng-Qiang Qian; Zhan-Lin Liu; Ma-Li Wang; Cai-Ping Tian; Meng-Han Du; Yin-Jun Li; Zhong-Hu Li; Gui-Fang Zhao (Conservation Genetics Resources, 2014)

Potent in vitro synergism of fusidic acid (FA) and berberine chloride (BBR) against clinical isolates of methicillin-resistant Staphylococcus aureus (MRSA) - Rong-mei Liang; Xiao-lan Yong; Yu-qin Duan; Yong-hong Tan; Ping Zeng; Zi-ying Zhou; Yan Jiang; Shi-hua Wang; Yun-ping Jiang; Xiao-chun Huang; Zhao-hui Dong; Ting-ting Hu; et al. (World Journal of Microbiology and Biotechnology, 2014)

The Association Between Single Nucleotide Polymorphisms of GSK 3β Gene and Sporadic Alzheimer’s Disease in a Cohort of Southern Chinese Han Population - Jing Li; Fan Zeng; Juan Deng; Jie Zhu; Lin Li; Tao Zhang; Juan Liu; Li–Li Zhang; Chang-Yue Gao; Meng Zhang; Zhi-Qiang Xu; Hua-Dong Zhou; et al. (Neurotoxicity Research, 2014)

A new genus Pseudoaustroboletus (Boletaceae, Boletales) from Asia as inferred from molecular and morphological data - Yan-Chun Li; Fang Li; Nian-Kai Zeng; Yang Yang Cui; Zhu L. Yang (Mycological Progress, 2014)

Deciphering the molecular responses to methanol-enhanced photosynthesis and stomatal conductance in broad bean - Yan Zhao; Zhi-Dong Zeng; Chuan-Jiao Qi; Xue-Song Yu; Chuan-Long Guo; Qi Chen; Li-Mei Chen (Acta Physiologiae Plantarum, 2014)

Palaeoproterozoic Chibaisong mafic intrusion and mineralization (Northeast China), the oldest Cu–Ni sulphide deposit in China: evidence from Re–Os dating of pyrrhotite - Yong Zhang; Shu–Wen Xing; Yan Wang; Yu–Bo Ma; Xiao–Hui Du; Zeng–Jie Zhang; Chao Li; Si–Yu Liu; Ming Chen (International Geology Review, 2014)

Needle-free injection of insulin powder: delivery efficiency and skin irritation assessment - Chun-yu Li; Zhe-wei Wang; Can Tu; Jia-bo Wang; Bing-qian Jiang; Qi Li; Ling-na Zeng; Zhi-jie Ma; Ping Zhang; Yan-ling Zhao; Ya-ming Zhang; Dan Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Cross-modal interaction between visual and olfactory learning in Apis cerana - Li-Zhen Zhang; Shao-Wu Zhang; Zi-Long Wang; Wei-Yu Yan; Zhi-Jiang Zeng (Journal of Comparative Physiology A, 2014)

A field study of the relationship between sulfide-bound metals and bioaccumulation by Limnodrilus sp. in a heavily polluted river - Feng Li; Xiang-yun Zeng; Yun-jun Yu; Chang-hua Wu; Ge Mai; Wei-wei Song; Yan-mao Wen; Zhi-peng Duan; Jia-yu Yang (Environmental Monitoring and Assessment, 2014)

A promoter analysis of MOTHER OF FT AND TFL1 1 (JcMFT1), a seed-preferential gene from the biofuel plant Jatropha curcas - Yan-Bin Tao; Li Luo; Liang-Liang He; Jun Ni; Zeng-Fu Xu (Journal of Plant Research, 2014)

Over-expression of heat shock factor gene (AtHsfA1d) from Arabidopsis thaliana confers formaldehyde tolerance in tobacco - Hong-Juan Nian; Dao-Jun Zhang; Zhi-Dong Zeng; Jin-Ping Yan; Kun-Zhi Li; Li-Mei Chen (Acta Physiologiae Plantarum, 2014)

Mineral photoelectrons and their implications for the origin and early evolution of life on Earth - AnHuai Lu; Xin Wang; Yan Li; HongRui Ding; ChangQiu Wang; CuiPing Zeng; RuiXia Hao; XiaoXue Yang (Science China Earth Sciences, 2014)

Coffee consumption and prostate cancer risk: an updated meta-analysis - Yu Lu; Limin Zhai; Jie Zeng; Qiliu Peng; Jian Wang; Yan Deng; Li Xie; Cuiju Mo; Shi Yang; Shan Li; Xue Qin (Cancer Causes & Control, 2014)

Clitocine targets Mcl-1 to induce drug-resistant human cancer cell apoptosis in vitro and tumor growth inhibition in vivo - Jian-guo Sun; Hua Li; Xia Li; Xueli Zeng; Ping Wu; Kwok-Pui Fung; Fei-yan Liu (Apoptosis, 2014)

Differences in Gene Expression and Regulation during Ontogenetic Phase Change in Apple Seedlings - Yan Gao; Feng Qiu Yang; Xin Cao; Chun Min Li; Yi Wang; Yong Bo Zhao; Guang Juan Zeng; Dong Mei Chen; Zhen Hai Han; Xin Zhong Zhang (Plant Molecular Biology Reporter, 2014)

Laforin–Malin Complex Degrades Polyglucosan Bodies in Concert with Glycogen Debranching Enzyme and Brain Isoform Glycogen Phosphorylase - Yan Liu; Li Zeng; Keli Ma; Otto Baba; Pen Zheng; Yang Liu; Yin Wang (Molecular Neurobiology, 2014)

Regulation network and expression profiles of Epstein-Barr virus-encoded microRNAs and their potential target host genes in nasopharyngeal carcinomas - ZhaoYang Zeng; HongBin Huang; LiLi Huang; MengXi Sun; QiJia Yan; YaLi Song; Fang Wei; Hao Bo; ZhaoJian Gong; Yong Zeng; Qiao Li; WenLing Zhang; et al. (Science China Life Sciences, 2014)

Diversity of bacterioplankton in coastal seawaters of Fildes Peninsula, King George Island, Antarctica - Yin-Xin Zeng; Yong Yu; Zong-Yun Qiao; Hai-Yan Jin; Hui-Rong Li (Archives of Microbiology, 2014)

Involvement of abscisic acid in regulating antioxidative defense systems and IAA-oxidase activity and improving adventitious rooting in mung bean [Vigna radiata (L.) Wilczek] seedlings under cadmium stress - Shi-Weng Li; Yan Leng; Lin Feng; Xiao-Ying Zeng (Environmental Science and Pollution Research, 2014)

Chromium level and intake from Chinese made tea - Wei-hao Li; Hai-ping Zhou; Ning Li; Sai-di Wang; Xiao-juan Liu; Zeng-jun Jin; Yan-zhen Bu; Zhi-xue Liu (Food Additives & Contaminants Part B-Surveillance, 2013)

Human umbilical cord-derived MSC culture: the replacement of animal sera with human cord blood plasma - Yan Ding; Hua Yang; Jing Bo Feng; Ying Qiu; Dong Sheng Li; Yi Zeng (In Vitro Cellular & Developmental Biology - Animal, 2013)

Overexpression of the Mesenchymal Stem Cell Cxcr4 Gene in Irradiated Mice Increases the Homing Capacity of These Cells - Wei Chen; Miao Li; Hai Cheng; Zhiling Yan; Jiang Cao; Bin Pan; Wei Sang; Qingyun Wu; Lingyu Zeng; Zhenyu Li; Kailin Xu (Cell Biochemistry and Biophysics, 2013)

Identification of MHC class I sequences in four species of Macaca of China - Xiang Yan; Aixue Li; Lin Zeng; Yuhua Cao; Jianbin He; Longbao Lv; Lihua Sui; Huahu Ye; Junwen Fan; Xiaoxia Cui; Zhaozeng Sun (Immunogenetics, 2013)

Rhynchophylline-induced vasodilation in human mesenteric artery is mainly due to blockage of L-type calcium channels in vascular smooth muscle cells - Peng-Yun Li; Xiao-Rong Zeng; Jun Cheng; Jing Wen; Isao Inoue; Yan Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

A Highly Selective Turn-On Fluorescent Chemosensor for Zinc Ion in Aqueous Media - Zeng-chen Liu; Zheng-yin Yang; Yan-xia Li; Bao-dui Wang; Yong Li; Tian-rong Li; Yong-jie Ding (Journal of Fluorescence, 2013)

Ecological Risks Assessment and Pollution Source Identification of Trace Elements in Contaminated Sediments from the Pearl River Delta, China - Feng Li; Xiang-yun Zeng; Chang-hua Wu; Zhi-peng Duan; Yan-mao Wen; Guo-ru Huang; Xiao-lin Long; Min-Jian Li; Man-Jie Li; Jiang-Yu Xu (Biological Trace Element Research, 2013)

A new triterpene saponin from the roots of Ilex pubescens - Zhong-Liu Zhou; Zong-Cai Feng; Chun-Yan Fu; Li Zeng (Natural Product Research, 2013)

Quantification of serum HBXAP DNA in lung cancer patients by quantitative fluorescent polymerase chain reaction - Yu-Lei Hou; Hui Chen; Ming-Jian Ge; Feng-Zeng Li; Cheng-Jun Xue; Yan-Feng Wu; Hai-Xia Luo (Molecular Biology Reports, 2013)

Musca Domestica Larva Lectin Induces Apoptosis in BEL-7402 Cells Through a Ca2+/JNK-mediated Mitochondrial Pathway - Chun-Ling Wang; Yan Xia; Jian-Zeng Nie; Minghui Zhou; Rong-Ping Zhang; Li-Li Niu; Li-Hua Hou; Xiao-Hong Cao (Cell Biochemistry and Biophysics, 2013)

Arbuscular mycorrhizal symbiosis and active ingredients of medicinal plants: current research status and prospectives - Yan Zeng; Lan-Ping Guo; Bao-Dong Chen; Zhi-Peng Hao; Ji-Yong Wang; Lu-Qi Huang; Guang Yang; Xiu-Ming Cui; Li Yang; Zhao-Xiang Wu; Mei-Lan Chen; Yan Zhang (Mycorrhiza, 2013)

Diversity of bacteria in surface ice of Austre Lovénbreen glacier, Svalbard - Yin-Xin Zeng; Ming Yan; Yong Yu; Hui-Rong Li; Jian-Feng He; Kun Sun; Fang Zhang (Archives of Microbiology, 2013)

In vitro isolation and cultivation of rabbit tracheal epithelial cells using tissue explant technique - Hong-Can Shi; Dan Lu; Hai-Jia Li; Shi Han; Yan-Jun Zeng (In Vitro Cellular & Developmental Biology - Animal, 2013)

Application of portable gas chromatography-photo ionization detector combined with headspace sampling for field analysis of benzene, toluene, ethylbenzene, and xylene in soils - You-Ya Zhou; Ji-Fang Yu; Zeng-Guang Yan; Chao-Yan Zhang; Ya-Bo Xie; Li-Qiang Ma; Qing-Bao Gu; Fa-Sheng Li (Environmental Monitoring and Assessment, 2013)

Genetic diversity of Bartonella quintana in macaques suggests zoonotic origin of trench fever - Hao Li; Jie‐Ying Bai; Li‐Yuan Wang; Lin Zeng; Yan‐Sheng Shi; Zheng‐Liang Qiu; Hua‐Hu Ye; Xiao‐Fei Zhang; Qing‐Bin Lu; Michael Kosoy; Wei Liu; Wu‐Chun Cao (Molecular Ecology, 2013)
Bartonella quintana is a bacterium that causes a broad spectrum of diseases in humans including trench fever. Humans were previously considered to be the primary, if not the only, reservoir hosts for B. quintana . To identify the animal reservoir and extend our understanding of the ecological and evolutionary history of B. quintana , we examined blood samples from macaques and performed multilocus sequence typing ( MLST ) analysis. We demonstrated the prevalence of B. quintana infection was common in macaques from main primate centres in mainland C hina. Overall, 18.0% (59/328) of rhesus macaques and 12.7% (39/308) of cynomolgus macaques were found to be infected with B. quintana by blood culture and/or polymerase chain reaction. The infection was more frequently identified in juvenile and young monkeys compared with adult animals. In contrast with the relatively low level of sequence divergence of B. quintana reported in humans, our investigation revealed much higher genetic diversity in nonhuman primates. We identified 44 new nucleotide variable sites and 14 novel sequence types (STs) among the B. quintana isolates by MLST analysis. Some STs were found only in cynomolgus macaques, while some others were detected only in rhesus macaques, suggesting evidence of host‐cospeciation, which were further confirmed by phylogenetic analysis and Splits decomposition analysis. Our findings suggest that trench fever may primarily be a zoonotic disease with macaques as the natural hosts.

Heavy metal contamination of urban soils and dusts in Guangzhou, South China - Quan-Ying Cai; Ce-Hui Mo; Hai-Qin Li; Huixiong Lü; Qiao-Yun Zeng; Yan-Wen Li; Xiao-Lian Wu (Environmental Monitoring and Assessment, 2013)

An Arabidopsis mutant atcsr-2 exhibits high cadmium stress sensitivity involved in the restriction of H2S emission - Ya-wei Li; Ze-hua Gong; Yao Mu; Yi-xian Zhang; Zeng-jie Qiao; Li-ping Zhang; Zhu-ping Jin; Hua Li; Yan-xi Pei (Journal of Zhejiang University-SCIENCE B, 2012)

Infusion of Endothelial Progenitor Cells Accelerates Hematopoietic and Immune Reconstitution, and Ameliorates the Graft-Versus-Host Disease After Hematopoietic Stem Cell Transplantation - Lingyu Zeng; Chong Chen; Guoliang Song; Zhiling Yan; Shijuan Xu; Lu Jia; Shuang Ding; Jiang Cao; Wei Chen; Hai Cheng; Zhenyu Li; Wei Sang; et al. (Cell Biochemistry and Biophysics, 2012)

Triterpenoid saponins from Ilex mamillata C.Y. Wu ex C.J. Tseng - Che Yan-Yun; Zhang Liang; Li Ning; Zeng Ke-Wu; Tu Peng-Fei (Natural Product Research, 2012)

Two-photon excitation chlorophyll fluorescence lifetime imaging: a rapid and noninvasive method for in vivo assessment of cadmium toxicity in a marine diatom Thalassiosira weissflogii - Yan Zeng; Yun Wu; Dong Li; Wei Zheng; Wen-Xiong Wang; Jianan Y. Qu (Planta, 2012)

Involvement of FGF9/16/20 subfamily in female germ cell development of the Nile tilapia, Oreochromis niloticus - Yun-Lv Sun; Sheng Zeng; Kai Ye; Chao Yang; Ming-Hui Li; Bao-Feng Huang; Li-Na Sun; Lin-Yan Zhou; De-Shou Wang (Fish Physiology and Biochemistry, 2012)

Synoptic-scale disturbances over the northern South China Sea and their responses to El Niño - Lili Zeng; Xixi Li; Yan Du; Rui Shi; Jinglong Yao; Dongxiao Wang; Dandan Sui (Acta Oceanologica Sinica, 2012)

The relationship between species diversity and ecosystem function (productivity) of the late Middle Permian brachiopods community at the region of Hechuan, Chongqing, China - Yong Zeng; LiJun Jiang; Yan Ke; Qian Lü; Li Zhao; JiaDong Liang; Han Hu; Bo Linghu (Science China Earth Sciences, 2012)

Synthesis and antihypertensive activity evaluation in spontaneously hypertensive rats of lacidipine analogues - Zeng-jun Guo; Kai Zhou; Yong-xiao Cao; Yan Li; San-qi Zhang (Medicinal Chemistry Research, 2012)

Value of a new post-procedural intravascular ultrasound score in predicting target vessel revascularization after coronary drug-eluting stents implantation - Kai Xu; Ya-ling Han; Quan-min Jing; Shou-li Wang; Ying-yan Ma; Xiao-zeng Wang; Geng Wang; Zu-lu Wang (Journal of Zhejiang University-SCIENCE B, 2012)

Production of monoclonal antibody and application in indirect competitive ELISA for detecting okadaic acid and dinophytoxin-1 in seafood - Shi-Ying Lu; Yu Zhou; Yan-Song Li; Chao Lin; Xian-Mei Meng; Dong-Ming Yan; Zhao-Hui Li; Shi-Yu Yu; Zeng-Shan Liu; Hong-Lin Ren (Environmental Science and Pollution Research, 2012)

The Influence of Fluoride on the Expression of Inhibitors of Wnt/β-Catenin Signaling Pathway in Rat Skin Fibroblast Cells - Xiao-Li Liu; Chang-Cheng Li; Ke-Jian Liu; Cai-Yan Cui; Yu-Zeng Zhang; Yun Liu (Biological Trace Element Research, 2012)

Occurrence of Nonylphenol and Nonylphenol Monoethoxylate in Soil and Vegetables from Vegetable Farms in the Pearl River Delta, South China - Quan-Ying Cai; Hui-Juan Huang; Huixiong Lü; Ce-Hui Mo; Jun Zhang; Qiao-Yun Zeng; Jun-Jian Tian; Yan-Wen Li; Xiao-Lian Wu (Archives of Environmental Contamination and Toxicology, 2012)

Caffeic acid product from the highly copper-tolerant plant Elsholtzia splendens post-phytoremediation: its extraction, purification, and identification - Yan Xing; Hong-yun Peng; Meng-xi Zhang; Xia Li; Wei-wei Zeng; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2012)

Artificial Cold Wave-Induced Cerebral Infarction in Rats with Carotid Atherosclerosis - Zhen-Yu Tang; Qiu-Yan Zhu; Li-Jun Xu; Li-Ying Deng; Ying Zeng; Wei-Jiang Ding; Wei Huang (Journal of Molecular Neuroscience, 2012)

SIRT1 is required for long-term growth of human mesenchymal stem cells - Hong-Feng Yuan; Chao Zhai; Xin-Long Yan; Dan-Dan Zhao; Jing-Xue Wang; Quan Zeng; Lin Chen; Xue Nan; Li-Juan He; Si-Ting Li; Wen Yue; Xue-Tao Pei (Journal of Molecular Medicine, 2012)

Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Systematic assessment and meta-analysis of the efficacy and safety of fasudil in the treatment of cerebral vasospasm in patients with subarachnoid hemorrhage - Guang Jian Liu; Zheng Jun Wang; Yun Fu Wang; Li Li Xu; Xiao Ling Wang; Yong Liu; Guo Jun Luo; Guo Hou He; Yan Jun Zeng (European Journal of Clinical Pharmacology, 2012)

Erratum to: Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Effect of dirhamnolipid on the removal of phenol catalyzed by laccase in aqueous solution - Zhi-Feng Liu; Guang-Ming Zeng; Hua Zhong; Xing-Zhong Yuan; Hai-Yan Fu; Mei-Fang Zhou; Xiao-Ling Ma; Hui Li; Jian-Bing Li (World Journal of Microbiology and Biotechnology, 2012)

The therapeutic potential of G-CSF in pressure overload induced ventricular reconstruction and heart failure in mice - Ji Ming Li; Zhi Feng Yao; Yun Zeng Zou; Jun Bo Ge; Ai Li Guan; Jian Wu; Shou Ling Mi; Yan Yan Liang; Zhen Ma (Molecular Biology Reports, 2012)

Identification and characterization of SHORTENED UPPERMOST INTERNODE 1, a gene negatively regulating uppermost internode elongation in rice - Li Zhu; Jiang Hu; Keming Zhu; Yunxia Fang; Zhenyu Gao; Yinghong He; Guangheng Zhang; Longbiao Guo; Dali Zeng; Guojun Dong; Meixian Yan; Jian Liu; et al. (Plant Molecular Biology, 2011)

Effects of rhizobial inoculation, cropping systems and growth stages on endophytic bacterial community of soybean roots - Yun Zeng Zhang; En Tao Wang; Mao Li; Qin Qin Li; Yan Ming Zhang; Shuang Jin Zhao; Xiu Ling Jia; Li Hua Zhang; Wen Feng Chen; Wen Xin Chen (Plant and Soil, 2011)

Map-based cloning proves qGC-6, a major QTL for gel consistency of japonica/indica cross, responds by Waxy in rice (Oryza sativa L.) - Yan Su; Yuchun Rao; Shikai Hu; Yaolong Yang; Zhenyu Gao; Guanghen Zhang; Jian Liu; Jiang Hu; Meixian Yan; Guojun Dong; Li Zhu; Longbiao Guo; et al. (Theoretical and Applied Genetics, 2011)

Genetic analysis of starch paste viscosity parameters in glutinous rice (Oryza sativa L.) - Chang-Jie Yan; Zhi-Xi Tian; Yu-Wei Fang; Ya-Chun Yang; Jian Li; Sheng-Yuan Zeng; Shi-Liang Gu; Chen-Wu Xu; Shu-Zhu Tang; Ming-Hong Gu (Theoretical and Applied Genetics, 2011)

Ecotoxicity assessment of aged petroleum sludge using a suite of effects-based end points in earthworm Eisenia fetida - Shi-Jie Wang; Zeng-Guang Yan; Guan-Lin Guo; Gui-Lan Lu; Qun-Hui Wang; Fa-Sheng Li (Environmental Monitoring and Assessment, 2010)

Identification and characterization of NARROW AND ROLLED LEAF 1, a novel gene regulating leaf morphology and plant architecture in rice - Jiang Hu; Li Zhu; Dali Zeng; Zhenyu Gao; Longbiao Guo; Yunxia Fang; Guangheng Zhang; Guojun Dong; Meixian Yan; Jian Liu; Qian Qian (Plant Molecular Biology, 2010)

Effects of precipitation variation on severe acid rain in southern China - Zhiqing Xie; Yin Du; Yan Zeng; Yachun Li; Mingliang Yan; Shengming Jiao (Journal of Geographical Sciences, 2009)

Fluorous Lewis acids and phase transfer catalysts - Chun Cai; Wen-Bin Yi; Wei Zhang; Ming-Gui Shen; Mei Hong; Li-Yan Zeng (Molecular Diversity, 2009)

Factors affecting crop damage by wild boar and methods of mitigation in a giant panda reserve - Jing Cai; Zhigang Jiang; Yan Zeng; Chunwang Li; Benjamin D. Bravery (European Journal of Wildlife Research, 2008)

Ambiguity in a trans-disciplinary stakeholder assessment of neglected and underutilized species in China, Cambodia, Thailand and Vietnam - Markus Schmidt; Wei Wei; Anan Polthanee; Nguyen Thanh Lam; Sophal Chuong; Li-juan Qiu; Poramate Banterng; Pham Thi Dung; Stefan Glaser; Ralph Gretzmacher; Veronika Hager; Edwin de Korte; et al. (Biodiversity and Conservation, 2008)

Solid Substrate–Room Temperature Phosphorimetry for the Determination of Trace Terbutaline Sulfate Based on Its Inhibition Oxidation of Rhodamine 6G by Sodium Periodate - Jia-Ming Liu; Fei Gao; Wen-Yan Gao; Li-Qing Zeng; Xiao-Mei Huang; Zhi-Ming Li; Xiu-Chai Huang; Wei-Nv Lin; Fang-Mei Wang; Chang-Ling Nie (Journal of Fluorescence, 2008)

Expression and characteristic of synthetic human epidermal growth factor (hEGF) in transgenic tobacco plants - Jie-Ying Bai; Lin Zeng; Yuan-Lei Hu; Yan-Fang Li; Zhong-Ping Lin; Shi-Chen Shang; Yan-Sheng Shi (Biotechnology Letters, 2007)

Du1, encoding a novel Prp1 protein, regulates starch biosynthesis through affecting the splicing of Wx b pre-mRNAs in rice (Oryza sativa L.) - Dali Zeng; Meixian Yan; Yonghong Wang; Xinfang Liu; Qian Qian; Jiayang Li (Plant Molecular Biology, 2007)

Genetic variability in relocated Père David’s deer (Elaphurus davidianus) populations—Implications to reintroduction program - Yan Zeng; Zhigang Jiang; Chunwang Li (Conservation Genetics, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Tegaserod for dyspepsia and reflux symptoms in patients with chronic constipation: an exploratory open-label study - Juan Zeng; Xiu-Li Zuo; Yan-Qing Li; Wei Wei; Guo-Ping Lv (European Journal of Clinical Pharmacology, 2007)

Laccase activities of a soil fungus Penicillium simplicissimum in relation to lignin degradation - Guang Ming Zeng; Hong Yan Yu; Hong Li Huang; Dan Lian Huang; Yao Ning Chen; Guo He Huang; Jian Bing Li (World Journal of Microbiology and Biotechnology, 2006)

cDNA cloning and expression analysis of a novel human F-box domain containing gene† - Li Zeng; Shaohua Gu; Yao Li; Wenhu Wang; Yan Huang; Xin Ye; Jian Xu; Enpeng Zhao; Chaoneng Ji; Kang Ying; Yi Xie; Yumin Mao (Molecular Biology Reports, 2004)

Elevational gradients of small mammal diversity on the northern slopes of Mt. Qilian, China - Jun Sheng Li; Yan Ling Song; Zhi Gao Zeng (Global Ecology and Biogeography, 2003)
Aim Small mammal species richness and relative abundance vary along elevational gradients, but there are different patterns that exist. This study reports the patterns of distribution and abundance of small mammals along the broader elevational gradient of Mt. Qilian range. Location The study was conducted in the Mt. Qilian range, north‐western China, from June to August 2001. Methods Removal trapping was conducted using a standardized technique at 7 sites ranging between 1600 and 3900 m elevation within three transects. Correlation, regression and graphical analyses were used to evaluate the diversity patterns along this elevational gradient. Results In total, 586 individuals representing 18 nonvolant small mammal species were collected during 20 160 trap nights. Species composition was different among the three transects with 6 (33%) of the species found only within one transect. Elevational distribution and relative abundance of small rodents showed substantial spatial variation, with only 2 species showing nonsignificant capture frequencies across elevations. Despite these variations, some general patterns of elevational distribution emerged: humped‐shape relationships between species diversity and elevation were noted in all three transects with diversity peaks at middle elevations. In addition, relative abundance was negatively correlated with elevation. Conclusions Results indicate that maximum richness and diversity of nonvolant small mammals occurred at mid‐elevations where several types of plants reached their maximum diversity and primary productivity, and where rainfall and humidity reached a maximum. It is demonstrated that the mid‐elevation bulge is a general feature of at least a large portion of the biota on the Mt. Qilian range.

Molecular cloning and characterization of a novel Dehydrogenase/reductase (SDR family) member 1 genea from human fetal brain - Qihan Wu; Ming Xu; Chao Cheng; Zongxiang Zhou; Yan Huang; Wei Zhao; Li Zeng; Jian Xu; Xuping Fu; Kang Ying; Yi Xie; Yumin Mao (Molecular Biology Reports, 2001)